Component Velocities and Turbulence Intensities within Ship Twin-Propeller Jet Using CFD and ADV - Yonggang Cui; Wei Haur Lam; How Tion Puay; Muhammad S. I. Ibrahim; Desmond Robinson; Gerard Hamill (Journal of Marine Science and Engineering, 2020)
This study presents the decays of three components of velocity for a ship twin-propeller jet associated with turbulence intensities using the Acoustic Doppler Velocimetry (ADV) measurement and computational fluid dynamics (CFD) methods. Previous research has shown that a single-propeller jet consists of a zone of flow establishment and a zone of established flow. Twin-propeller jets are more complex than single-propeller jets, and can be divided into zones with four peaks, two peaks, and one peak. The axial velocity distribution is the main contributor and can be predicted using the Gaussian normal distribution. The axial velocity decay is described by linear equations using the maximum axial velocity in the efflux plane. The tangential and radial velocity decays show linear and nonlinear distributions in different zones. The turbulence intensity increases locally in the critical position of the noninterference zone and the interference zone. The current research converts the axial momentum theory of a single propeller into twin-propeller jet theory with a series of equations used to predict the overall twin-propeller jet structure.

Issue of Accumulation and Redistribution of Oil and Gas Rental Income in the Context of Exhaustible Natural Resources in Arctic Zone of Russian Federation - Natalia Kirsanova; Olga Lenkovets; Muhammad Hafeez (Journal of Marine Science and Engineering, 2020)
The significant resource potential of the Arctic has attracted the attention of its adjacent countries and extra-regional states. The mineral and raw material base of the Arctic Zone of the Russian Federation (AZRF) comprises a wide range of minerals. However, due to its hydrocarbon reserves, the Arctic is considered to be the most important geopolitical and geo-economic macro-region for Russia. A significant portion of the Arctic hydrocarbons (about 19%) is concentrated in the territory of Russia’s shelf. The extraction of Arctic marine oil and gas resources and ensuring the sustainability of the Russian energy complex depend significantly on the level of Arctic development. Thus, the pace and quality of the development of AZRF are strategically important to ensure the national interests of the country. It has been proven that the implementation of the state program for AZRF development and strategic plans of the largest companies operating in the region consolidate the raw material nature of AZRF development. Rent becomes the main form of income. This article addresses the main directions of the region’s development and the factors that prevent a high level of industrialization, which increase attention to the withdrawal and redistribution of rental income. The article considers the Russian and foreign experiences of withdrawal and redistribution of oil and gas rental income, and analyzes the level of socio-economic development of AZRF. The authors suggest a methodology for assessing the impact of a country’s area and population size on the ability to achieve a high income due to hydrocarbons. The authors also explain the principles of rental income redistribution in the region as a basis for improving the level of AZRF’s socio-economic development and as a condition for transition from the “colonial model” of development to the “sustainable development” model. The study results can be used to elaborate a mechanism for rental income redistribution in AZRF and state programs for the region’s development.

Three new guaiane-type sesquiterpenoids and a monoterpenoid from Litsea lancilimba Merr - Ishaq Muhammad; Yong Zhen Xiao; Syed Shams ul Hassan; Xue Xiao; Shi-Kai Yan; Yuan-Qiang Guo; Xian-peng Ma; Hui-Zi Jin (Natural Product Research, 2020)

Comparative secondary metabolites profiling and biological activities of aerial, stem and root parts of Salvadora oleoides decne (Salvadoraceae) - Hammad Saleem; Irshad Ahmad; Gokhan Zengin; Fawzi M. Mahomoodally; Kashif-Ur- Rehman Khan; Hafiz Muhammad Ahsan; Syafiq Asnawi Zainal Abidin; Nafees Ahemad (Natural Product Research, 2020)

Environmental transformation and nano-toxicity of engineered nano-particles (ENPs) in aquatic and terrestrial organisms - Qumber Abbas; Balal Yousaf; Habib Ullah; Muhammad Ubaid Ali; Yong Sik Ok; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2020)

Mechanisms and Signaling Pathways of Salt Tolerance in Crops: Understanding from the Transgenic Plants - Muhammad Zohaib Afzal; Qi Jia; Aminu Kurawa Ibrahim; Sylvain Niyitanga; Liwu Zhang (Tropical Plant Biology, 2020)

Identifying the Optimal Path and Computing the Threshold Pressure for Flow of Bingham Fluids Through Heterogeneous Porous Media - Hamid Didari; Hassan Aghdasinia; Mahdi Salami Hosseini; Fatemeh Ebrahimi; Muhammad Sahimi (Transport in Porous Media, 2020)

Hydropower development along the major rivers basins in South Asia: benefits for Bangladesh - Muhammad Mizanur Rahaman; Mohammad Safayat Hossain (Sustainable Water Resources Management, 2020)

Assessment of drought and wet projections in the humid climatic regions for Pakistan - Hamd Ullah; Muhammad Akbar; Firdos Khan (Stochastic Environmental Research and Risk Assessment, 2020)

Factors Influencing Sleep Quality and Effects of Sleep on Hypertension - Ali Asghar Mirjat; Ali Akbar Mirjat; Muhammad Naveed; Fatima Majeed; Shen Chong (Sleep and Vigilance, 2020)

Prediction Modeling for the Estimation of Dynamic Elastic Young’s Modulus of Thermally Treated Sedimentary Rocks Using Linear–Nonlinear Regression Analysis, Regularization, and ANFIS - Umer Waqas; Muhammad Farooq Ahmed (Rock Mechanics and Rock Engineering, 2020)

Altered baseline and amphetamine-mediated behavioral profiles in dopamine transporter Cre (DAT-Ires-Cre) mice compared to tyrosine hydroxylase Cre (TH-Cre) mice - Muhammad O. Chohan; Sari Esses; Julia Haft; Susanne E. Ahmari; Jeremy Veenstra-VanderWeele (Psychopharmacology, 2020)

Probabilistic Modeling of Earthquake Interevent Times in Different Regions of Pakistan - Muhammad Yousaf Khan; Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah (Pure and Applied Geophysics, 2020)

Modulation of sugar and nitrogen in callus induction media alter PAL pathway, SA and biomass accumulation in rice callus - Rahmatullah Jan; Muhammad Aaqil Khan; Sajjad Asaf; In-Jung Lee; Kyung-Min Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Interactive role of zinc and iron lysine on Spinacia oleracea L. growth, photosynthesis and antioxidant capacity irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Hamzah Saleem; Mohsin Ali; Muhammad Riaz; Sehar Javed; Anam Sehar; Zohaib Abbas; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Physiology and Molecular Biology of Plants, 2020)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Influence of IP-injected ZnO-nanoparticles in Catla catla fish: hematological and serological profile - Tariq Munir; Muhammad Latif; Arslan Mahmood; Arif Malik; Fahad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

IL-6/STAT3 and adipokine modulation using tocilizumab in rats with fructose-induced metabolic syndrome - Haneen Yahia; Azza Hassan; Mona R. El-Ansary; Muhammad Y. Al-Shorbagy; Mohamed F. El-Yamany (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Rockburst Risk Analysis During High-Hard Roof Breaking in Deep Mines - Qiming Zhang; Enyuan Wang; Xiaojun Feng; Yue Niu; Muhammad Ali; Song Lin; Hao Wang (Natural Resources Research, 2020)

Lauric acid alleviates insulin resistance by improving mitochondrial biogenesis in THP-1 macrophages - Yong Yao Tham; Quok Cheong Choo; Tengku Sifzizul Tengku Muhammad; Choy Hoong Chew (Molecular Biology Reports, 2020)

Identification and computational analysis of USH1C, and SLC26A4 variants in Pakistani families with prelingual hearing loss - Muhammad Noman; Shazia A. Bukhari; Sakina Rehman; Muhammad Qasim; Muhammad Ali; Saima Riazuddin; Zubair M. Ahmed (Molecular Biology Reports, 2020)

Synthetic β-hydroxy ketone derivative inhibits cholinesterases, rescues oxidative stress and ameliorates cognitive deficits in 5XFAD mice model of AD - Syed Ilyas Ahmad; Gowhar Ali; Tahir Muhammad; Rahim Ullah; Muhammad Naveed Umar; Aisha Nasir Hashmi (Molecular Biology Reports, 2020)

First evaluation of the population structure, genetic diversity and landscape connectivity of the Endangered Arabian tahr - Steven Ross; Jean-Marc Costanzi; Mansoor Al Jahdhami; Haitham Al Rawahi; Muhammad Ghazali; Helen Senn (Mammalian Biology, 2020)
The Arabian tahr ( Arabitragus jayakari ) occurs only in the mountains of northern Oman and the United Arab Emirates. The species is classified as Endangered due to its small declining population. In this study, we combined genetic and landscape ecology techniques in order to inform landscape scale conservation and genetic management of Arabian tahr. Using 540 base pairs of mitochondrial control region in a dataset of 53 samples, we found eight haplotypes, which fell into two haplogroups. Population genetic analysis using a panel of 14 microsatellite loci also showed a weak, but significant division. Analyses of landscape connectivity supported the genetic results showing poor connectivity between populations in the far south of the study area and those in the north. The most likely location of corridors connecting Arabian tahr populations were identified. Many corridors between tahr populations are impeded by multi-lane highways and restoration of these connections is required to maintain population viability of Arabian tahr. Owing to limited genetic samples outside of Wadi Sareen, further sampling is needed to elucidate both mtDNA and the nuclear structure of Arabian tahr more fully. Our study provides a toolkit that may be used for future genetic and connectivity monitoring of the Arabian tahr population.

Zinc Application in Combination with Zinc Solubilizing Enterobacter sp. MN17 Improved Productivity, Profitability, Zinc Efficiency, and Quality of Desi Chickpea - Aman Ullah; Muhammad Farooq; Faisal Nadeem; Abdul Rehman; Mubshar Hussain; Ahmad Nawaz; Muhammad Naveed (Journal of Soil Science and Plant Nutrition, 2020)

Effect of Vanadium on Growth, Photosynthesis, Reactive Oxygen Species, Antioxidant Enzymes, and Cell Death of Rice - Muhammad Mohsin Altaf; Xiao-ping Diao; Atique ur Rehman; Muhammad Imtiaz; Awais Shakoor; Muhammad Ahsan Altaf; Haseeb Younis; Pengcheng Fu; Muhammad Usman Ghani (Journal of Soil Science and Plant Nutrition, 2020)

Depth Distribution of Bulk and Aggregate-Associated Manganese Oxides Mediated by Soil Chemical Properties in a Long-Term Fertilized Paddy Soil - Christian Kofi Anthonio; Huang Jing; Han Tianfu; Muhammad Qaswar; Liu Kailou; Du Jiangxue; Muhammad Numan Khan; Muhammad Abbas; Sehrish Ali; Lehlogonolo Abner Matelele; Liu Shujun; Liu Guangrong; et al. (Journal of Soil Science and Plant Nutrition, 2020)

Sandy Soil Amended with Clay Soil: Effect of Clay Soil Properties on Soil Respiration, Microbial Biomass, and Water Extractable Organic C - Muhammad Riaz; Petra Marschner (Journal of Soil Science and Plant Nutrition, 2020)

Optimizing Boron Seed Coating Level and Boron-Tolerant Bacteria for Improving Yield and Biofortification of Chickpea - Mubshar Hussain; Noman Mehboob; Muhammad Naveed; Kousar Shehzadi; Tauqeer Ahmad Yasir (Journal of Soil Science and Plant Nutrition, 2020)

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes - Muhammad Aamer; Muhammad Shaaban; Muhammad Umair Hassan; Liu Ying; Tang Haiying; Ma Qiaoying; Hassan Munir; Adnan Rasheed; Li Xinmei; Li Ping; Huang Guoqin (Journal of Soil Science and Plant Nutrition, 2020)

Morpho-physiological Effects and Molecular Mode of Action of Mepiquat Chloride Application in Cotton: A Review - Shahbaz Atta Tung; Ying Huang; Abdul Hafeez; Saif Ali; Anda Liu; Muhammad Sohaib Chattha; Shoaib Ahmad; Guozheng Yang (Journal of Soil Science and Plant Nutrition, 2020)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Molybdenum Application Regulates Oxidative Stress Tolerance in Winter Wheat Under Different Nitrogen Sources - Muhammad Imran; Xuecheng Sun; Saddam Hussain; Usman Ali; Muhammad Shoaib Rana; Fahd Rasul; Shadab Shaukat; Chengxiao Hu (Journal of Soil Science and Plant Nutrition, 2020)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

Effects of Elevated Ammonia Concentration on Corn Growth and Grain Yield Under Different Nitrogen Application Rates - Xiaoli Chen; Xiaolong Ren; Sadam Hussain; Saddam Hussain; Muhammad Saqib (Journal of Soil Science and Plant Nutrition, 2020)

Interactive Effect of Biochar and Silicon on Improving Morpho-Physiological and Biochemical Attributes of Maize by Reducing Drought Hazards - Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Madiha Butt; Muhammad Irfan; Muhammad Shahid Rizwan; Hakoomat Ali; Mumtaz A. Cheema (Journal of Soil Science and Plant Nutrition, 2020)

Foliar Potassium-Induced Regulations in Glycine Betaine and Malondialdehyde Were Associated with Grain Yield of Heat-Stressed Bread Wheat (Triticum aestivum L.) - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Haroon Zaman Khan; Abdul Shakoor (Journal of Soil Science and Plant Nutrition, 2020)

The sedimentological and stratigraphical analysis of the Paleocene to Early Eocene Dungan Formation, Kirthar Fold and Thrust Belt, Pakistan: implications for reservoir potential - Sajjad Ahmad; Bilal Wadood; Suleman Khan; Abd Ullah; Ghazi Mustafa; Muhammad Hanif; Hasbee Ullah (Journal of Sedimentary Environments, 2020)

24-Epibrassinolide Alleviates the Injurious Effects of Cr(VI) Toxicity in Tomato Plants: Insights into Growth, Physio-Biochemical Attributes, Antioxidant Activity and Regulation of Ascorbate–Glutathione and Glyoxalase Cycles - Sumira Jan; Ali Noman; Cengiz Kaya; Muhammad Ashraf; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2020)

Relationship of Nitrogen Deficiency-Induced Leaf Senescence with ROS Generation and ABA Concentration in Rice Flag Leaves - Shamsu Ado Zakari; Muhammad-Asad-Ullah Asad; Zhanyu Han; Qian Zhao; Fangmin Cheng (Journal of Plant Growth Regulation, 2020)

Influence of Extraction Variables on Free Radical Scavenging Potential of Nelumbo nucifera Seed Kernel: Optimization by Response Surface Methodology - Haq Nawaz; Muhammad Aslam Shad; Sabiha Tahir Abbasi (Journal of Pharmaceutical Innovation, 2020)

Synthesis, Structure Study, First-Principles Investigations and Luminescence Properties of Europium and Terbium Complexes - Bakhat Ali; Helio A. Stefani; Muhammad Imran; Ahmad Irfan; Mohammed A. Assiri; Maria Claudia F. C. Felinto; Muhammad Khalid; Abdullah G. Al-Sehemi (Journal of Fluorescence, 2020)

Impact of rainfall intensity, monsoon and MJO to rainfall merging in the Indonesian maritime continent - Giarno; Muhammad Pramono Hadi; Slamet Suprayogi; Sigit Herumurti (Journal of Earth System Science, 2020)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

Enhancement of photocatalytic potential and recoverability of Fe3O4 nanoparticles by decorating over monoclinic zirconia - Idrees Khan; Noor Zada; Ibrahim Khan; Muhammad Sadiq; Khalid Saeed (Journal of Environmental Health Science and Engineering, 2020)

Influence of indigenous plant materials on reproductive performance of Callosobruchus chinensis (L.) (Coleoptera: Bruchidae) on chickpea - Bilawal Nizamani; Mushtaque Ahmed Agha; Qurban Ali; Amjad Hussain; Hakim Manghwar; Muhammad Kamran; Aafaque Ahmed Keerio; Zeeshan Ahmed Solangi; Muhammad Akbar Lashari; Din Muhammad Soomro (International Journal of Tropical Insect Science, 2020)

Diversity of red palm weevil, Rhynchophorus ferrugineus Oliv. (Coleoptera: Curculionidae) in the Kingdom of Saudi Arabia: studies on the phenotypic and DNA barcodes - Sukirno Sukirno; Muhammad Tufail; Khawaja Ghulam Rasool; Mureed Husain; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2020)

Impacts and evaluation of Hormoligosis of some insect growth regulators on Phenacoccus solenopsis (Hemiptera: Pseudococcidae) - Muhammad Idrees; Muhammad Dildar Gogi; Waqar Majeed; Arbab Yaseen; Mubashar Iqbal (International Journal of Tropical Insect Science, 2020)

Molecular identification of sugarcane black bug (Cavelarius excavates) from Pakistan using cytochrome C oxidase I (COI) gene as DNA barcode - Khadim Hussain; Kamran Rashid; Faisal Hafeez; Ikrma Amad; Muhammad Ashraf (International Journal of Tropical Insect Science, 2020)

Management of Tribolium castaneum using synergism between conventional fumigant and plant essential oils - Abdul Khaliq; Muhammad Irfan Ullah; Muhammad Afzal; Sajjad Ali; Asif Sajjad; Akhlaq Ahmad; Samina Khalid (International Journal of Tropical Insect Science, 2020)

Histomorphology of Seminal Vesicles Subsequent to Exogenous Neurokinin B Administration in New Zealand White Rabbits - Zain Ullah; Muhammad Haris Ramzan; Faiqah Ramzan (International Journal of Peptide Research and Therapeutics, 2020)

Pulses Production in Pakistan: Status, Constraints and Opportunities - Aman Ullah; Tariq Mahmud Shah; Muhammad Farooq (International Journal of Plant Production, 2020)

Sowing Date and Hybrid Choice Matters Production of Maize–Maize System - Ghulam Abbas; Shakeel Ahmad; Mubshar Hussain; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Farooq (International Journal of Plant Production, 2020)

Correction to: Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Methanolic extract of Ephedra ciliata promotes wound healing and arrests inflammatory cascade in vivo through downregulation of TNF-α - Hafiza Sidra Yaseen; Muhammad Asif; Malik Saadullah; Mahrukh; Sajid Asghar; Muhammad Usman Shams; Rizwan Rashid Bazmi; Mohammad Saleem; Hafiz Muhammad Yousaf; Maria Yaseen (Inflammopharmacology, 2020)

RETRACTED ARTICLE: Polystichum braunii extracts inhibit Complete Freund’s adjuvant-induced arthritis via upregulation of I-κB, IL-4, and IL-10, downregulation of COX-2, PGE2, IL-1β, IL-6, NF-κB, and TNF-α, and subsiding oxidative stress - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Novel loss-of-function mutations in COCH cause autosomal recessive nonsyndromic hearing loss - Kevin T. Booth; Amama Ghaffar; Muhammad Rashid; Luke T. Hovey; Mureed Hussain; Kathy Frees; Erika M. Renkes; Carla J. Nishimura; Mohsin Shahzad; Richard J. Smith; Zubair Ahmed; Hela Azaiez; et al. (Human Genetics, 2020)

Mapping and predicting subsidence from spatio-temporal regression models of groundwater-drawdown and subsidence observations - Muhammad Zeeshan Ali; Hone-Jay Chu; Thomas J. Burbey (Hydrogeology Journal, 2020)

Recent advances, approaches and challenges in targeting pathways for potential COVID-19 vaccines development - Daniela Calina; Chandan Sarkar; Andreea Letitia Arsene; Bahare Salehi; Anca Oana Docea; Milon Mondal; Muhammad Torequl Islam; Alireza Zali; Javad Sharifi-Rad (Immunologic Research, 2020)

Genetic manipulation of pea (Pisum sativum L.) with Arabidopsisˈs heat shock factor HsfA1d improves ROS scavenging system to confront thermal stress - Zamarud Shah; Arshad Iqbal; Fahim Ullah Khan; Hidayat Ullah Khan; Faran Durrani; Muhammad Zulfiqar Ahmad (Genetic Resources and Crop Evolution, 2020)

Spatially analyzing food consumption inequalities using GIS with disaggregated data from Punjab, Pakistan. - Sana Khushi; Sajid Rashid Ahmad; Ather Ashraf; Muhammad Imran (Food Security, 2020)

Thirty years of trade data suggests population declines in a once common songbird in Indonesia - Boyd T. C. Leupen; Lalita Gomez; Chris R. Shepherd; K. Anne-Isola Nekaris; Muhammad Ali Imron; Vincent Nijman (European Journal of Wildlife Research, 2020)

Potential Risk and Occupational Exposure of Pesticides Among Rice Farmers of a Village Located in Northern Peninsular of Malaysia - Nur Anis Ahmad; Ali Salehabadi; Syahidah Akmal Muhammad; Mardiana Idayu Ahmad (Exposure and Health, 2020)

Inheritance of leaf resistance to Sclerotinia sclerotiorum in Brassica napus and its genetic correlation with cotyledon resistance - Muhammad Azam Khan; Wallace Cowling; Surinder Singh Banga; Ming Pei You; Vikrant Tyagi; Baudh Bharti; Martin J. Barbetti (Euphytica, 2020)

Correction to: Assessing the integration of solar power projects: SWOT-based AHP–F-TOPSIS case study of Turkey - Muhammad Khalid Anser; Muhammad Mohsin; Qaiser Abbas; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Correction to: Optimal oil stockpiling, peak oil, and general equilibrium: case study of South Asia (oil importers) and Middle East (oil supplier) - Muhammad Khalid Anser; Qaiser Abbas; Imran Sharif Chaudhry; Arman Khan (Environmental Science and Pollution Research, 2020)

Elevated exposure to polycyclic aromatic hydrocarbons (PAHs) may trigger cancers in Pakistan: an environmental, occupational, and genetic perspective - Muhammad Yasir Abdur Rehman; Malik Mumtaz Taqi; Imran Hussain; Jawad Nasir; Syed Hussain Haider Rizvi; Jabir Hussain Syed (Environmental Science and Pollution Research, 2020)

Dechlorane Plus as an emerging environmental pollutant in Asia: a review - Mazhar Iqbal Zafar; Sundas Kali; Mehtabidah Ali; Muhammad Asam Riaz; Tayyaba Naz; Muhammad Mazhar Iqbal; Noshin Masood; Kashif Munawar; Bilal Jan; Sohail Ahmed; Amir Waseem; Muhammad Bilal Khan Niazi (Environmental Science and Pollution Research, 2020)

Analyzing extended STIRPAT model of urbanization and CO2 emissions in Asian countries - Misbah Nosheen; Muhammad Ali Abbasi; Javed Iqbal (Environmental Science and Pollution Research, 2020)

Assessment of European and hybrid aspen clones efficiency based on height growth and removal percentage of petroleum hydrocarbons—a field trial - Mir Md Abdus Salam; Muhammad Mohsin; Fahad Rasheed; Muhammad Ramzan; Zikria Zafar; Pertti Pulkkinen (Environmental Science and Pollution Research, 2020)
Soils polluted by organic or inorganic pollutants are an emerging global environmental issue due to their toxic effects. A phytoremediation experiment was conducted to evaluate the extraction potential of three European aspen clones (R2, R3, and R4) and seven hybrid aspen clones (14, 27, 34, 134, 172, 191, and 291) grown in soils polluted with hydrocarbons (includes polycyclic aromatic hydrocarbons (PAH) and total petroleum hydrocarbons (TPH)). Height growth, plant survival rates, and .hydrocarbon removal efficiencies were investigated over a 4-year period at a site in Somerharju, Luumaki Finland, to assess the remediation potential of the clones. Hydrocarbon content in the soil was determined by gas chromatography and mass spectrometry. The results revealed that hybrid aspen clones 14 and 34 and European aspen clone R3 achieved greater height growth (171, 171, and 114 cm, respectively) than the other clones in the study. Further, the greatest removals of PAH (90% at depth 10–50 cm) and (86% at depth 5–10 cm) were observed in plot G15 planted with clone R2. Furthermore, the greatest TPH removal rate at 5–10 cm depth (C 22 –C 40 , 97%; C 10 –C 40 , 96%; and C 10 –C 21 , 90%) was observed in plot 117 with clone 134. However, other clones demonstrated an ability to grow in soils with elevated levels of TPH and PAH, which indicates their tolerance to hydrocarbons and their potential capacity for phytoremediation of hydrocarbon-polluted soils. Our study suggests that European aspen and hybrid aspen clones could be used for the remediation of soils polluted with PAH and TPH.

Does globalization and financial sector development affect environmental quality? A panel data investigation for the Middle East and North African countries - Abdul Majid Awan; Muhammad Azam; Imran Ullah Saeed; Baher Bakhtyar (Environmental Science and Pollution Research, 2020)

Combined application of Bacillus sp. MN-54 and phosphorus improved growth and reduced lead uptake by maize in the lead-contaminated soil - Muhammad Junaid Afzal; Muhammad Imran Khan; Sardar Alam Cheema; Saddam Hussain; Muhammad Anwar-ul-Haq; Muhammad Hayder Ali; Muhammad Naveed (Environmental Science and Pollution Research, 2020)

The role of sense of place, risk perception, and level of disaster preparedness in disaster vulnerable mountainous areas of Gilgit-Baltistan, Pakistan - Garee Khan; Javed Akhter Qureshi; Anwar Khan; Attaullah Shah; Sajid Ali; Iram Bano; Muhammad Alam (Environmental Science and Pollution Research, 2020)

Residual organics removal from manganese electrochemical solution using combined Fenton oxidation process with adsorption over activated carbon - Jingxian Cui; Xueping Li; Yaseen Muhammad; Chongyi Shi; Haibin Li; Haifeng Su (Environmental Science and Pollution Research, 2020)

Measuring education sector resilience in the face of flood disasters in Pakistan: an index-based approach - Ashfaq Ahmad Shah; Zaiwu Gong; Muhammad Ali; Ali Jamshed; Syed Asif Ali Naqvi; Shaista Naz (Environmental Science and Pollution Research, 2020)

Study of occupational exposure to brick kiln emissions on heavy metal burden, biochemical profile, cortisol level and reproductive health risks among female workers at Rawat, Pakistan - Mehwish David; Qurat-Ul-Ain; Muhammad Afzal; Muhammad Shoaib; Faiza Aman; Karen J. Cloete; Naheed Turi; Sarwat Jahan (Environmental Science and Pollution Research, 2020)

Revealing empirical association among ecological footprints, renewable energy consumption, real income, and financial development: a global perspective - Syed Asif Ali Naqvi; Syed Ale Raza Shah; Muhammad Abuzar Mehdi (Environmental Science and Pollution Research, 2020)

The role of financial development, tourism, and energy utilization in environmental deficit: evidence from 20 highest emitting economies - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

Frequency of PPAR-γ, FTO and ABCC8 genetic variation in Pakistani cardiovascular smokers - Kanwal Rehman; Ayesha Tahir; Sania Niaz; Sara Shabbir; Komal Jabeen; Amna Faheem; Muhammad Sajid Hamid Akash (Environmental Science and Pollution Research, 2020)

Characterization and adsorption capacity of modified 3D porous aerogel from grapefruit peels for removal of oils and organic solvents - Muhammad Imran; Ashraful Islam; Muhammad Umair Farooq; Junpei Ye; Panyue Zhang (Environmental Science and Pollution Research, 2020)

Assessment of health and ecological risks of heavy metal contamination: a case study of agricultural soils in Thall, Dir-Kohistan - Irshad Ullah; Allah Ditta; Muhammad Imtiaz; Sajid Mehmood; Muhammad Rizwan; Muhammad Shahid Rizwan; Amin Ullah Jan; Iftikhar Ahmad (Environmental Monitoring and Assessment, 2020)

Emission factors of some common grass species in West Africa - Khadijat Abdulkareem Abdulraheem; Jamiu Adetayo Adeniran; Adeniyi Saheed Aremu; Muhammad-Najeeb O. Yusuf; Jeleel Adekunle Adebisi; Nusirat Aderinsola Sadiku; Oluwatosin Onaopemipo Olofintoye; Abubakar Ismail; Jacob Ademola Sonibare (Environmental Monitoring and Assessment, 2020)

Exploring Water Consumption in Dhaka City Using Instrumental Variables Regression Approaches - Muhammad Shahadat Hossain Siddiquee; Raihan Ahamed (Environmental Processes, 2020)
This paper explores water consumption in Dhaka city for better understanding of its usage, and considers the implications of findings from distributive rationale. Using 459 household survey data collected by BRAC Institute of Governance and Development (BIGD), this study estimates income elasticities of water consumption after controlling the effects of other covariates including wealth-proxies, location, household size, water bill and spatial zones using the instrumental variable regression (IVREG) and instrumental variable quantile regression (IVQREG) approaches. The latter has an additive advantage over the former as the IVQREG provides a more accurate picture of the relationship of water consumption with the income throughout the entire water consumption distribution. Using the fixed pay variable as instrument, findings reveal the strong evidence that income is endogenous. The IVQREG results show that income elasticities are heterogeneous and vary significantly across the water quantiles, implying inequality in water consumption. It also provides strong systematic evidence as income elasticity of water consumption decreases with the increase in percentile. Significant spatial inequality in water consumption from IVREG approach disappears as we use IVQREG. This also strongly supports the systematic evidence obtained. Therefore, it is imperative to introduce different tariff structures among different water consumer groups for bringing equity in water consumption and revenue generation. However, Dhaka Water Supply & Sewerage Authority (DWASA) must ensure smart water meter before implementing such tariff structure as we face severe challenges while measuring residential water consumption.

Optimization of biosurfactant production from chemically mutated strain of Bacillus subtilis using waste automobile oil as low-cost substrate - Muhammad Asgher; Mariam Afzal; Sarmad Ahmad Qamar; Nimrah Khalid (Environmental Sustainability, 2020)

Potentially toxic elements’ occurrence and risk assessment through water and soil of Chitral urban environment, Pakistan: a case study - Inayat ur Rehman; Muhammad Ishaq; Liaqat Ali; Said Muhammad; Imran Ud Din; Muhammad Yaseen; Hameed Ullah (Environmental Geochemistry and Health, 2020)

Quantification and risk assessment of heavy metal build-up in soil–plant system after irrigation with untreated city wastewater in Vehari, Pakistan - Tania Sarwar; Muhammad Shahid; Natasha; Sana Khalid; Ali Haidar Shah; Naveed Ahmad; Muhammad Asif Naeem; Zia ul Haq; Behzad Murtaza; Hafiz Faiq Bakhat (Environmental Geochemistry and Health, 2020)

On the nexus among carbon dioxide emissions, energy consumption and economic growth in G-7 countries: new insights from the historical decomposition approach - Mehmet Balcilar; Zeynel Abidin Ozdemir; Bedriye Tunçsiper; Huseyin Ozdemir; Muhammad Shahbaz (Environment, Development and Sustainability, 2020)

Do technology and structural changes favour environment in Malaysia: an ARDL-based evidence for environmental Kuznets curve - Wajahat Ali; Inam Ur Rahman; Muhammad Zahid; Muhammad Anees Khan; Tafazal Kumail (Environment, Development and Sustainability, 2020)

Economic impact assessment of natural disaster with multi-criteria decision making for interdependent infrastructures - Muhammad Abdullah Khalid; Yousaf Ali (Environment, Development and Sustainability, 2020)

Modelling of seismicity in southern pakistan using GIS techniques - Muhammad Jahangir Khan (Earth Science Informatics, 2020)

Comparison of two model calibration approaches and their influence on future projections under climate change in the Upper Indus Basin - Muhammad Fraz Ismail; Bibi S. Naz; Michel Wortmann; Markus Disse; Laura C. Bowling; Wolfgang Bogacki (Climatic Change, 2020)
This study performs a comparison of two model calibration/validation approaches and their influence on future hydrological projections under climate change by employing two climate scenarios (RCP2.6 and 8.5) projected by four global climate models. Two hydrological models (HMs), snowmelt runoff model + glaciers and variable infiltration capacity model coupled with a glacier model, were used to simulate streamflow in the highly snow and glacier melt–driven Upper Indus Basin. In the first (conventional) calibration approach, the models were calibrated only at the basin outlet, while in the second (enhanced) approach intermediate gauges, different climate conditions and glacier mass balance were considered. Using the conventional and enhanced calibration approaches, the monthly Nash-Sutcliffe Efficiency (NSE) for both HMs ranged from 0.71 to 0.93 and 0.79 to 0.90 in the calibration, while 0.57–0.92 and 0.54–0.83 in the validation periods, respectively. For the future impact assessment, comparison of differences based on the two calibration/validation methods at the annual scale (i.e. 2011–2099) shows small to moderate differences of up to 10%, whereas differences at the monthly scale reached up to 19% in the cold months (i.e. October–March) for the far future period. Comparison of sources of uncertainty using analysis of variance showed that the contribution of HM parameter uncertainty to the overall uncertainty is becoming very small by the end of the century using the enhanced approach. This indicates that enhanced approach could potentially help to reduce uncertainties in the hydrological projections when compared to the conventional calibration approach.

The Relevance of SNPs at 3′UTR Region of CASP7 and miR-371b-5p Associated Diseases: A Computational Analysis - Muhammad Safdar; Sana Zaheer; Rozhgar A. Khailany; Sadaf Parvez; Muhammad Naveed; Piplu Bhuiyan; Mehmet Ozaslan; Rebaz Moatasam; Mustafa S. Al-Attar; Musarrat Abbas Khan; Yasmeen Junejo (Cell Biochemistry and Biophysics, 2020)

Sedimentological attributes of the Middle Jurassic peloids-dominated carbonates of eastern Tethys, lesser Himalayas, Pakistan - Abdus Saboor; Muhammad Haneef; Muhammad Hanif; Muhammad Azhar Farooq Swati (Carbonates and Evaporites, 2020)

Microfacies analysis and depositional environments of the Upper Cretaceous Fort Munro Formation in the Rakhi Nala Section, Sulaiman range, Pakistan - Muhammad Rizwan; Muhammad Hanif; Nowrad Ali; Maqsood Ur Rehman (Carbonates and Evaporites, 2020)

Diagenetic evolution and associated dolomitization events in the middle Jurassic Samana Suk Formation, Lesser Himalayan Hill Ranges, NW Pakistan - Hamad ur Rahim; Mumtaz Muhammad Shah; Mercè Corbella; Dídac Navarro-Ciurana (Carbonates and Evaporites, 2020)

Unraveling the effects of cadmium on growth, physiology and associated health risks of leafy vegetables - Junaid Latif; Javaid Akhtar; Iftikhar Ahmad; Muhammad Mahmood-ur-Rehman; Ghulam Mustafa Shah; Qamaruz Zaman; Tariq Javaid; Zia Ur Rahman Farooqi; Muhammad Shakar; Azka Saleem; Muhammad Rizwan (Brazilian Journal of Botany, 2020)

Effects of Replacing Inorganic with Respective Complexed Glycinate Minerals on Apparent Mineral Bioavailability and Deposition Rate in Tissues of Broiler Breeders - Wanjing Sun; Geng Wang; Xun Pei; Lujie Liu; Zhiping Xiao; Wenjing Tao; Muhammad Umar Yaqoob; Minqi Wang; Mingyan Huai; Lily Li; Wolf Pelletier (Biological Trace Element Research, 2020)

Potential reverse spillover of infectious bursal disease virus at the interface of commercial poultry and wild birds - Rania F. El Naggar; Mohammed A. Rohaim; Muhammad Munir (Virus Genes, 2020)
Recently, multiple spillover events between domesticated poultry and wild birds have been reported for several avian viruses. This phenomenon highlights the importance of the livestock-wildlife interface in the possible emergence of novel viruses. The aim of the current study was to investigate the potential spillover and epidemiological links of infectious bursal disease virus (IBDV) between wild birds and domestic poultry. To this end, twenty-eight cloacal swabs were collected from four species of free-living Egyptian wild birds (i.e. mallard duck, bean goose, white-fronted goose and black-billed magpie). Genetic and phylogenetic analysis of three positive isolates revealed that the IBDV/USC-1/2019 strain clustered with previously reported very virulent IBDV (vvIBDV) Egyptian isolates. Interestingly, two other wild bird-origin isolates (i.e. IBDV/USC-2/2019 and IBDV/USC-3/2019) grouped with a vaccine strain that is being used in commercial poultry. In conclusion, our results revealed the molecular detection of vaccine and vvIBDV-like strains in Egyptian wild birds and highlighted the potential role of wild birds in IBDV epidemiology in disease-endemic regions.

A Review on Traditional Uses and Pharmacological Importance of Genus Elaeagnus Species - Nausheen Nazir; Muhammad Zahoor; Mohammad Nisar (The Botanical Review, 2020)

Over expression of a Chitinase 2 gene from Chinese Wild Strawberry improves resistance to anthracnose disease in transgenic Arabidopsis thaliana - Zhifeng Wen; Jinhui Bai; Lin Wang; Liping Yao; Bilal Ahmad; Muhammad Hanif; Qingxi Chen (Plant Biotechnology Reports, 2020)

Analyzing adaptation strategies for maize production under future climate change in Guanzhong Plain, China - Qaisar Saddique; Huanjie Cai; Jiatun Xu; Ali Ajaz; Jianqiang He; Qiang Yu; Yunfei Wang; Hui Chen; Muhammad Imran Khan; De Li Liu; Liang He (Mitigation and Adaptation Strategies for Global Change, 2020)

Structural changes in carbon dioxide (CO2) emissions in the United Kingdom (UK): an emission multiplier product matrix (EMPM) approach - Yousaf Ali; Rosita Pretaroli; Muhammad Sabir; Claudio Socci; Francesca Severini (Mitigation and Adaptation Strategies for Global Change, 2020)

Exploring the potential of Sentinel-2A satellite data for aboveground biomass estimation in fragmented Himalayan subtropical pine forest - Mobiishir Riaz Khan; Iftikhar Ahmad Khan; Muhammad Hasan Ali Baig; Zheng-jia Liu; Muhammad Irfan Ashraf (Journal of Mountain Science, 2020)

Efficacy of electrolyzed water against bacteria on fresh fish for increasing the shelf-life during transportation and distribution - Alam A. K. M. Nowsad; Nakib Dad Khan; Muhammad Mehedi Hasan; Syed Md Ehsanur Rahman; Toshiyoshi Araki; Takao Yoshimatsu (Journal of Consumer Protection and Food Safety, 2020)

The potential and efficacy of Allium sativum leaf lectin (ASAL) against sap-sucking insect pests of transgenic maize - Muhammad Umar Bhatti; Saman Riaz; Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Iqra Yousaf; Muhammad Tariq; Shahid Murtaza; Idrees Ahmad Nasir; Bushra Tabassum (Biologia, 2020)

Oral supplementation of Ficus religiosa leaf extract adversely affects the selected behavioral aspects of male albino mice - Naheed Akhtar; Shahid Iqbal; Muhammad Faisal Shahzad; Muhammad Latif; Furhan Iqbal (Biologia, 2020)

Simplex-Centroid Design and Artificial Neural Network-Genetic Algorithm for the Optimization of Exoglucanase Production by Penicillium Roqueforti ATCC 10110 Through Solid-State Fermentation Using a Blend of Agroindustrial Wastes - Nájila da Silva Nunes; Lucas Lima Carneiro; Luiz Henrique Sales de Menezes; Marise Silva de Carvalho; Adriana Bispo Pimentel; Tatielle Pereira Silva; Clissiane Soares Viana Pacheco; Iasnaia Maria de Carvalho Tavares; Pedro Henrique Santos; Thiago Pereira das Chagas; Erik Galvão Paranhos da Silva; Julieta Rangel de Oliveira; et al. (BioEnergy Research, 2020)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Microalgae Isolation for Nutrient Removal Assessment and Biodiesel Production - Muhammad Arif; Le Wang; El-Sayed Salama; Mian Sabir Hussain; Xiangkai Li; Mohammed Jalalah; M. S. Al-Assiri; Farid A. Harraz; Min-Kyu Ji; Pu Liu (BioEnergy Research, 2020)

De Novo Assembly and Annotation of the Juvenile Tuber Transcriptome of a Gastrodia elata Hybrid by RNA Sequencing: Detection of SSR Markers - Yunsheng Wang; Muhammad Qasim Shahid; Fozia Ghouri; Faheem Shehzad Baloch (Biochemical Genetics, 2020)

Effect of silicon on tritrophic interaction of cotton, Gossypium hirsutum (Linnaeus), Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) and the predator, Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) - Asim Abbasi; Muhammad Sufyan; Muhammad Jalal Arif; Shahbaz Talib Sahi (Arthropod-Plant Interactions, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

The comparative analysis of essential nutrient fractions in permafrost and different land use systems of Diamer Division, Gilgit-Baltistan - Didar Ahmad; Farhan Hafeez; Muhammad Irshad; Qaisar Mehmood; Adnan Ahmed Tahir; Akhtar Iqbal; Faridullah (Arabian Journal of Geosciences, 2020)

Comparative effects of dietary micro- and nano-scale chitosan on the growth performance, non-specific immunity, and resistance of silver carp Hypophthalmichthys molitrix against Staphylococcus aureus infection - Naima Younus; Amina Zuberi; Tariq Mahmoood; Wasim Akram; Muhammad Ahmad (Aquaculture International, 2020)

Three Planctomycetes isolated from biotic surfaces in the Mediterranean Sea and the Pacific Ocean constitute the novel species Symmachiella dynata gen. nov., sp. nov. and Symmachiella macrocystis sp. nov. - Markus Salbreiter; Muhammad Waqqas; Mareike Jogler; Nicolai Kallscheuer; Sandra Wiegand; Stijn H. Peeters; Anja Heuer; Mike S. M. Jetten; Christian Boedeker; Patrick Rast; Manfred Rohde; Christian Jogler (Antonie van Leeuwenhoek, 2020)
Planctomycetes is a phylum of environmentally important bacteria, which also receive significant attention due to their fascinating cell biology. Access to axenic Planctomycete cultures is crucial to study cell biological features within this phylum in further detail. In this study, we characterise three novel strains, Mal52 T , Pan258 and CA54 T , which were isolated close to the coasts of the islands Mallorca (Spain) and Panarea (Italy), and from Monterey Bay, CA, USA. The three isolates show optimal growth at temperatures between 22 and 24 °C and at pH 7.5, divide by polar budding, lack pigmentation and form strong aggregates in liquid culture. Analysis of five phylogenetic markers suggests that the strains constitute two novel species within a novel genus in the family Planctomycetaceae . The strains Mal52 T (DSM 101177 T = VKM B-3432 T ) and Pan258 were assigned to the species Symmachiella dynata gen nov., sp. nov., while strain CA54 T (DSM 104301 T = VKM B-3450 T ) forms a separate species of the same genus, for which we propose the name Symmachiella macrocystis sp. nov.

Rosistilla oblonga gen. nov., sp. nov. and Rosistilla carotiformis sp. nov., isolated from biotic or abiotic surfaces in Northern Germany, Mallorca, Spain and California, USA - Muhammad Waqqas; Markus Salbreiter; Nicolai Kallscheuer; Mareike Jogler; Sandra Wiegand; Anja Heuer; Patrick Rast; Stijn H. Peeters; Christian Boedeker; Mike S. M. Jetten; Manfred Rohde; Christian Jogler (Antonie van Leeuwenhoek, 2020)
Planctomycetes are ubiquitous bacteria with fascinating cell biological features. Strains available as axenic cultures in most cases have been isolated from aquatic environments and serve as a basis to study planctomycetal cell biology and interactions in further detail. As a contribution to the current collection of axenic cultures, here we characterise three closely related strains, Poly24 T , CA51 T and Mal33, which were isolated from the Baltic Sea, the Pacific Ocean and the Mediterranean Sea, respectively. The strains display cell biological features typical for related Planctomycetes, such as division by polar budding, presence of crateriform structures and formation of rosettes. Optimal growth was observed at temperatures of 30–33 °C and at pH 7.5, which led to maximal growth rates of 0.065–0.079 h −1 , corresponding to generation times of 9–11 h. The genomes of the novel isolates have a size of 7.3–7.5 Mb and a G + C content of 57.7–58.2%. Phylogenetic analyses place the strains in the family Pirellulaceae and suggest that Roseimaritima ulvae and Roseimaritima sediminicola are the current closest relatives. Analysis of five different phylogenetic markers, however, supports the delineation of the strains from members of the genus Roseimaritima and other characterised genera in the family. Supported by morphological and physiological differences, we conclude that the strains belong to the novel genus Rosistilla gen. nov. and constitute two novel species, for which we propose the names Rosistilla carotiformis sp. nov. and Rosistilla oblonga sp. nov. (the type species). The two novel species are represented by the type strains Poly24 T (= DSM 102938 T = VKM B-3434 T = LMG 31347 T = CECT 9848 T ) and CA51 T (= DSM 104080 T = LMG 29702 T ), respectively.

A brief review of socio-economic and environmental impact of Covid-19 - Muhammad Farhan Bashir; Benjiang MA; Luqman Shahzad (Air Quality, Atmosphere & Health, 2020)

Retraction Note to: Impact of Drought Stress on Some Grain Quality Traits in Rice (Oryza sativa) - Zulqarnain Haider; Umar Farooq; Imad Naseem; Samta Zia; Muhammad Alamgeer (Agricultural Research, 2020)

A review on phyto pharmacological, botanical and marketed formulation studies of Anethum sowa - Sangeeta Singh; Mohammad Khalid; Muhammad Arif; Farogh Ahsan (Advances in Traditional Medicine, 2020)

Exogenous calcium mitigates heat stress effects in common bean: a coordinated impact of photoprotection of PSII, up-regulating antioxidants, and carbohydrate metabolism - Muhammad Naeem; Jesse Riaz Traub; Habib-ur-Rehman Athar; Wayne Loescher (Acta Physiologiae Plantarum, 2020)

Improving ANN-based streamflow estimation models for the Upper Indus Basin using satellite-derived snow cover area - Muhammad Hassan; Ishtiaq Hassan (Acta Geophysica, 2020)

Phylogenomics and species delimitation for effective conservation of manta and devil rays - Jane Hosegood; Emily Humble; Rob Ogden; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Mohammed Abudaya; Kim Bassos‐Hull; Ramon Bonfil; Daniel Fernando; Andrew D. Foote; Helen Hipperson; et al. (Molecular Ecology, 2020)
Practical biodiversity conservation relies on delineation of biologically meaningful units. Manta and devil rays (Mobulidae) are threatened worldwide, yet morphological similarities and a succession of recent taxonomic changes impede the development of an effective conservation strategy. Here, we generate genome‐wide single nucleotide polymorphism (SNP) data from a geographically and taxonomically representative set of manta and devil ray samples to reconstruct phylogenetic relationships and evaluate species boundaries under the general lineage concept. We show that nominal species units supported by alternative data sources constitute independently evolving lineages, and find robust evidence for a putative new species of manta ray in the Gulf of Mexico. Additionally, we uncover substantial incomplete lineage sorting indicating that rapid speciation together with standing variation in ancestral populations has driven phylogenetic uncertainty within Mobulidae. Finally, we detect cryptic diversity in geographically distinct populations, demonstrating that management below the species level may be warranted in certain species. Overall, our study provides a framework for molecular genetic species delimitation that is relevant to wide‐ranging taxa of conservation concern, and highlights the potential for genomic data to support effective management, conservation and law enforcement strategies.

Activin A affects feeding by promoting the inner diameter and muscle development of the pharynx and oesophagus in zebrafish ( Danio rerio ) larvae - Shulin Tang; Xu‐Fang Liang; Shan He; Muhammad Shoaib Alam; Haocan Luo; Yulan Kuang (Journal of Fish Biology, 2020)
Activin A belongs to the superfamily of transforming growth factor‐β and plays an important role in hormone regulation and tissue development. However, few research studies have been conducted on the effect of activin A on feeding organs in fish. In this study, the zebrafish ( Danio rerio ) larvae were treated with 1 ng ml –1 activin A for 8 days continuously. The haematoxylin and eosin (H&E) staining section results revealed that the transverse inner diameter of the pharynx and oesophagus significantly increased on the third and eighth days after treatment compared with the control group ( P 2 compared to the control group ( P in situ hybridization results also showed that the expression of skeletal muscle‐specific genes ( myog and myod ) was significantly increased in pharyngeal muscle on the eighth day. Furthermore, the qRT‐PCR results showed the expression of gh gene was significantly increased on the eighth day ( P Artemia ) than in the control group on the eighth day. In conclusion, activin A could affect feeding by promoting the inner diameter and muscle development of the pharynx and oesophagus in zebrafish larvae. This study is the first to report that the development of the pharynx and oesophagus can directly affect food intake in fish larvae, which provides a theoretical basis for the study of food intake of fish at an early stage.

Investment profitability and economic efficiency of the drip irrigation system: Evidence from Egypt * - Abdelrahman Ali; Chunping Xia; Cheng Jia; Muhammad Faisal (Irrigation and Drainage, 2020)
Modern irrigation systems are key to improving the productivity of water and land units. This study assesses the economic aspects of the drip irrigation system (DIS) by calculating the investment profitability and economic efficiency of the DIS for growing tomatoes in Egypt. One hundred tomato farmers were surveyed. Financial discounted criteria were used in addition to data envelopment analysis to estimate the economic efficiency of growing tomatoes using the DIS. The results showed that investment in the DIS is lucrative, with an increase of 67% in the net return per hectare, compared with results using non‐drip irrigation. The benefit–cost ratio amounted to 1.35, the net present value was US$1720, and the internal rate of return was 44%. The data envelopment analysis results revealed that most farms achieved technical and allocative efficiencies; however, cost and scale efficiencies still need improvement. These results could guide policymakers when designing irrigation transformation strategies that involve the use of micro‐credit to encourage small farmers to change from conventional irrigation systems to DISs. Agricultural extension agencies should organize intensive training programmes for small farmers on how to operate and maintain the DIS. These policies will accelerate the adoption of irrigation modernization and help vulnerable farmers maximize productivity and achieve sustainability in the use of limited resources.

Assessing inflow variability at rim stations of the Indus Basin Irrigation System * - Yasir Abbas; Noor Muhammad Khan; Habib‐Ur‐Rehman Mughal; Khalid Mahmood (Irrigation and Drainage, 2020)
Having one of the largest interconnected irrigation systems in the world, the distribution of irrigation water in Pakistan is largely dependent on river supplies. Seasonal planning of water distribution in the country ignores day‐to‐day inflow variability which impacts water distribution operations. This study has been carried out to assess the inflow variability at four rim stations of the Indus Basin Irrigation System (IBIS) in Pakistan, namely: Kabul River at Noshera, Indus River at Tarbela, Jhelum River at Mangla, and Chenab River at Marala. Nine vital hydrological parameters, depicting various aspects of variability, were computed using 24 years of daily inflow time series. Analysis indicated that Mangla and Marala stations depicted more instances of high flow pulses, which highlighted their flashy nature compared to Noshera and Tarbela whose contributions were mainly from snowmelt. Mangla and Marala stations also depicted higher variations in terms of number and duration of low flow pulses, whereas least low flow variations were observed at Tarbela. Assessment of variability indicated that Tarbela exhibited minimum variations in inflows in the months of October to January, while Marala showed highest inflow variations among all stations in the same months. This study identified successfully the critical months of high flow variability, in addition to identification of the climate shift in the region—two aspects that need attention in future planning and operations.

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

Mechanistic Approaches of Internalization, Subcellular Trafficking, and Cytotoxicity of Nanoparticles for Targeting the Small Intestine - Asadullah Madni; Sadia Rehman; Humaira Sultan; Muhammad Muzamil Khan; Faiz Ahmad; M. Rafi Raza; Nadia Rai; Farzana Parveen (AAPS PharmSciTech, 2020)

Predicting peak summer monsoon precipitation over Pakistan in ECMWF SEAS5 and North American Multimodel Ensemble - Muhammad Azhar Ehsan; Michael K. Tippett; Fred Kucharski; Mansour Almazroui; Muhammad Ismail (International Journal of Climatology, 2020)
The potential and actual forecast skill of peak summer monsoon precipitation (July–August [JA]) over the core summer monsoon region of Pakistan (CSMRP: 68°–76°E, 30°–36°N) is investigated. The predictions from the latest version of the European Centre for Medium‐Range Weather Forecast System5 (SEAS5) and the North American Multimodel Ensemble (NMME) initialized in the beginning of June, May, and April are utilized. The potential skill is estimated by signal‐to‐noise ratio and perfect model correlation. The forecast skill is evaluated using the temporal anomaly correlation as well as the ranked probability skill score for probabilistic forecasts. The SEAS5 generally captures the observed climatological mean and variability patterns of peak summer monsoon precipitation over the region, with some biases mainly located over the complex topography zones. Observed SST anomalies in the El Niño–Southern Oscillation (ENSO) region are negatively correlated with observed peak summer monsoon precipitation over the region. The ENSO–precipitation connection is weakly reproduced in SEAS5 at Lead‐1 and fades gradually with increasing lead time. The potentially predictable component (signal) is small compared to the unpredictable part (noise). Nonetheless, statistically significant potential skill is found over the CSMRP. However, the forecast skill of peak summer monsoon precipitation over the region is lower than the potential skill in SEAS5. A multimodel ensemble average of five models shows little benefit in predicting peak monsoon precipitation over Pakistan. Extended spatial averaging has some impact on the skill; however, temporal averaging has no effect on the skill of the summer monsoon precipitation in SEAS5. Together these results show limitations of the current seasonal prediction models and demonstrate their inadequate performance in predicting peak summer monsoon precipitation over Pakistan.

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Interaction of the surface bound antimicrobial peptides melimine and Mel4 with Staphylococcus aureus - Muhammad Yasir; Debarun Dutta; Naresh Kumar; Mark D. P. Willcox (Biofouling, 2020)

Decoupled Hydrodynamic Models and Their Outdoor Identification for an Unmanned Inland Cargo Vessel with Embedded Fully Rotatable Thrusters - Gerben Peeters; Senne Van Baelen; Gökay Yayla; Tim Catoor; Muhammad Raheel Afzal; Christos Christofakis; Robrecht Louw; Yogang Singh; Maarten Vanierschot; René Boonen; Peter Slaets (Journal of Marine Science and Engineering, 2020)
Expanding the automation level of the freshly introduced fleet of self-propelled Watertruck+ barges, which house fully-rotatable embedded thrusters, might increase their ability to compete with their less sustainable but dominating road-based alternatives. Hydrodynamic motion models, which reveal the manoeuvring capabilities of these barges, can serve as inputs for many pieces of this automation puzzle. No identified motion models or hydrodynamic data seem to be publicly available for the hull design and the novel actuation system configuration of these barges. Therefore, this study offers: (i) decoupled motion model structures for these barges for surge, sway, and yaw, with a focus on the thruster and damping models; (ii) two identification procedures to determine these motion models; (iii) all the experimental data, generated outdoors with a scale model barge to identify (i) based on (ii). In addition, the identified surge models were compared with both computational and empirical data. These comparisons offer more physical insights into the identified model structures and can aid in the model selection for which the desired complexity and accuracy evidently depend on their envisaged application. Finally, this methodology need not be limited to the vessel and actuation types utilised by us.

Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Muhammad Zubair Ghouri; Muhammad Ismail; Muhammad Asif Javed; Sultan Habibullah Khan; Nayla Munawar; Abdullah Bin Umar; Mehr-un-Nisa; Syed Ovais Aftab; Shazia Amin; Zulqurnain Khan; Aftab Ahmad (Frontiers in Marine Science, 2020)

Effects of different light durations during incubation on hatching, subsequent growth, welfare, and meat quality traits among three broiler strains - Rao Muhammad Kashif Yameen; Jibran Hussain; Athar Mahmud; Saima (Tropical Animal Health and Production, 2020)

Pregnancy status and thyroid function in semi-intensive-kept Marecha she-camels (Camelus dromedarius): managerial implications - Asim Faraz; Carlos Iglesias Pastrana; Annamaria Passantino; Ayman Balla Mustafa; Abdul Waheed; Nasir Ali Tauqir; Muhammad Shahid Nabeel (Tropical Animal Health and Production, 2020)

Spirulina inclusion levels in a broiler ration: evaluation of growth performance, gut integrity, and immunity - Sarzamin Khan; Muhammad Mobashar; Farid Khan Mahsood; Shahbaz Javaid; A. A. Abdel-Wareth; Haq Ammanullah; Asif Mahmood (Tropical Animal Health and Production, 2020)

Effect of increasing pre-pubertal concentrate levels on reproductive and lactation performance of Nili-Ravi Buffalo heifers - Muhammad Saadullah; Zeeshan Muhammad Iqbal; Muhammad Naveed-ul-Haque; Hifzulrahman; Jalees Ahmed Bhatti; Muhammad Abdullah (Tropical Animal Health and Production, 2020)

TaCKX gene family, at large, is associated with thousand-grain weight and plant height in common wheat - Muhammad Shoaib; Wenlong Yang; Qiangqiang Shan; Linhe Sun; Dongzhi Wang; Muhammad Sajjad; Xin Li; Jiazhu Sun; Dongcheng Liu; Kehui Zhan; Aimin Zhang (Theoretical and Applied Genetics, 2020)

Evaluating the relationship between climate variability and agricultural crops under indeterminacy - Azhar Ali Janjua; Muhammad Aslam; Naheed Sultana (Theoretical and Applied Climatology, 2020)

Effect of anti-fungal compound phytosphingosine in wheat root exudates on the rhizosphere soil microbial community of watermelon - Chunxia Li; Qing Tian; Muhammad Khashi u Rahman; Fengzhi Wu (Plant and Soil, 2020)

Characterization of dimethoate resistance in Oxycarenus hyalinipennis (Costa): resistance selection, cross-resistance to three insecticides and mode of inheritance - Ansa Banazeer; Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad (Phytoparasitica, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

RETRACTED ARTICLE: Property market price response to flood-hazard - Muhammad Najib Razali; Siti Hafsah Zulkarnain; Zakri Tarmidi; Nurul Hana Adi Maimun; Yasmin Mohd. Adnan; Muhamad Ali Yuzir (Natural Hazards, 2020)

A comparative phylogenomic analysis of SARS-CoV-2 strains reported from non-human mammalian species and environmental samples - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Muhammad Waqar Aziz; Saima Yaqub; Asif Mehmood; Muhammad Asif Raza; Muhammad Zubair Shabbir (Molecular Biology Reports, 2020)

Peronosclerospora australiensis is a synonym of P. maydis, which is widespread on Sumatra, and distinct from the most prevalent Java maize downy mildew pathogen - Radix Suharjo; I. Gede Swibawa; Joko Prasetyo; Yuyun Fitriana; Yanuar Danaatmadja; Ari Budiawan; Sean Roberts; Nanin Noorhajati; Muhammad Amad; Marco Thines (Mycological Progress, 2020)
This study was performed to identify Peronosclerospora species found in Indonesia based on sequence analysis of the cox 2 gene. In addition, sequence data in total, 26 isolates of Peronosclerospora were investigated in this study. They were obtained from 7 provinces in Indonesia, namely Lampung, Jawa Timur, Jawa Barat, Sumatera Utara, Jawa Tengah, Yogyakarta, and Sulawesi Selatan. Sequence analysis of cox 2 and phylogenetic inference were performed on all the 26 isolates. A set of primers developed in this study, PCOX2F and PCOX2R, was used for PCR amplification. Phylogenetic analyses showed that all the Indonesian isolates were divided into two groups. Group I contained 13 isolates; 9 isolates obtained from Lampung, 3 isolates from Sumatera Utara, and 1 isolate from Jawa Barat. Group II consisted of 13 isolates; 7 isolates from Jawa Timur, 2 isolates from Jawa Tengah, 1 isolate from Yogyakarta, and 3 isolates from Sulawesi Selatan. All the members of group I clustered with the ex-type sequence of P. australiensis . Meanwhile, all members of Group II formed the sister clade of isolates obtained from Timor-Leste and may represent P. maydis .

Identification of significant risks in pediatric acute lymphoblastic leukemia (ALL) through machine learning (ML) approach - Nasir Mahmood; Saman Shahid; Taimur Bakhshi; Sehar Riaz; Hafiz Ghufran; Muhammad Yaqoob (Medical & Biological Engineering & Computing, 2020)

Sponges in shallow tropical and temperate reefs are important habitats for marine invertebrate biodiversity - Ying-Yueh Chin; Jane Prince; Gary Kendrick; Muhammad Azmi Abdul Wahab (Marine Biology, 2020)

Incorporated maize residues will induce more accumulation of new POC in HF compared with that in LF soils: a comparison of different residue types - Yang Wang; Shuangyi Li; Yingde Xu; Ming Li; Te Shan; Weijun Zhang; Xu Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2020)

First report of apple mosaic virus in peach in Pakistan - Azhar Ul Islam; Muhammad Wahaj Javed; Muhammad Akram; Javed Rahman; Muhammad Tahir; Muhammad Farooq Hussain Munis; Abu Bakr Umer Farooq (Journal of Plant Pathology, 2020)

First report of Curvularia verruculosa causing leaf spot disease of grape (Vitis vinifera) in Afghanistan - Nasir Ahmed Rajput; Hussainullah; Chao Huo; JiFen Cao; Muhammad Atiq; Rana Muhammad Atif; Abdul Mubeen Lodhi; Rehana Naz Syed; Sohaib Sarfraz; Akhtar Hameed; Zhijian Zhao (Journal of Plant Pathology, 2020)

First report of root rot caused by Ceratobasidium sp. AG-Fa on Capsicum annuum in Pakistan - Aliya Tariq; Farah Naz; Muhammad Shahid; Amjad Shahzad Gondle; Abdul Sattar; Muhammad Nabeel; Zobia Jabeen; Imran Hassan (Journal of Plant Pathology, 2020)

First report of Fusarium equiseti causing stem rot disease of grape (Vitis vinifera L.) in Afghanistan - Nasir Ahmed Rajput; Bakhat Zaman; Chao Huo; JiFen Cao; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Babar Khan; Owais Iqbal; Zhijian Zhao (Journal of Plant Pathology, 2020)

Evaluation of rapid polymyxin Nordmann Poirel test for detection of polymyxin resistance in clinical isolates of Enterobacteriaceae - Muhammad Shoaib; Ashfaq Hussain; Luqman Satti; Wajid Hussain; Gohar Zaman; Faisal Hanif (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Correction to: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Correction to: A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Environmental toxicology and associated human health risks - Muhammad Shahid; Muhammad Nadeem; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2020)

Biogeochemical transformation of greenhouse gas emissions from terrestrial to atmospheric environment and potential feedback to climate forcing - Awais Shakoor; Fatima Ashraf; Saba Shakoor; Adnan Mustafa; Abdul Rehman; Muhammad Mohsin Altaf (Environmental Science and Pollution Research, 2020)

Impact assessment of urban development patterns on land surface temperature by using remote sensing techniques: a case study of Lahore, Faisalabad and Multan district - Muhammad Sajid Saleem; Sajid Rashid Ahmad; Shafiq-Ur-Rehman; Muhammad Asif Javed (Environmental Science and Pollution Research, 2020)

Preserving wheat grain quality and preventing aflatoxin accumulation during storage without pesticides using dry chain technology - Muhammad Amir Bakhtavar; Irfan Afzal (Environmental Science and Pollution Research, 2020)

Heavy metal contamination and exposure risk assessment via drinking groundwater in Vehari, Pakistan - Sana Khalid; Muhammad Shahid; Natasha; Ali Haidar Shah; Farhan Saeed; Mazhar Ali; Saeed Ahmad Qaisrani; Camille Dumat (Environmental Science and Pollution Research, 2020)

Analyzing the linkage between military spending, economic growth, and ecological footprint in Pakistan: evidence from cointegration and bootstrap causality - Zahoor Ahmed; Muhammad Wasif Zafar; Sadia Mansoor (Environmental Science and Pollution Research, 2020)

The sorbed mechanisms of engineering magnetic biochar composites on arsenic in aqueous solution - Zulqarnain Haider Khan; Minling Gao; Weiwen Qiu; Muhammad Qaswar; Md. Shafiqul Islam; Zhengguo Song (Environmental Science and Pollution Research, 2020)

Determinants of the ecological footprint in Thailand: the influences of tourism, trade openness, and population density - Nattapan Kongbuamai; Muhammad Wasif Zafar; Syed Anees Haider Zaidi; Yun Liu (Environmental Science and Pollution Research, 2020)

The impact of macroeconomic and financial development on carbon dioxide emissions in Pakistan: evidence with a novel dynamic simulated ARDL approach - Muhammad Imran Khan; Jian Zhou Teng; Muhammad Kamran Khan (Environmental Science and Pollution Research, 2020)

Modeling smallholder livestock herders’ intentions to adopt climate smart practices: An extended theory of planned behavior - Muhammad Faisal; Xia Chunping; Shoaib Akhtar; Muhammad Haseeb Raza; Muhammad Tariq Iqbal Khan; Muhammad Arslan Ajmal (Environmental Science and Pollution Research, 2020)

An empirical nexus between economic growth, energy utilization, trade policy, and ecological footprint: a continent-wise comparison in upper-middle-income countries - Muhammad Usman; Rakhshanda Kousar; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

Risk assessment of heavy metal(loid)s via Spinacia oleracea ingestion after sewage water irrigation practices in Vehari District - Aneeza Sardar; Muhammad Shahid; Natasha; Sana Khalid; Hasnain Anwar; Muhammad Tahir; Ghulam Mustafa Shah; Muhammad Mubeen (Environmental Science and Pollution Research, 2020)

Green purchase behavior towards green housing: an investigation of Bangladeshi consumers - Israt Zahan; Shuai Chuanmin; Madiha Fayyaz; Muhammad Hafeez (Environmental Science and Pollution Research, 2020)

Evaluation of the Swat River, Northern Pakistan, water quality using multivariate statistical techniques and water quality index (WQI) model - Shah Jehan; Ihsan Ullah; Sardar Khan; Said Muhammad; Seema Anjum Khattak; Tariq Khan (Environmental Science and Pollution Research, 2020)
This study evaluates the characteristics of water along the Swat River, Northern Pakistan. For this purpose, water samples ( n = 30) were collected and analyzed for physicochemical parameters including heavy metals (HM). The mean concentrations of physicochemical parameters and HM were within the drinking water guideline values set by the World Health Organization (WHO 2011) except 34%, 60%, and 56% of copper (Cu), nickel (Ni), and lead (Pb), respectively. Pollution sources were identified by various multivariate statistical techniques including correlation analysis (CA) and principal component analysis (PCA) indicating different origins both naturally and anthropogenically. Results of the water quality index (WQI) ranged from 13.58 to 209 with an average value of 77 suggesting poor water quality for drinking and domestic purposes. The poor water quality was mainly related to high sodium (alkalinity) and salinity hazards showing > 27% and 20% water samples have poor alkalinity and salinity hazards, respectively. Hazard quotient (HQ) and hazard index (HI) were used to determine the health risk of HM in the study area. For water-related health risk, HQ ingestion , HQ dermal , and HI values were > 1, indicating noncarcinogenic health risk (NCR) posed by these HM to the exposed population.

Identification of irrigation potential areas, using multi-criteria analysis in Khyber District, Pakistan - Muhammad Waleed; Sajid Rashid Ahmad; Muhammad Asif Javed; Saifullah Samiullah (Environmental Science and Pollution Research, 2020)

Influence of metallic species for efficient photocatalytic water disinfection: bactericidal mechanism of in vitro results using docking simulation - Aaima Iftikhar; Muhammad Saqib Khan; Umer Rashid; Qaisar Mahmood; Habiba Zafar; Muhammad Bilal; Nadia Riaz (Environmental Science and Pollution Research, 2020)

Enhanced uptake of Cd, Cr, and Cu in Catharanthus roseus (L.) G.Don by Bacillus cereus: application of moss and compost to reduce metal availability - Muhammad Umair Mushtaq; Ameena Iqbal; Ismat Nawaz; Cyrus Raza Mirza; Sohail Yousaf; Ghazanfar Farooq; Muhammad Arif Ali; Aqib Hassan Ali Khan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Comparative efficacy of mitigation techniques for the detoxification of Prunus persica (L.) from selected pesticide residues - Neelab; Muhammad Rafique Asi; Sundas Kali; Muhammad Asam Riaz; Amir Waseem; Muhammad Mazhar Iqbal; Nauman Ahmad; Mazhar Iqbal; Noshin Masood; Mazhar Iqbal Zafar (Environmental Science and Pollution Research, 2020)

Environmental concerns and switching toward electric vehicles: geographic and institutional perspectives - Aqsa Sajjad; Fahad Asmi; Jianxun Chu; Muhammad Azfar Anwar (Environmental Science and Pollution Research, 2020)

Foliar application of lead and arsenic solutions to Spinacia oleracea: biophysiochemical analysis and risk assessment - Natasha; Muhammad Shahid; Sana Khalid (Environmental Science and Pollution Research, 2020)

Lead availability and phytoextraction in the rhizosphere of Pelargonium species - Maria Manzoor; Iram Gul; Aamir Manzoor; Usman Rauf Kamboh; Kiran Hina; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Developing the first halophytic turfgrasses for the urban landscape from native Arabian desert grass - Muhammad Zamin; Shah Fahad; Abdul Mateen Khattak; Muhammad Adnan; Fazli Wahid; Ahmad Raza; Depeng Wang; Shah Saud; Muhammad Noor; Hafiz Faiq Bakhat; Muhammad Mubeen; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2020)

Dietary intake assessment of pyrethroid residues from okra and eggplant grown in peri-urban areas of Punjab, Pakistan - Adnan Amjad; Muhammad Atif Randhawa; Muhammad Sameem Javed; Zafarullah Muhammad; Mussawar Ashraf; Zulfiqar Ahmad; Shamas Murtaza (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Halotolerant potassium solubilizing plant growth promoting rhizobacteria may improve potassium availability under saline conditions - Muhammad Ashfaq; Hasnuri Mat Hassan; Amir Hamzah Ahmad Ghazali; Maqshoof Ahmad (Environmental Monitoring and Assessment, 2020)

Spatial distribution of microplastics in soil with context to human activities: a case study from the urban center - Anam Rafique; Muhammad Irfan; Mehvish Mumtaz; Abdul Qadir (Environmental Monitoring and Assessment, 2020)

Fabrication, functionalization and performance of doped photocatalysts for dye degradation and mineralization: a review - Ackmez Mudhoo; Sonam Paliya; Prittam Goswami; Mukesh Singh; Giusy Lofrano; Maurizio Carotenuto; Federica Carraturo; Giovanni Libralato; Marco Guida; Muhammad Usman; Sunil Kumar (Environmental Chemistry Letters, 2020)

Projection of vegetation impacts on future droughts over West Africa using a coupled RegCM-CLM-CN-DV - Muhammad Shafqat Mehboob; Yeonjoo Kim; Jaehyeong Lee; Myoung-Jin Um; Amir Erfanian; Guiling Wang (Climatic Change, 2020)

Climate change impacts and adaptations for wheat employing multiple climate and crop modelsin Pakistan - Jamshad Hussain; Tasneem Khaliq; Senthold Asseng; Umer Saeed; Ashfaq Ahmad; Burhan Ahmad; Ishfaq Ahmad; Muhammad Fahad; Muhammad Awais; Asmat Ullah; Gerrit Hoogenboom (Climatic Change, 2020)

Analysis and Human Health Risk from Selected Heavy Metals in Common Instant Noodles - Muhammad Idrees (Biological Trace Element Research, 2020)

Heavy Metals Level, Health Risk Assessment Associated with Contamination of Black Tea; A Case Study from Khyber Pakhtunkhwa (KPK), Pakistan - Muhammad Idrees; Fazal Akbar Jan; Shah Hussain; Abdul Salam (Biological Trace Element Research, 2020)

Investigation of Amounts of Vitamins, Lycopene, and Elements in the Fruits of Opuntia ficus-indica Subjected to Different Pretreatments - Büşra Bakar; Meltem Çakmak; Muhammad Salihu Ibrahim; Dursun Özer; Sinan Saydam; Fikret Karatas (Biological Trace Element Research, 2020)

Morphology and composition of the midgut bacterial community of Scaptocoris castanea Perty, 1830 (Hemiptera: Cydnidae) - Jamile Fernanda Silva Cossolin; Déborah Romaskevis Gomes Lopes; Luis Carlos Martínez; Helen Cristina Pinto Santos; Muhammad Fiaz; Mônica Josene Barbosa Pereira; Lucia Madalena Vivan; Hilário Cuquetto Mantovani; José Eduardo Serrão (Cell and Tissue Research, 2020)

Assessment of Real Time, Multi-Satellite Precipitation Products under Diverse Climatic and Topographic Conditions - Muhammad Masood; Abdul Sattar Shakir; Aftab Hussain Azhar; Guhlam Nabi; Habib-u-Rehman (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Risk assessment of hazardous elements in wastewater irrigated soil and cultivated vegetables in Pakistan - Alia Naz; Sardar Khan; Said Muhammad; Rafiq Ahmad; Salma Khalid; Abdullah Khan; Rashid Nazir; Sadia Alam; Zia ur Rahman (Arabian Journal of Geosciences, 2020)

Seismicity depth distribution analysis in southern Pakistan - Muhammad Jahangir Khan; Mubarik Ali (Arabian Journal of Geosciences, 2020)

Environmental pollution and COVID-19 outbreak: insights from Germany - Bilal; Muhammad Farhan Bashir; Maroua Benghoul; Umar Numan; Awais Shakoor; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan (Air Quality, Atmosphere & Health, 2020)

Does the inflow of remittances and energy consumption increase CO2 emissions in the era of globalization? A global perspective - Bo Yang; Atif Jahanger; Muhammad Atif Khan (Air Quality, Atmosphere & Health, 2020)

Predicting the non-carcinogenic health hazards associated with emissions from developing coal-fired power plants in Payra, Bangladesh - Mashiat Hossain; Tanvir Ahmed; Muhammad Ashraf Ali (Air Quality, Atmosphere & Health, 2020)

Fabrication, Physical Characterizations, and In Vitro, In Vivo Evaluation of Ginger Extract-Loaded Gelatin/Poly(Vinyl Alcohol) Hydrogel Films Against Burn Wound Healing in Animal Model - Barkat Ali Khan; Shahid Ullah; Muhammad Khalid Khan; Bushra Uzair; Farid Menaa; Valdir A. Braga (AAPS PharmSciTech, 2020)

Vicissitudes experienced by the oldest urban center in Bangladesh in relation to the migration of the Brahmaputra River - Gang Hu; Ping Wang; Sufi Mostafizur Rahman; Dehong Li; Muhammad Mahbubul Alam; Jiafu Zhang; Zhengyao Jin; Anchuan Fan; Jie Chen; Aimin Zhang; Wenqing Yang (Journal of Quaternary Science, 2020)
Bangladesh is one of the most densely populated countries in the world. There are 57 trans‐frontier rivers in the country, the widest being the Brahmaputra River. The river's channels have frequently changed course, but the relationship between such river migrations and human settlement patterns has remained unstudied. In this paper, optically stimulated luminescence and radiocarbon dating techniques were applied to sedimentary and organic materials in the oldest urban center (Wari‐Bateshwar) in Bangladesh. The results showed that the landscape around the urban center was dominated by floodplain and peatland facies between 7.9–7.6 and 4.7–1.6 ka, respectively. Humans occupied this area at ~3.2 ka, and manufactured delicate semi‐precious gemstone beads between ~2.4 and 1.8 ka. The urban center might be the same as an important city of the Gangaridai described in historical records. Due to fluvial migration at ~1.8 ka, the area surrounding the urban center was covered by fluvial sand. Humans might have been forced to abandon the urban center, leading to the bead processing technology in Bangladesh being lost forever.

Post discharge positive re-tests in COVID-19: common but clinically non-significant - Muhammad Syafiq Abdullah; Pui Lin Chong; Rosmonaliza Asli; Riamiza Natalie Momin; Babu Ivan Mani; Dhiya Metussin; Vui Heng Chong (Infectious Diseases, 2020)

Globrauneine A–F: six new triterpenoid esters from the leaves of Globimetula braunii - Kamal Ja’afar Muhammad; Shajarahtunnur Jamil; Norazah Basar; Satyajit D. Sarker; Magaji Garba Mohammed (Natural Product Research, 2020)

Trace elements-induced phytohormesis: A critical review and mechanistic interpretation - Muhammad Shahid; Nabeel Khan Niazi; Jörg Rinklebe; Jochen Bundschuh; Camille Dumat; Eric Pinelli (Critical Reviews in Environmental Science and Technology, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Proposed Definition of Experimental Secondary Ischemia for Mouse Subarachnoid Hemorrhage - Jasper Hans van Lieshout; Serge Marbacher; Sajjad Muhammad; Hieronymus D. Boogaarts; Ronald H. M. A. Bartels; Maxine Dibué; Hans-Jakob Steiger; Daniel Hänggi; Marcel A. Kamp (Translational Stroke Research, 2020)
Inconsistency in outcome parameters for delayed cerebral ischemia (DCI) makes it difficult to compare results between mouse studies, in the same way inconsistency in outcome parameters in human studies has for long obstructed adequate comparison. The absence of an established definition may in part be responsible for the failed translational results. The present article proposes a standardized definition for DCI in experimental mouse models, which can be used as outcome measure in future animal studies. We used a consensus-building approach to propose a definition for “experimental secondary ischemia” (ESI) in experimental mouse subarachnoid hemorrhage that can be used as an outcome measure in preclinical studies. We propose that the outcome measure should be as follows: occurrence of focal neurological impairment or a general neurological impairment compared with a control group and that neurological impairment should occur secondarily following subarachnoid hemorrhage (SAH) induction compared with an initial assessment following SAH induction. ESI should not be used if the condition can be explained by general anesthesia or if other means of assessments sufficiently explain function impairment. If neurological impairment cannot reliably be evaluated, due to scientific setup. Verification of a significant secondary impairment of the cerebral perfusion compared with a control group is mandatory. This requires longitudinal examination in the same animal. The primary aim is that ESI should be distinguished from intervention-related ischemia or neurological deficits, in order establish a uniform definition for experimental SAH in mice that is in alignment with outcome measures in human studies.

Phenotypic characterisation and linkage mapping of domestication syndrome traits in yellow lupin (Lupinus luteus L.) - Muhammad Munir Iqbal; William Erskine; Jens D. Berger; Matthew N. Nelson (Theoretical and Applied Genetics, 2020)
The transformation of wild plants into domesticated crops usually modifies a common set of characters referred to as ‘domestication syndrome’ traits such as the loss of pod shattering/seed dehiscence, loss of seed dormancy, reduced anti-nutritional compounds and changes in growth habit, phenology, flower and seed colour. Understanding the genetic control of domestication syndrome traits facilitates the efficient transfer of useful traits from wild progenitors into crops through crossing and selection. Domesticated forms of yellow lupin ( Lupinus luteus L.) possess many domestication syndrome traits, while their genetic control remains a mystery. This study aimed to reveal the genetic control of yellow lupin domestication traits. This involved phenotypic characterisation of those traits, defining the genomic regions controlling domestication traits on a linkage map and performing a comparative genomic analysis of yellow lupin with its better-understood relatives, narrow-leafed lupin ( L. angustifolius L.) and white lupin ( L. albus L.). We phenotyped an F 9 recombinant inbred line (RIL) population of a wide cross between Wodjil (domesticated) × P28213 (wild). Vernalisation responsiveness, alkaloid content, flower and seed colour in yellow lupin were each found to be controlled by single loci on linkage groups YL-21, YL-06, YL-03 and YL-38, respectively. Aligning the genomes of yellow with narrow-leafed lupin and white lupin revealed well-conserved synteny between these sister species (76% and 71%, respectively). This genomic comparison revealed that one of the key domestication traits, vernalisation-responsive flowering, mapped to a region of conserved synteny with the vernalisation-responsive flowering time Ku locus of narrow-leafed lupin, which has previously been shown to be controlled by an FT homologue. In contrast, the loci controlling alkaloid content were each found at non-syntenic regions among the three species. This provides a first glimpse into the molecular control of flowering time in yellow lupin and demonstrates both the power and the limitation of synteny as a tool for gene discovery in lupins.

Genetic analyses of native Fusarium head blight resistance in two spring wheat populations identifies QTL near the B1, Ppd-D1, Rht-1, Vrn-1, Fhb1, Fhb2, and Fhb5 loci - Dinushika Thambugala; Anita L. Brûlé-Babel; Barbara A. Blackwell; George Fedak; Adam J. Foster; Dan MacEachern; Jeannie Gilbert; Maria Antonia Henriquez; Richard A. Martin; Brent D. McCallum; Dean Spaner; Muhammad Iqbal; et al. (Theoretical and Applied Genetics, 2020)

The mechanism of EAP-EU combined impact on summer rainfall over North Asia - Po Hu; Jianbo Cheng; Guolin Feng; Muhammad Mubashar Ahmad Dogar; Zhiqiang Gong (Theoretical and Applied Climatology, 2020)

Modeling regional precipitation over the Indus River basin of Pakistan using statistical downscaling - Muhammad Saleem Pomee; Moetasim Ashfaq; Bashir Ahmad; Elke Hertig (Theoretical and Applied Climatology, 2020)
Complex processes govern spatiotemporal distribution of precipitation within the high-mountainous headwater regions (commonly known as the upper Indus basin (UIB)), of the Indus River basin of Pakistan. Reliable precipitation simulations particularly over the UIB present a major scientific challenge due to regional complexity and inadequate observational coverage. Here, we present a statistical downscaling approach to model observed precipitation of the entire Indus basin, with a focus on UIB within available data constraints. Taking advantage of recent high altitude (HA) observatories, we perform precipitation regionalization using K-means cluster analysis to demonstrate effectiveness of low-altitude stations to provide useful precipitation inferences over more uncertain and hydrologically important HA of the UIB. We further employ generalized linear models (GLM) with gamma and Tweedie distributions to identify major dynamic and thermodynamic drivers from a reanalysis dataset within a robust cross-validation framework that explain observed spatiotemporal precipitation patterns across the Indus basin. Final statistical models demonstrate higher predictability to resolve precipitation variability over wetter southern Himalayans and different lower Indus regions, by mainly using different dynamic predictors. The modeling framework also shows an adequate performance over more complex and uncertain trans-Himalayans and the northwestern regions of the UIB, particularly during the seasons dominated by the westerly circulations. However, the cryosphere-dominated trans-Himalayan regions, which largely govern the basin hydrology, require relatively complex models that contain dynamic and thermodynamic circulations. We also analyzed relevant atmospheric circulations during precipitation anomalies over the UIB, to evaluate physical consistency of the statistical models, as an additional measure of reliability. Overall, our results suggest that such circulation-based statistical downscaling has the potential to improve our understanding towards distinct features of the regional-scale precipitation across the upper and lower Indus basin. Such understanding should help to assess the response of this complex, data-scarce, and climate-sensitive river basin amid future climatic changes, to serve communal and scientific interests.

Effect of Water Temperature on Survival, Growth and Molting Cycle During Early Crablet Instar of Mud Crab, Scylla paramamosain (Estampador, 1950) - Muhammad Nur Syafaat; Syahnon Mohammad; Mohamad Nor Azra; Hongyu Ma; Ambok Bolong Abol-Munafi; Mhd Ikhwanuddin (Thalassas: An International Journal of Marine Sciences, 2020)

Genetic Structure of Amphioctopus ovulum (Mollusca: Cephalopoda: Octopodidae) as Revealed by Mitochondrial and Nuclear DNA - Faiz Muhammad; Canfeng Dou; Liqin Liu; Gong Li; Punhal Lashari; Zhen-ming Lü (Thalassas: An International Journal of Marine Sciences, 2020)

Partial Substitution of Fishmeal with Plant Protein Source the Soybean Meal in the Diets of Arabian Yellowfin Seabream Acanthopagrus arabicus Juveniles - Naveed Ahmad; Jamal Pirzada A. Siddiqui; Ghulam Nabi; Khan Mir Khan; Amjad Ali; Yasmeen Zamir; Mohammad Abdul Momin Siddique; Shabir Ali Amir; Farah Naz Khokhar; Muhammad Amin (Thalassas: An International Journal of Marine Sciences, 2020)

Modeling radon time series on the North Anatolian Fault Zone, Turkiye: Fourier transforms and Monte Carlo simulations - Ahmad Muhammad; Fatih Külahcı; Pishtiwan Akram (Natural Hazards, 2020)

Nexus between natural and technical disaster shocks, resource depletion and growth-specific factors: evidence from quantile regression - Waseem Akhter; Khalid Zaman; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro (Natural Hazards, 2020)

Methylphenidate and Rosmarinus officinalis improves cognition and regulates inflammation and synaptic gene expression in AlCl3-induced neurotoxicity mouse model - Anibah Khalid; Umme Aimen Abbasi; Sanila Amber; Sumera; Fatima Javed Mirza; Muhammad Asif; Aneela Javed; Saadia Zahid (Molecular Biology Reports, 2020)

Molecular and morphological discrimination of Chrysanthemum indicum using allele-specific PCR and T-shaped trichome - Suleman Abid; Lalitha Kaliraj; Muhammad Huzaifa Arif; Joon Hurh; Jong Chan Ahn; Deok Chun Yang; Seok-Kyu Jung (Molecular Biology Reports, 2020)

Telomerase reverse transcriptase downregulation by RNA interference modulates endoplasmic reticulum stress and mitochondrial energy production - Muhammad Zuhair Mohd Zain; Nor Hayati Ismail; Nadhirah Ahmad; Sarina Sulong; Saiful Anuar Karsani; Nazia Abdul Majid (Molecular Biology Reports, 2020)

Gene expression of thrombomodulin, TNF-α and NF-KB in coronary artery disease patients of Pakistan - Muhammad Rafiq; Afrose Liaquat; Nadia Saeed; Ghassan Umair Shamshad; Sana Mumtaz; Muhammad Jawad Khan (Molecular Biology Reports, 2020)

Anti-urease and cytotoxic activity of 1-Nitro-2-phenylethane and Nerolidol; two major compounds isolated from the seeds of Dennettia tripetala - Samuel E. Ugheighele; Kate E. Imafidon; Muhammad I. Choudhary; Ahmed Shakil; Majid Khan; Zaid A. Sherwani; Zaheer Ul-Haq (Medicinal Chemistry Research, 2020)

Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2020)

Is there low maternal genetic variation in West Asian populations of leopard? - Mohammad S. Farhadinia; Mohammad Reza Ashrafzadeh; Helen Senn; Sohrab Ashrafi; Hamid Farahmand; Muhammad Ghazali; Luke T. B. Hunter; David W. Macdonald (Mammal Research, 2020)
Persian leopards Panthera pardus saxicolor have been extirpated from over 84% of their historic range and are now limited to rugged landscapes of West Asia and the Caucasus. Understanding and maintaining genetic diversity and population connectivity is important for preventing inbreeding and genetic drift, both of which can threaten population viability. All previous analyses of intraspecific genetic variation of West Asian leopards based on the NADH dehydrogenase subunit 5 gene have reported low mitogenomic diversity. In the current study, we sequenced 959 bp of the mtDNA cytochrome b gene to describe the spatial genetic structure of 22 wild Persian leopards across Iran, which hosts most of the subspecies extant range. The findings based on phylogenetic trees and median-joining network indicated that leopards from Iran formed a distinct subclade, i.e., P. p. saxicolor . The AMOVA analysis showed significant differentiation (88.55%) between the subclades of Persian leopards and other Asian leopards. The lowest levels of haplotype (0.247) and nucleotide (0.00078) diversity were estimated in Persian leopards from Iran. Mitochondrial genome sequencing revealed only two closely related haplotypes. There was no evidence for recent sudden demographic expansion scenario in Persian leopards. The low diversity in cytochrome b gene could potentially be brought about by selective pressure on mitochondria to adapt to oxidative stress and higher metabolic rates in cold environments.

Characterization of displacement and internal structure of landslides from multitemporal UAV and ERT imaging - Guruh Samodra; Muhammad Fauzan Ramadhan; Junun Sartohadi; Muhammad Anggri Setiawan; Nugroho Christanto; Adhera Sukmawijaya (Landslides, 2020)

COVID-19 and therapy with essential oils having antiviral, anti-inflammatory, and immunomodulatory properties - Muhammad Asif; Mohammad Saleem; Malik Saadullah; Hafiza Sidra Yaseen; Raghdaa Al Zarzour (Inflammopharmacology, 2020)

The potential of Allium sativum and Cannabis sativa extracts for anti-tick activities against Rhipicephalus (Boophilus) microplus - Nasreen Nasreen; Sadaf Niaz; Adil Khan; Muhammad Arfan Zaman; Sultan Ayaz; Huma Naeem; Nasrullah Khan; Abdallah M. Elgorban (Experimental and Applied Acarology, 2020)

Virulence of Helicobacter pylori outer membrane proteins: an updated review - Chenjing Xu; Djaleel Muhammad Soyfoo; Yao Wu; Shunfu Xu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Genome wide association mapping and candidate gene mining for root architectural traits in rapeseed/canola (Brassica napus L.) at late growth stage - Muhammad Arifuzzaman; Mukhlesur Rahman (Euphytica, 2020)

Influence of elements of climate change on the growth and fecundity of Datura stramonium - Aakansha Chadha; Singarayer Florentine; Muhammad Javaid; Amali Welgama; Christopher Turville (Environmental Science and Pollution Research, 2020)

Adsorption, degradation, and mineralization of emerging pollutants (pharmaceuticals and agrochemicals) by nanostructures: a comprehensive review - Monika Jain; Ackmez Mudhoo; Deepika Lakshmi Ramasamy; Mahsa Najafi; Muhammad Usman; Runliang Zhu; Gopalakrishnan Kumar; Sutha Shobana; Vinod Kumar Garg; Mika Sillanpää (Environmental Science and Pollution Research, 2020)

Examining the asymmetric effects of fiscal policy instruments on environmental quality in Asian economies - Sana Ullah; Muhammad Tariq Majeed; Muhammad Zubair Chishti (Environmental Science and Pollution Research, 2020)

The effect of expected financial performance on corporate environmental responsibility disclosure: evidence from China - Yanqi Zeng; Muhammad Awais Gulzar; Zongjun Wang; Xinxin Zhao (Environmental Science and Pollution Research, 2020)

Impact of average temperature, energy demand, sectoral value added, and population growth on water resource quality and mortality rate: it is time to stop waiting around - Hafiza Samina Tehreem; Muhammad Khalid Anser; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Energy consumption, FDI, and urbanization linkage in coastal Mediterranean countries: re-assessing the pollution haven hypothesis - Solomon Nathaniel; Ekene Aguegboh; Chimere Iheonu; Gagan Sharma; Muhammad Shah (Environmental Science and Pollution Research, 2020)

Foliar application of gibberellic acid endorsed phytoextraction of copper and alleviates oxidative stress in jute (Corchorus capsularis L.) plant grown in highly copper-contaminated soil of China - Muhammad Hamzah Saleem; Shah Fahad; Muhammad Adnan; Mohsin Ali; Muhammad Shoaib Rana; Muhammad Kamran; Qurban Ali; Inas A. Hashem; Parashuram Bhantana; Mubassir Ali; Reem M. Hussain (Environmental Science and Pollution Research, 2020)

Immobilized atmospheric particulate matter on leaves of 96 urban plant species - Samira Muhammad; Karen Wuyts; Roeland Samson (Environmental Science and Pollution Research, 2020)

Does asymmetric persistence in convergence of the air quality index (AQI) exist in China? - Xue-Tao Zhang; Xi-Hua Liu; Chi-Wei Su; Muhammad Umar (Environmental Science and Pollution Research, 2020)

Environmental toxicology and biogeochemistry of ecosystems - Muhammad Aqeel Ashraf; Muhammad Faheem (Environmental Science and Pollution Research, 2020)

Bacterial-mediated synthesis of silver nanoparticles and their significant effect against pathogens - Saira Saeed; Atia Iqbal; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2020)

Application of biochar in advanced oxidation processes: supportive, adsorptive, and catalytic role - Faheem; Jiangkun Du; Sang Hoon Kim; Muhammad Azher Hassan; Sana Irshad; Jianguo Bao (Environmental Science and Pollution Research, 2020)

Estimating the UK Index Flood: an Improved Spatial Flooding Analysis - Marinah Muhammad; Zudi Lu (Environmental Modeling & Assessment, 2020)
Flooding is one of the major natural hazards in the UK. Accurate flood estimation at ungauged catchment is an important component to understand and mitigate flood hazards, but still a difficult issue. This study therefore attempts to explore and improve an index flood estimation model, known as the FEH-QMED model, popular in the UK. It was developed under the assumption that the index flood of QMED, i.e., the median of the set of annual maximum (AMAX) flood data, standing for a flooding level of 2-year return period, can be explained by catchment descriptors. In this study, two fundamentals are empirically explored, including assessing reliability of the nonlinear functional impacts of the catchment descriptors on the logarithmic transformation of QMED, specified by the FEH-QMED model, and the potential to improve the model for more accurate index flood estimation, based on the flooding data of 586 gauged stations across the UK. Through a spatial additive regression analysis, we empirically find that the nonlinear impacts of the catchment descriptors in an updated FEH-QMED model appear reliable. However, spatial correlation tests including Moran’s I and Lagrange multiplier tests show that strong spatial dependence exists in the residuals of, but was not fully taken into account by, the QMED type models. We have therefore empirically established new spatial index flood estimation models by proposing spatial autoregressive models to model the impacts of the neighboring sites. Cross-validation assessments demonstrate that the suggested spatial error-based index flood model outperforms the updated FEH-QMED model with a significant improvement, which is robust in the sense of different error measures, say by a reduction of 13.8% of the mean squared error of prediction, for the UK index flood estimation.

Advances in photo-catalysis approach for the removal of toxic personal care product in aqueous environment - Muhammad Bilal Tahir; Anam Ahmad; Tahir Iqbal; Mohsin Ijaz; Shabbir Muhammad; Saifeldin M. Siddeeg (Environment, Development and Sustainability, 2020)

Analysis of coal-related energy consumption in Pakistan: an alternative energy resource to fuel economic development - Muhammad Yousaf Raza; Muhammad Tauqir Sultan Shah (Environment, Development and Sustainability, 2020)

RETRACTED ARTICLE: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2020)

Effects of Different Sample Pulverisation Methods on the Extraction of Metabolites from the Fermented Cottonseed Meal Based on UPLC-Q-TOF-MS - Yongqiang Wang; Hongbing Xie; Dongyang Liu; Yimin Wang; Changzhong Liu; Muhammad Akram Khan; Jinqing Jiang; Wenjv Zhang (Current Microbiology, 2020)

Heavy Metals Assessment in Water, Sediments, Algae and Two Fish Species from River Swat, Pakistan - Israr Alam; Muhammad Nasir Khan Khattak; Shahi Mulk; Farman Ullah Dawar; Lubna Shahi; Ihsanullah Ihsanullah (Bulletin of Environmental Contamination and Toxicology, 2020)

RETRACTED ARTICLE: Relationship between water content, shear deformation, and elastic wave velocity through unsaturated soil slope - Yulong Chen; Muhammad Irfan; Taro Uchimura; Qingxiang Meng; Jie Dou (Bulletin of Engineering Geology and the Environment, 2020)

An overview of polymeric nano-biocomposites as targeted and controlled-release devices - Muhammad Rahim; Mas Rosemal Hakim Mas Haris; Najm Us Saqib (Biophysical Reviews, 2020)

Statistical Assessment of Toxic and Essential Metals in the Serum of Female Patients with Lung Carcinoma from Pakistan - Muhammad Abdul Qayyum; Zahid Farooq; Muhammad Yaseen; Mian HR Mahmood; Ahmad Irfan; Muhammad Nadeem Zafar; Muddassir Khawaja; Kashif Naeem; Dursun Kisa (Biological Trace Element Research, 2020)

Morphological and genetic characterisation of Centrorhynchus clitorideus (Meyer, 1931) (Acanthocephala: Centrorhynchidae) from the little owl Athene noctua (Scopoli) (Strigiformes: Strigidae) in Pakistan - Qing Zhao; Nehaz Muhammad; Hui-Xia Chen; Jun Ma; Suleman; Liang Li (Systematic Parasitology, 2020)

Green remediation of saline–sodic Pb-factored soil by growing salt-tolerant rice cultivar along with soil applied inorganic amendments - Muhammad Mazhar Iqbal; Tayyaba Naz; Mazhar Iqbal Zafar; Muhammad Imtiaz; Omer Farooq; Atique ur Rehman; Shafaqat Ali; Muhammad Rizwan; Sabir Hussain; Wasim Javed; Ghulam Murtaza; Muhammad Afzal; et al. (Paddy and Water Environment, 2020)

Genesis of Manganese Deposits in the Ali Khanzai Block of the Zhob Ophiolite, Pakistan: Inferences from Geochemistry and Mineralogy - Muhammad Ayoub Khan; Muhammad Ishaq Kakar; Thomas Ulrich; Liaqat Ali; Andrew C. Kerr; Khalid Mahmood; Rehanul Haq Siddiqui (Journal of Earth Science, 2020)

Genome-wide analysis of glutathione S-transferase gene family in G. max - Muhammad Zulfiqar Ahmad; Jamal Abdul Nasir; Shakeel Ahmed; Bushra Ahmad; Aiman Sana; Said Salman; Zamarud Shah; CunYi Yang (Biologia, 2020)

Soil fungal taxonomic diversity along an elevation gradient on the semi-arid Xinglong Mountain, Northwest China - Salman Khan; Ning Chen; Cankun Zhang; Luning Wang; Chun Han; Kanglong Lu; Yage Li; Muhammad Rafiq; Awais Iqbal; Changming Zhao (Archives of Microbiology, 2020)

Heterologous expression of azoreductase-encoding gene azrS of Bacillus sp. MR-1/2 for enhanced azo dye decolorization and wastewater treatment - Ali Abbas; Aqsa Mushtaq; Ayesha Iftikhar Cheema; Faisal Mahmood; Muhammad Asaf Khan; Tahir Naqqash; Mohsin Khurshid; Irfan Manzoor; Sher Muhammad; Muhammad Shahid (Archives of Microbiology, 2020)

Influence of selected mineral material on the water solubility and leachability of heavy metals from contaminated soil - Muhammad Irshad; Sardar Owais Mukhtar (Arabian Journal of Geosciences, 2020)

Soil selenium transformation across different parent materials in Pothwar uplands of Pakistan - Muhammad Imran; Mohammad Saleem Akhtar; Ayaz Mehmood; Shah Rukh; Ahmad Khan; Chen Zhikun; Ghulam Mujtaba (Arabian Journal of Geosciences, 2020)

Flash flood risk modeling of swat river sub-watershed: a comparative analysis of morphometric ranking approach and El-Shamy approach - Muhammad Jamal Nasir; Javed Iqbal; Waqas Ahmad (Arabian Journal of Geosciences, 2020)

Predictive modeling and comparative evaluation of geostatistical models for geochemical exploration through stream sediments - Muhammad Ahsan Mahboob; Turgay Celik; Bekir Genc (Arabian Journal of Geosciences, 2020)

Correction to: Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

Assessing the sustainability of public health in the era of globalization - Mohsin Raza; Muhammad Inam Afzal; Muhammad Ather Elahi (Arabian Journal of Geosciences, 2020)

Determinants of farmers’ adaptation to climate change in rain-fed agriculture of Pakistan - Sarah Amir; Zafeer Saqib; Muhammad Irfan Khan; Akhter Ali; Muhammad Azeem Khan; Syed Atif Bokhari; Zaman-ul-Haq (Arabian Journal of Geosciences, 2020)

Application of regression in seasonal flow forecasting for Upper Indus Basin of Pakistan - Muhammad Umar (Arabian Journal of Geosciences, 2020)

Manufacture of Portland cement from Late Miocene claystone, Injana formation, Central Iraq - Salih Muhammad Awadh; Ali Mutlag Awad (Arabian Journal of Geosciences, 2020)

Current findings on carp edema virus, control challenges, and future outlook - Tayyab Rehman; Lizi Yin; Muhammad Bilal Latif; Yaojia Zhou; Kaiyu Wang; Yi Geng; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Hongrui Guo; Weiming Lai; et al. (Aquaculture International, 2020)

Effects of dietary Lactobacillus plantarum C20015 on growth, immunity, and disease resistance in koi carp - Hai-peng Zhang; Wen-long Dong; Long Chen; Yi-ming Wang; Inam Muhammad; An-qi Ju; Xiao-feng Shan; Hong-xia Ma; Ling-cong Kong (Aquaculture International, 2020)

Foliage application and seed priming with nitric oxide causes mitigation of salinity-induced metabolic adversaries in broccoli (Brassica oleracea L.) plants - Nudrat Aisha Akram; Naima Hafeez; Muhammad Farid-ul-Haq; Abrar Ahmad; Muhammad Sadiq; Muhammad Ashraf (Acta Physiologiae Plantarum, 2020)

An Inland Shore Control Centre for Monitoring or Controlling Unmanned Inland Cargo Vessels - Gerben Peeters; Gökay Yayla; Tim Catoor; Senne Van Baelen; Muhammad Raheel Afzal; Christos Christofakis; Stijn Storms; René Boonen; Peter Slaets (Journal of Marine Science and Engineering, 2020)
Augmenting the automation level of the inland waterway cargo transport sector, coupled with mechatronic innovation in this sector, could increase its competitiveness. This increase might potentially induce a sustainable paradigm shift in the road-dominated inland cargo transport sector. A key enabler of this envisaged shift may be an inland shore control centre (I-SCC) capable of remotely monitoring and controlling inland vessels. Accordingly, this study investigated the concept and design requirements to achieve an inland I-SCC that provides interaction services when supervising an unmanned surface vessel (USV). This I-SCC can help its operator to develop situational awareness and sensemaking. The conducted experiments offered insights into the performance of both the I-SCC system and its operator, and unlock research on the impact on ship sense and harmony when remotely controlling a USV. The Hull-To-Hull project extends the current I-SCC by providing enhanced motion control. This enhancement enables further performance insights and might improve the future monitoring of USVs. The successful I-SCC construction, the preliminary experiments, and the design-extension demonstrate that the I-SCC can serve as an experimental platform for both mechatronic innovation and human-automation integration research in the inland waterway sector, whilst additionally providing fruitful knowledge for adjacent research domains.

Performance Analysis of Combined Cycle with Air Breathing Derivative Gas Turbine, Heat Recovery Steam Generator, and Steam Turbine as LNG Tanker Main Engine Propulsion System - Wahyu Nirbito; Muhammad Arif Budiyanto; Robby Muliadi (Journal of Marine Science and Engineering, 2020)
This study explains the performance analysis of a propulsion system engine of an LNG tanker using a combined cycle whose components are gas turbine, steam turbine, and heat recovery steam generator. The researches are to determine the total resistance of an LNG tanker with a capacity of 125,000 m3 by using the Maxsurf Resistance 20 software, as well as to design the propulsion system to meet the required power from the resistance by using the Cycle-Tempo 5.0 software. The simulation results indicate a maximum power of the system of about 28,122.23 kW with a fuel consumption of about 1.173 kg/s and a system efficiency of about 48.49% in fully loaded conditions. The ship speed can reach up to 20.67 knots.

Comparing the potential of stereo aerial photographs, stereo very high-resolution satellite images, and TanDEM-X for estimating forest height - Sami Ullah; Matthias Dees; Pawan Datta; Petra Adler; Tahir Saeed; Muhammad Sadiq Khan; Barbara Koch (International Journal of Remote Sensing, 2020)

Zeolitic imidazolate frameworks and their derived materials for sequestration of radionuclides in the environment: A review - Elvis Djam Miensah; Musaa Muhammad Khan; Jiu Yu Chen; Xiao Mei Zhang; Peng Wang; Zong Xiang Zhang; Yan Jiao; Ying Liu; Yi Yang (Critical Reviews in Environmental Science and Technology, 2020)

Future Vision for Autonomous Ocean Observations - Christopher Whitt; Jay Pearlman; Brian Polagye; Frank Caimi; Frank Muller-Karger; Andrea Copping; Heather Spence; Shyam Madhusudhana; William Kirkwood; Ludovic Grosjean; Bilal Muhammad Fiaz; Satinder Singh; et al. (Frontiers in Marine Science, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Effect of hemoglobin polymorphism on performance traits in indigenous chicken genotypes in Nigeria - M. Orunmuyi; H. Muhammad; A. A. Musa; A. K. Olutunmogun; B. I. Nwagu (Tropical Animal Health and Production, 2020)

Principles and approaches of association mapping in plant breeding - Aminu Kurawa Ibrahim; Liwu Zhang; Sylvain Niyitanga; Muhammad Zohaib Afzal; Yi Xu; Lilan Zhang; Liemei Zhang; Jianmin Qi (Tropical Plant Biology, 2020)

QTL mapping for field resistance to wheat blast in the Caninde#1/Alondra population - Xinyao He; Muhammad Rezaul Kabir; Krishna K. Roy; Md. Babul Anwar; Kaijie Xu; Felix Marza; Firuz Odilbekov; Aakash Chawade; Etienne Duveiller; Eric Huttner; Pawan K. Singh (Theoretical and Applied Genetics, 2020)
Key message Wheat blast resistance in Caninde#1 is controlled by a major QTL on 2NS/2AS translocation and multiple minor QTL in an additive mode. Abstract Wheat blast (WB) is a devastating disease in South America, and it recently also emerged in Bangladesh. Host resistance to WB has relied heavily on the 2NS/2AS translocation, but the responsible QTL has not been mapped and its phenotypic effects in different environments have not been reported. In the current study, a recombinant inbred line population with 298 progenies was generated, with the female and male parents being Caninde#1 (with 2NS) and Alondra (without 2NS), respectively. Phenotyping was carried out in two locations in Bolivia, namely Quirusillas and Okinawa, and one location in Bangladesh, Jashore, with two sowing dates in each of the two cropping seasons in each location, during the years 2017–2019. Genotyping was performed with the DArTseq® technology along with five previously reported STS markers in the 2NS region. QTL mapping identified a major and consistent QTL on 2NS/2AS region, explaining between 22.4 and 50.1% of the phenotypic variation in different environments. Additional QTL were detected on chromosomes 1AS, 2BL, 3AL, 4BS, 4DL and 7BS, all additive to the 2NS QTL and showing phenotypic effects less than 10%. Two codominant STS markers, WGGB156 and WGGB159 , were linked proximally to the 2NS/2AS QTL with a genetic distance of 0.9 cM, being potentially useful in marker-assisted selection.

A Surface-to-Borehole TEM System Based on Grounded-wire Sources: Synthetic Modeling and Data Inversion - Weiying Chen; Sixu Han; Muhammad Younis Khan; Wen Chen; Yiming He; Linbo Zhang; Dongyang Hou; Guoqiang Xue (Pure and Applied Geophysics, 2020)

Comparative Assessment of Reference Evapotranspiration Estimation Using Conventional Method and Machine Learning Algorithms in Four Climatic Regions - Ali Raza; Muhammad Shoaib; Muhammad Abrar Faiz; Faisal Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah; Muhammad Zubair (Pure and Applied Geophysics, 2020)

Transcription Factor TaDof1 Improves Nitrogen and Carbon Assimilation Under Low-Nitrogen Conditions in Wheat - Ammarah Hasnain; Muhammad Irfan; Aftab Bashir; Asma Maqbool; Kauser A. Malik (Plant Molecular Biology Reporter, 2020)

Effect of osmopriming and thermopriming on amelioration of mercuric chloride stress tolerance in mungbean (Vigna radiata L.) - Ijaz Ahmad; Sami Ullah; Muhammad Nafees (Plant Physiology Reports, 2020)

Reproductive tissues-specific meta-QTLs and candidate genes for development of heat-tolerant rice cultivars - Qasim Raza; Awais Riaz; Khurram Bashir; Muhammad Sabar (Plant Molecular Biology, 2020)

Genetic mapping and identification of new major loci for tolerance to low phosphorus stress in rice - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Majeeduddin Solangi; Saba Khanzada; Muhammad Faheem; Jianmin Bian; Xiaohua Pan; Rui Cai Han; Xunfeng He; et al. (Physiology and Molecular Biology of Plants, 2020)
Phosphorus (P) is one of the essential macronutrients for rice. In this study, we used 120 rice backcross recombinant inbred lines (BRILs) derived from a cross indica cv. Changhui 891 and japonica cv. 02428. To elucidate the genetic control of P deficiency tolerance in rice, we have used high quality SNPs bin markers to identify some important loci underlying phosphorus deficiency. The bin map was generated which includes 3057 bins covering distance of 1266.5 cM with an average of 0.41 cM between markers. Based on this map, 50 loci, including four novel loci, qSL - 3 , qRL - 11 , qSDW - 1 , qRDW - 1 with phenotypic variance 23.26%, 12.06%, 9.89% associated with P deficiency-related seedling traits were identified. No significant QTLs was found for root length under P+, shoot fresh weight P− and root length, shoot fresh weight for P+, P− and their ratio respectively. Root fresh weight, and root dry weight were strongly correlated to each other, and QTLs for these variables were located on the same chromosome 1 at the same region. Notably, 3 pleiotropic regions is the pioneer of our study, and these regions would facilitate map-based cloning to expedite the MAS selection for developing low phosphorous tolerant varieties. This study not only improves our knowledge about molecular processes associated with P deficiency, but also provides useful information to understand the genetic architecture of low phosphorous tolerance.

Modulation of growth and key physiobiochemical attributes after foliar application of zinc sulphate (ZnSO4) on wheat (Triticum aestivum L.) under cadmium (Cd) stress - Shagufta Perveen; Muhammad Saeed; Abida Parveen; Muhammad Tariq Javed; Sara Zafar; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2020)

Attenuating the adverse aspects of water stress on wheat genotypes by foliar spray of melatonin and indole-3-acetic acid - Sara Zafar; Muhammad Akhtar; Shagufta Perveen; Zuhair Hasnain; Aansa Khalil (Physiology and Molecular Biology of Plants, 2020)

Evaluation of indigenous Omani alfalfa landraces for morphology and forage yield under different levels of salt stress - Safaa Mohammed Al-Farsi; Saleem K. Nadaf; Abdullah M. Al-Sadi; Aman Ullah; Muhammad Farooq (Physiology and Molecular Biology of Plants, 2020)

Pharmacokinetic Advantage of ASD Device Promote Drug Absorption through the Epicardium - Reyaj Mikrani; Cunyu Li; Muhammad Naveed; Cuican Li; Mirza Muhammad Faran Ashraf Baig; Qin Zhang; Yue Wang; Juanjuan Peng; Lingzhi Zhao; Xiaohui Zhou (Pharmaceutical Research, 2020)

Removing top leaves increases yield and nutrient uptake in maize plants - Muhammad Ali Raza; Wopke van der Werf; Mukhtar Ahmed; Wenyu Yang (Nutrient Cycling in Agroecosystems, 2020)

An indicator based approach for assessing household’s perceptions of landslide risk in Murree hills of Pakistan - Said Qasim; Muhammad Qasim (Natural Hazards, 2020)

Scenario-based seismic hazard analysis using spectral element method in northeastern Pakistan - Saad Khan; Mark van der Meijde; Harald van der Werff; Muhammad Shafique (Natural Hazards, 2020)
Seismic hazard analysis is carried out in this study by estimating ground motion for hypothetical earthquakes in the area of Muzaffarabad, Pakistan, with the MT solution of the 2005 Kashmir earthquake. The earth’s topography influences seismic waves by scattering and reflecting it, thereby causing spatial variation in seismic response. Using the moment tensor solution of the 2005 Kashmir earthquake, we perform 25 spectral element method (SEM)-based 3D simulations along major faults in the study area. The SEM model incorporates the topography and homogeneous half-space characteristics. Our results show that, beside topography, the relative location of the source with respect to slopes also has an influence on the observed variation in ground shaking amplitudes. By integrating the mean and standard deviation of estimated ground shaking from 25 simulations, we present a seismic hazard map for the study area. The map summarizes the topographic and potential source location effect on seismic-induced ground shaking in the study area. It provides a classification from hazardous to safe in relative terms and can be used as a guide in earthquake preparedness.

Streamflow forecasting by modeling the rainfall–streamflow relationship using artificial neural networks - Shahzad Ali; Muhammad Shahbaz (Modeling Earth Systems and Environment, 2020)

Investigation and dynamic analyses of rockslide-induced debris avalanche in Shuicheng, Guizhou, China - Yanbo Zhang; Aiguo Xing; Kaiping Jin; Yu Zhuang; Muhammad Bilal; Shimin Xu; Yaoqiang Zhu (Landslides, 2020)

Nitrous oxide emissions from tea garden soil following the addition of urea and rapeseed cake - Jialuo Yu; Shan Lin; Muhammad Shaaban; Wenliang Ju; Linchuan Fang (Journal of Soils and Sediments, 2020)

Mo-Inefficient Wheat Response Toward Molybdenum Supply in Terms of Soil Phosphorus Availability - Muhammad Shoaib Rana; Xuecheng Sun; Muhammad Imran; Zaid Khan; Mohamed G. Moussa; Muhammad Abbas; Parashuram Bhantana; Muhamad Syaifudin; Intisar Ud Din; Muhammad Younas; Md Ashrafuzzaman Shah; Javaria Afzal; et al. (Journal of Soil Science and Plant Nutrition, 2020)

Sodium Exclusion Affects Seed Yield and Physiological Traits of Wheat Genotypes Grown Under Salt Stress - Muhammad Sohail Saddiq; Irfan Afzal; Shahzad M.A. Basra; Shahid Iqbal; Muhammad Ashraf (Journal of Soil Science and Plant Nutrition, 2020)

Characterizing Lentil Germplasm for Zinc Biofortification and High Grain Output - Naser Rasheed; Muhammad Aamer Maqsood; Tariq Aziz; Abdul Jabbar (Journal of Soil Science and Plant Nutrition, 2020)

Iron Nutrition Improves Productivity, Profitability, and Biofortification of Bread Wheat under Conventional and Conservation Tillage Systems - Usman Zulfiqar; Muhammad Maqsood; Saddam Hussain; Muhammad Anwar-ul-Haq (Journal of Soil Science and Plant Nutrition, 2020)

Zinc Nutrition for Improving the Productivity and Grain Biofortification of Mungbean - Muhammad Umar Haider; Mubshar Hussain; Muhammad Farooq; Ahmad Nawaz (Journal of Soil Science and Plant Nutrition, 2020)

Changes in Soil Organic Carbon Fractions Across a Loess Toposequence - Arsalan Azam; Mohammad Saleem Akhtar; Shah Rukh; Ayaz Mehmood; Muhammad Imran; Ahmad Khan; Abdul Qayyum; Waseem Ahmad; Ali Raza Gurmani (Journal of Soil Science and Plant Nutrition, 2020)

Silicon and Its Application Methods Improve Physiological Traits and Antioxidants in Triticum aestivum (L.) Under Cadmium Stress - Shafeeq-ur-Rahman; Qi Xuebin; Xiao Yatao; Muhammad Irfan Ahmad; Muhammad Shehzad; Muhammad Zain (Journal of Soil Science and Plant Nutrition, 2020)

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

Comparative Cytological and Gene Expression Analysis Reveals Potential Metabolic Pathways and Target Genes Responsive to Salt Stress in Kenaf (Hibiscus cannabinus L.) - Muhammad Haneef Kashif; Danfeng Tang; Zengqiang Li; Fan Wei; Zhichen Liang; Peng Chen (Journal of Plant Growth Regulation, 2020)

Correction to: Fluctuating temperatures influence the susceptibility of pest insects to biological control agents - Muhammad Usman Ghazanfar; Steffen Hagenbucher; Jörg Romeis; Giselher Grabenweger; Michael Meissle (Journal of Pest Science, 2020)

Investigating the importance of B cells and antibodies during Trichuris muris infection using the IgMi mouse - Rinal Sahputra; Emma A Murphy; Ruth Forman; Iris Mair; Muhammad Z. H. Fadlullah; Ari Waisman; Werner Muller; Kathryn J. Else (Journal of Molecular Medicine, 2020)
The IgMi mouse has normal B cell development; its B cells express an IgM B cell receptor but cannot class switch or secrete antibody. Thus, the IgMi mouse offers a model system by which to dissect out antibody-dependent and antibody-independent B cell function. Here, we provide the first detailed characterisation of the IgMi mouse post- Trichuris muris ( T. muris ) infection, describing expulsion phenotype, cytokine production, gut pathology and changes in T regulatory cells, T follicular helper cells and germinal centre B cells, in addition to RNA sequencing (RNA seq) analyses of wild-type littermates (WT) and mutant B cells prior to and post infection. IgMi mice were susceptible to a high-dose infection, with reduced Th2 cytokines and elevated B cell-derived IL-10 in mesenteric lymph nodes (MLN) compared to controls. A low-dose infection regime revealed IgMi mice to have significantly more apoptotic cells in the gut compared to WT mice, but no change in intestinal inflammation. IL-10 levels were again elevated. Collectively, this study showcases the potential of the IgMi mouse as a tool for understanding B cell biology and suggests that the B cell plays both antibody-dependent and antibody-independent roles post high- and low-dose T. muris infection. Key messages During a high-dose T. muris infection, B cells are important in maintaining the Th1/Th2 balance in the MLN through an antibody-independent mechanism. High levels of IL-10 in the MLN early post-infection, and the presence of IL-10-producing B cells, correlates with susceptibility to T. muris infection. B cells maintain gut homeostasis during chronic T. muris infection via an antibody-dependent mechanism.

Attraction and retention-period of different stuffs and stuffing techniques with their active food baits for the management of peach fruit fly, Bactrocera zonata (Diptera: Tephritidae) - Muhammad Junaid Nisar; Muhammad Dildar Gogi; Muhammad Jalal Arif; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2020)

Exogenous Neurokinin B Administration May Have a Strong Effect on Negative Feedback Loop of Hypothalamic Pituitary Thyroid Axis - Maria Wishal Asmat; Muhammad Haris Ramzan; Faiqah Ramzan (International Journal of Peptide Research and Therapeutics, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

Growth, Biomass Production, and Yield Potential of Quinoa (Chenopodium quinoa Willd.) as Affected by Planting Techniques Under Irrigated Conditions - Saif Ali; Muhammad Umer Chattha; Muhammad Umair Hassan; Imran Khan; Muhammad Bilal Chattha; Babar Iqbal; Muzammal Rehman; Muhammad Nawaz; Muhammad Zubair Amin (International Journal of Plant Production, 2020)

Combining SVM and ECOC for Identification of Protein Complexes from Protein Protein Interaction Networks by Integrating Amino Acids’ Physical Properties and Complex Topology - Amen Faridoon; Aisha Sikandar; Muhammad Imran; Saman Ghouri; Misba Sikandar; Waseem Sikandar (Interdisciplinary Sciences: Computational Life Sciences, 2020)

High-resolution chemical profiling and antiparasitic potential of the tropical shrub Dillenia suffruticosa - Muhammad Dawood Shah; Kazuki Tani; Balu Alagar Venmathi Maran; Yoong Soon Yong; Ching Fui Fui; Sitti Raehanah Muhamad Shaleh; Charles S. Vairappan (Fisheries Science, 2020)

Selection criteria for yield potential in a large collection of Vigna radiata (L.) accessions - Ayesha Tahir; Muhammad Kashif Ilyas; Muhammad Muddassir Sardar; Ali Kiani Pouya; Fatemeh Rasouli; Ameer Bibi; Zahra Jabeen; Muhammad Sajjad; Sadar Uddin Siddiqui; Abdul Ghafoor (Euphytica, 2020)

Performance evaluation of conventional and hybrid woven fabrics for the development of sustainable personal protective clothing - Arshad Hussain Memon; Mazhar Hussain Peerzada; Khan Muhammad Brohi; Sheeraz Ahmed Memon; Sajjad Ali Mangi (Environmental Science and Pollution Research, 2020)

Social and administrative issues related to the COVID-19 pandemic in Pakistan: better late than never - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Xuan Hinh Vo; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Correction to: Economic efficiency of rainfed wheat farmers under changing climate: evidence from Pakistan - Nasir Mahmood; Muhammad Arshad; Harald Kächele; Ayat Ullah; Klaus Müller (Environmental Science and Pollution Research, 2020)

Environmental impacts and risk factors of renewable energy paradigm—a review - Muhammad Shahzad Nazir; Ziad M. Ali; Muhammad Bilal; Hafiz M. Sohail; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2020)

Response surface methodology and artificial neural network for remediation of acid orange 7 using TiO2-P25: optimization and modeling approach - Muhammad Zulfiqar; Sujan Chowdhury; Abdul Aziz Omar; Ahmer Ali Siyal; Suriati Sufian (Environmental Science and Pollution Research, 2020)

Economic efficiency of rainfed wheat farmers under changing climate: evidence from Pakistan - Nasir Mahmood; Muhammad Arshad; Harald Kächele; Ayat Ullah; Klaus Müller (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Effect of gibberellic acid on growth, biomass, and antioxidant defense system of wheat (Triticum aestivum L.) under cerium oxide nanoparticle stress - Azka Iftikhar; Muhammad Rizwan; Muhammad Adrees; Shafaqat Ali; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum; Afzal Hussain (Environmental Science and Pollution Research, 2020)

Effective sequestration of Cr (VI) from wastewater using nanocomposite of ZnO with cotton stalks biochar: modeling, kinetics, and reusability - Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Hussnain Siddique; Zafar Iqbal; Muhammad Amjad; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Assessment of copper, chromium, and lead toxicity in fish (Ctenopharyngodon idella Valenciennes, 1844) through hematological biomarkers - Nazish Shah; Muhammad Khisroon; Said Sajjad Ali Shah (Environmental Science and Pollution Research, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Synthesis of nickel nanoparticles using Citrullus colocynthis stem extract for remediation of Reactive Yellow 160 dye - Shumaila Kiran; Muhammad Asim Rafique; Sarosh Iqbal; Sofia Nosheen; Saba Naz; Abdur Rasheed (Environmental Science and Pollution Research, 2020)

Radon concentration in drinking water and soil after the September 24, 2019, Mw 5.8 earthquake, Mirpur, Azad Jammu, and Kashmir: an evaluation for potential risk - Said Muhammad; Rizwan Ullah; Syed Ali Turab; Muhammad Younis Khan; Nimat Ullah Khattak; Muhammad Asif Khan (Environmental Science and Pollution Research, 2020)

The long-run and short-run influence of environmental pollution, energy consumption, and economic activities on health quality in emerging countries - Muhammad Khalid Anser; Imran Hanif; Xuan Vinh Vo; Majed Alharthi (Environmental Science and Pollution Research, 2020)

Asymmetric effects of inflation instability and GDP growth volatility on environmental quality in Pakistan - Sana Ullah; Nicholas Apergis; Ahmed Usman; Muhammad Zubair Chishti (Environmental Science and Pollution Research, 2020)

Non-linear threshold effect of financial development on renewable energy consumption: evidence from panel smooth transition regression approach - Syed Ali Raza; Nida Shah; Muhammad Asif Qureshi; Shahzad Qaiser; Ramsha Ali; Farhan Ahmed (Environmental Science and Pollution Research, 2020)

Assessing the integration of solar power projects: SWOT-based AHP–F-TOPSIS case study of Turkey - Muhammad Khalid Anser; Muhammad Mohsin; Qaiser Abbas; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Application of geoelectrical resistivity method for the assessment of shallow aquifer quality in landfill areas - Nur Islami; Mitri Irianti; Fakhruddin Fakhruddin; Azhar Azhar; Muhammad Nor (Environmental Monitoring and Assessment, 2020)

Enhanced bioremediation of diesel range hydrocarbons in soil using biochar made from organic wastes - Sadia Aziz; Muhammad Ishtiaq Ali; Uzma Farooq; Asif Jamal; Fang-Jing Liu; Huan He; Hongguang Guo; Michael Urynowicz; Zaixing Huang (Environmental Monitoring and Assessment, 2020)

Spatial variation and health risk assessment of fluoride in drinking water in the Chongqing urban areas, China - Dongsheng Zheng; Yonglin Liu; Lili Luo; Muhammad Zeeshaan Shahid; Dongming Hou (Environmental Geochemistry and Health, 2020)

Theranostic applications of smart nanomedicines for tumor-targeted chemotherapy: a review - Ajkia Zaman Juthi; Md Aquib; Muhammad Asim Farooq; Sana Ghayas; Farah Khalid; George Frimpong Boafo; Dickson Pius Wande; Daulat Haleem Khan; Tasnim Zaman Bithi; Rohit Bavi; Bo Wang (Environmental Chemistry Letters, 2020)

Correction to: Sublethal effects of a juvenile hormone analog, Pyriproxyfen demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Sublethal effects of a juvenile hormone analog, Pyriproxyfen on demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Luteimonas granuli sp. nov., Isolated from Granules of the Wastewater Treatment Plant - Muhammad Zubair Siddiqi; Jun Mo Yeon; Hanna Choi; Jae Hag Lee; Sang Yong Kim; Ji-Hyang Wee; Wan Taek Im (Current Microbiology, 2020)

Evaluation of Factors Affecting Saccharification of Sugarcane Bagasse Using Cellulase Preparation from a Thermophilic Strain of Brevibacillus sp. - Maria Tariq Khan; Uroosa Ejaz; Muhammad Sohail (Current Microbiology, 2020)

Microfacies analysis, diagenetic overprints, geochemistry, and reservoir quality of the Jurassic Samanasuk Formation at the Kahi Section, Nizampur Basin, NW Himalayas, Pakistan - Emad ullah Khan; Maryam Saleem; Abbas Ali Naseem; Waqar Ahmad; Muhammad Yaseen; Tehseen Ullah Khan (Carbonates and Evaporites, 2020)

Microfacies, diagenesis and hydrocarbon potential of Eocene carbonate strata in Pakistan - Umer Khitab; Muhammad Umar; Muhammad Jamil (Carbonates and Evaporites, 2020)

HPLC-UV characterization, anticholinesterase, and free radical-scavenging activities of Rosa moschata Herrm. leaves and fruits methanolic extracts - Nausheen Nazir; Atif Ali Khan Khalil; Mohammad Nisar; Muhammad Zahoor; Sajjad Ahmad (Brazilian Journal of Botany, 2020)

Date palm rachis as a raw material for wood composite industry: anatomical characteristics - Pervaiz Rasheed Khan; Said Saad Hegazy; Muhammad Iqbal (Brazilian Journal of Botany, 2020)

Co-culturing corncob-immobilized yeasts on orange peels for the production of pectinase - Faizan Qadir; Uroosa Ejaz; Muhammad Sohail (Biotechnology Letters, 2020)

Environmental Integrants Affecting the Spreadability of SARS-CoV-12 - Muhammad Torequl Islam (Food and Environmental Virology, 2020)

Enhancement of salt tolerance in maize (Zea mays L.) using locally isolated Bacillus sp. SR-2-1/1 - Khadija Rafiq; Muhammad Sohail Akram; Muhammad Shahid; Uzma Qaisar; Naeem Rashid (Biologia, 2020)

Light intensity effects on the growth and biomass production of submerged macrophytes in different water strata - Shuquan Jin; Muhammad Ibrahim; Said Muhammad; Sardar Khan; Gang Li (Arabian Journal of Geosciences, 2020)

Bioaccumulation of potentially toxic elements in spinach grown on contaminated soils amended with organic fertilizers and their subsequent human health risk - Zawar Hussain; Mehboob Alam; Muhammad Amjad Khan; Muhammad Asif; Muhammad Azhar Shah; Shehnaz Khan; Sardar Khan; Javed Nawab (Arabian Journal of Geosciences, 2020)

Flood inundation modeling and hazard assessment in Lower Ping River Basin using MIKE FLOOD - Husnain Tansar; Muhammad Babur; Surchai Lai Karnchanapaiboon (Arabian Journal of Geosciences, 2020)

Hydrocarbon degradation in oily sludge by bacterial consortium assisted with alfalfa (Medicago sativa L.) and maize (Zea mays L.) - Asim Shahzad; Samina Siddiqui; Asghari Bano; Shehla Sattar; Muhammad Zaffar Hashmi; Mingzhou Qin; Abdul Shakoor (Arabian Journal of Geosciences, 2020)

Petrographic and rare earth elemental characteristics of Cambrian Girvanella oncoids exposed in the North China Platform: Constraints on forming mechanism, REE sources, and paleoenvironments - Muhammad Riaz; Tehseen Zafar; Khalid Latif; Shahid Ghazi; Enzhao Xiao (Arabian Journal of Geosciences, 2020)

Interactive effects of chitosan and cadmium on growth, secondary metabolism, oxidative defense, and element uptake in pea (Pisum sativum L.) - Rizwan Rasheed; Muhammad Arslan Ashraf; Asma Arshad; Muhammad Iqbal; Iqbal Hussain (Arabian Journal of Geosciences, 2020)

Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

The impacts of COVID-19 measures on global environment and fertility rate: double coincidence - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Xuan Hinh Voo; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Air Quality, Atmosphere & Health, 2020)

Predictive analysis of CO2 emissions and the role of environmental technology, energy use and economic output: evidence from emerging economies - Sidrah Ahmed; Khalid Ahmed; Muhammad Ismail (Air Quality, Atmosphere & Health, 2020)

The nexus of environmental degradation and technology innovation and adoption: an experience from dragon - Wang Xinmin; Peng Hui; Muhammad Hafeez; Babar Aziz; Muhammad Waqas Akbar; Muhammad Ayzed Mirza (Air Quality, Atmosphere & Health, 2020)

Biodeterioration of archaeological monuments of Taxila, Pakistan - Muhammad Farooq; Syeda Durre Maknoon (Aerobiologia, 2020)

Epidemiology, Associated Factors and Treatment Methods of Cutaneous Leishmaniasis Based on Previous Data from 2013 to 2018 in Ilam, Western Iran - Nasrin Rezaee; Vahid Raissi; Ahmad Rajaeipour; Mehdi Nazari; Muhammad Getso; Ali Taghipour; Omid Raiesi; Asmaa Ibrahim (Acta Parasitologica, 2020)

The engineering assessments and potential aggregate analysis of mesozoic carbonates of Kohat Hills Range, KP, Pakistan - Gohar Rehman; Guangcheng Zhang; Maqsood Ur Rahman; Naveed Ur Rahman; Tariq Usman; Muhammad Imraz (Acta Geodaetica et Geophysica, 2020)

Antibacterial and antioxidant activity of naphthofuranquinones from the twigs of tropical mangrove Avicennia officinalis - Suvik Assaw; Muhammad Isyraq Hazim Mohd Amir; Tyng Tyng Khaw; Kamariah Bakar; Siti Aisha Mohd Radzi; Noor Wini Mazlan (Natural Product Research, 2020)

Biological and phytochemical studies on Capparis decidua (Forssk) Edgew from Cholistan desert - Shazia Anjum; Muhammad Asif; Kashaf Zia; Bakhat Jahan; Muhammad Ashraf; Shafqat Hussain; Muhammad Qasim Hayat; Muhammad Raza Shah; Muhammad Nawaz Tahir (Natural Product Research, 2020)

Application of Generalized Likelihood Uncertainty Estimation (GLUE) at different temporal scales to reduce the uncertainty level in modelled river flows - Ragab Ragab; Alexandra Kaelin; Muhammad Afzal; Ioanna Panagea (Hydrological Sciences Journal, 2020)

Application of a Dye-Decolorizing Pseudomonas aeruginosa Strain ZM130 for Remediation of Textile Wastewaters in Aerobic/Anaerobic Sequential Batch Bioreactor and Soil Columns - Zahid Maqbool; Muhammad Shahid; Farrukh Azeem; Tanvir Shahzad; Faisal Mahmood; Muzammal Rehman; Tanvir Ahmed; Muhammad Imran; Sabir Hussain (Water, Air, & Soil Pollution, 2020)

Evaluation of Acer rubrum Tree Bark as a Bioindicator of Atmospheric Heavy Metal Pollution in Toronto, Canada - Muhammad Yousaf; Khakhathi L. Mandiwana; Khurram S. Baig; Julia Lu (Water, Air, & Soil Pollution, 2020)

Detecting Rainfall Trend and Development of Future Intensity Duration Frequency (IDF) Curve for the State of Kelantan - Muhammad Saiful Adham Shukor; Zulkifli Yusop; Fadhillah Yusof; Zulfaqar Sa’adi; Nor Eliza Alias (Water Resources Management, 2020)

Hydrological drought indexing approach in response to climate and anthropogenic activities - Waseem Muhammad; Shahid Muhammad; Noor Muhammad Khan; Chen Si (Theoretical and Applied Climatology, 2020)

Induction of Modern Water Distribution Systems in Punjab of Indo-Pak Subcontinent, South Asia During Late Nineteenth Century by British Government - Muhammad Sohail; Suryyia Manzoor (Sustainable Water Resources Management, 2020)

RETRACTED ARTICLE: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2020)

Probabilistic Seismic Hazard Assessment of Pakistan Territory Using an Areal Source Model - Muhammad Waseem; Sarfraz Khan; M. Asif Khan (Pure and Applied Geophysics, 2020)

Effects of cultivars, water regimes, and growth stages on cadmium accumulation in rice with different radial oxygen loss - Xiuqin Mei; Qusheng Li; Hailong Wang; Hao Fang; Huijun Chen; Xin Chen; Yaoshuai Yang; Muhammad Rizwan; Zhihong Ye (Plant and Soil, 2020)

Generation of High Dose Inhalable Effervescent Dispersions against Pseudomonas aeruginosa Biofilms - Aram Mohammed; Jakub Zurek; Somto Madueke; Hareir Al-Kassimy; Muhammad Yaqoob; Chahinez Houacine; Amina Ferraz; Rachith Kalgudi; Mohammed Gulrez Zariwala; Nicholas Hawkins; Hisham Al-Obaidi (Pharmaceutical Research, 2020)
Purpose Novel particle engineering approach was used in this study to generate high dose inhalable effervescent particles with synergistic effects against Pseudomonas aeruginosa biofilms. Methods Spray dried co-amorphous salt of ciprofloxacin (CFX) and tartaric acid (TA) was prepared and coated with external layer of sodium bicarbonate and silica coated silver nanobeads. Design of experiments (DOE) was used to optimize physicochemical properties of particles for enhanced lung deposition. Results Generated particles were co-amorphous CFX/TA showing that CFX lost its zwitterionic form and exhibiting distinct properties to CFX/HCl as assessed by FTIR and thermal analysis. Particles exhibited mass mean aerodynamic diameter (MMAD) of 3.3 μm, emitted dose of 78% and fine particle dose of 85%. Particles were further evaluated via antimicrobial assessment of minimum inhibitory concentrations (MIC) and minimum biofilm eradication concentration (MBEC). MIC and MBEC results showed that the hybrid particles were around 3–5 times more effective when compared to CFX signifying that synergistic effect was achieved. Diffusing wave spectroscopy results showed that the silver containing particles had a disruptive effect on rheological properties as opposed to silver free particles. Conclusions Overall, these results showed the potential to use particle engineering to generate particles that are highly disruptive of bacterial biofilms.

Preclinical study of the medicinal plants for the treatment of malignant melanoma - Fatma Aydoğmuş-Öztürk; Humera Jahan; Mehmet Öztürk; Keriman Günaydın; Muhammad Iqbal Choudhary (Molecular Biology Reports, 2020)

Advances in exogenous RNA delivery techniques for RNAi-mediated pest control - Olawale Samuel Adeyinka; Saman Riaz; Nida Toufiq; Iqra Yousaf; Muhammad Umar Bhatti; Anicet Batcho; Amos Afolarin Olajide; Idrees Ahmad Nasir; Bushra Tabassum (Molecular Biology Reports, 2020)

Development of green methodologies for Heck, Chan–Lam, Stille and Suzuki cross-coupling reactions - Muhammad Yousaf; Ameer Fawad Zahoor; Rabia Akhtar; Matloob Ahmad; Shazia Naheed (Molecular Diversity, 2020)

Efficient synthesis of 2,3-diarylbenzo[b]thiophene molecules through palladium (0) Suzuki–Miyaura cross-coupling reaction and their antithrombolyitc, biofilm inhibition, hemolytic potential and molecular docking studies - Nosheen Sial; Nasir Rasool; Komal Rizwan; Ataf Ali Altaf; Shaukat Ali; Ayesha Malik; Muhammad Zubair; Arusa Akhtar; Samia Kausar; Syed Adnan Ali Shah (Medicinal Chemistry Research, 2020)

Taxonomic assessment of the Malayan water shrew Chimarrogale hantu Harrison, 1958 and reclassification to the genus Crossogale - Muhammad Farhan Abd Wahab; Dharini Pathmanathan; Masaharu Motokawa; Faisal Ali Anwarali Khan; Hasmahzaiti Omar (Mammalian Biology, 2020)

CO2 and N2O emissions in response to dolomite application are moisture dependent in an acidic paddy soil - Hongtao Wu; Xiaohui Hao; Peng Xu; Jinli Hu; Mengdie Jiang; Muhammad Shaaban; Jinsong Zhao; Yupeng Wu; Ronggui Hu (Journal of Soils and Sediments, 2020)

Soil and microbial biomass stoichiometry regulate soil organic carbon and nitrogen mineralization in rice-wheat rotation subjected to long-term fertilization - Muhammad Nadeem Ashraf; Cheng Hu; Lei Wu; Yinghua Duan; Wenju Zhang; Tariq Aziz; Andong Cai; Muhammad Mohsin Abrar; Minggang Xu (Journal of Soils and Sediments, 2020)

Detection and molecular characterization of Clerodendron yellow mosaic virus infecting Volkameria inermis in Pakistan - Afzal Akram; Aqsa Hafeez Khan; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Journal of Plant Pathology, 2020)

First report of post-harvest Fusarium rot caused by Fusarium oxysporum on Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Fahim Abbas; Aqleem Abbas; Rana Binyamin (Journal of Plant Pathology, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Morpho-molecular identification of Alternaria alternata causing leaf spot on loquat in Pakistan - Muhammad Fahim Abbas; Farah Naz; Sana Batool; Misbah Iqbal Qamar; Anam Moosa (Journal of Plant Pathology, 2020)

First report of pepper leaf curl Bangladesh virus (PepLCBV) associated with cotton leaf curl Multan betasatellite on kidney bean (Phaseolus vulgaris) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Muhammad Zuhaib Khan; Ghulam Raza; Imran Amin; Shahid Mansoor (Journal of Plant Pathology, 2020)

Correction to: Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Aspect ratio effect of multi-walled carbon nanotubes and carbon fibers on high-performance cement mortar matrices - Muhammad Tariq Bashir; Shad Muhammad; Muhammad Jamal Butt; Majed Alzara; Mahmoud Samir El-kady (Innovative Infrastructure Solutions, 2020)

Foliage applied proline induces salt tolerance in chili genotypes by regulating photosynthetic attributes, ionic homeostasis, and antioxidant defense mechanisms - Madiha Butt; Abdul Sattar; Tahira Abbas; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Muhammad Rashid Shaheen; Fawad Kaleem (Horticulture, Environment, and Biotechnology, 2020)

Evaluation of Fagopyrum esculentum Moench germplasm based on agro-morphological traits and the rutin and quercetin content of seeds under spring cultivation - Muhammad Rauf; Hyemyeong Yoon; Sukyeung Lee; Do Yoon Hyun; Myung-Chul Lee; Sejong Oh; Yu -Mi Choi (Genetic Resources and Crop Evolution, 2020)
Buckwheat is an important grain crop known for its nutritional value and content of bioactive compounds, particularly rutin. In this study, we characterized diverse Fagopyrum esculentum Moench germplasm for the diversity of agro-morphological characteristics and the rutin and quercetin content in seeds under the spring cultivation. Of the 251 germplasm accessions assessed, 193 had red stems, 182 had a pale brown seed coat color, and 238 had ovate seeds. The times taken to reach 50% flowering and 80% maturity ranged from 38–45 to 73–95 days, respectively. The 1000-seed weight (TSW) varied from 21 to 42 g. Overall, the content of rutin and quercetin ranged from 7.22–47.86 to 0–1.22 mg/100 g DW, respectively. The number of days to flowering and maturity showed negative correlations with TSW and rutin and quercetin content. However, we found that at 73–80 days after sowing, early-maturing germplasm had significantly higher mean rutin content than either intermediate-or late-maturing germplasm. The TSW weight showed a positive correlation with the content of rutin and quercetin. We identified promising accessions based early maturity (< 80 days), higher seed weight (≥ 35 g) and higher content of rutin (≥ 35 mg/100 g DW) and quercetin (≥ 1 mg/100 g DW). These accessions will help to enhance grain yield and the rutin and quercetin content in existing buckwheat cultivars for spring cultivation.

Mitochondrial DNA diversity in the Khattak and Kheshgi of the Peshawar Valley, Pakistan - Muhammad Zubair; Brian E. Hemphill; Theodore G. Schurr; Muhammad Tariq; Muhammad Ilyas; Habib Ahmad (Genetica, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Climate change adaptation impact on cash crop productivity and income in Punjab province of Pakistan - Dilshad Ahmad; Muhammad Afzal (Environmental Science and Pollution Research, 2020)

Role of public-private partnerships investment in energy and technological innovations in driving climate change: evidence from Brazil - Mahmood Ahmad; Muhammad Yousaf Raza (Environmental Science and Pollution Research, 2020)

Signifying the imperative nexus between climate change and information and communication technology development: a case from Pakistan - Khurram Shehzad; Liu Xiaoxing; Muddassar Sarfraz; Muhammad Zulfiqar (Environmental Science and Pollution Research, 2020)

Hydrogeochemical investigation of arsenic in drinking water of schools and age dependent risk assessment in Vehari District, Punjab Pakistan: a multivariate analysis - Behzad Murtaza; Humaira Nazeer; Natasha; Muhammad Amjad; Muhammad Imran; Muhammad Shahid; Noor S. Shah; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Murtaza (Environmental Science and Pollution Research, 2020)

The impact of airborne pollution and exposure to solar ultraviolet radiation on skin: mechanistic and physiological insight - Atif Ali; Hira Khan; Raheem Bahadar; Asma Riaz; Muhammad Hassham Hassan Bin Asad (Environmental Science and Pollution Research, 2020)

Crop diversification and saline water irrigation as potential strategies to save freshwater resources and reclamation of marginal soils—a review - Muhammad Iftikhar Hussain; Muhammad Farooq; Adele Muscolo; Abdul Rehman (Environmental Science and Pollution Research, 2020)

Investigating the potential of different jute varieties for phytoremediation of copper-contaminated soil - Muhammad Hamzah Saleem; Muzammal Rehman; Muhammad Kamran; Javaria Afzal; Hamza Armghan Noushahi; Lijun Liu (Environmental Science and Pollution Research, 2020)

Human health risk assessment of heavy metals in raw milk of buffalo feeding at wastewater-irrigated agricultural farms in Pakistan - Zafar Iqbal; Farhat Abbas; Muhammad Ibrahim; Tahir Imran Qureshi; Matin Gul; Abid Mahmood (Environmental Science and Pollution Research, 2020)

The asymmetric effects of oil price changes on environmental pollution: evidence from the top ten carbon emitters - Sana Ullah; Muhammad Zubair Chishti; Muhammad Tariq Majeed (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Analyzing the association between innovation, economic growth, and environment: divulging the importance of FDI and trade openness in India - Hashim Zameer; Humaira Yasmeen; Muhammad Wasif Zafar; Abdul Waheed; Avik Sinha (Environmental Science and Pollution Research, 2020)

Cardiac toxicity of heavy metals (cadmium and mercury) and pharmacological intervention by vitamin C in rabbits - Shaukat Ali; Zubia Awan; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Siddique Awan; Saima Sharif; Muhammad Irfan; Muhammad Adeeb Khan (Environmental Science and Pollution Research, 2020)

Sectoral-based CO2 emissions of Pakistan: a novel Grey Relation Analysis (GRA) approach - Erum Rehman; Muhammad Ikram; Ma Tie Feng; Shazia Rehman (Environmental Science and Pollution Research, 2020)

The relationship between economic growth and carbon emissions in G-7 countries: evidence from time-varying parameters with a long history - Mehmet Akif Destek; Muhammad Shahbaz; Ilyas Okumus; Shawkat Hammoudeh; Avik Sinha (Environmental Science and Pollution Research, 2020)

Environmental degradation, economic growth, and energy innovation: evidence from European countries - Muhammad Ali; Syed Ali Raza; Bilal Khamis (Environmental Science and Pollution Research, 2020)

Sulfur dioxide removal: An overview of regenerative flue gas desulfurization and factors affecting desulfurization capacity and sorbent regeneration - Muhammad Adli Hanif; Naimah Ibrahim; Aishah Abdul Jalil (Environmental Science and Pollution Research, 2020)

Synthesis and characterization of poly(N-isopropylmethacrylamide-acrylic acid) smart polymer microgels for adsorptive extraction of copper(II) and cobalt(II) from aqueous medium: kinetic and thermodynamic aspects - Khalida Naseem; Zahoor H. Farooqi; Robina Begum; Muhammad Zia Ur Rehman; Maida Ghufran; Weitai Wu; Jawayria Najeeb; Ahmad Irfan (Environmental Science and Pollution Research, 2020)

Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2020)

Examining the asymmetric effects of globalization and tourism on pollution emissions in South Asia - Muhammad Zubair Chishti; Sana Ullah; Ilhan Ozturk; Ahmed Usman (Environmental Science and Pollution Research, 2020)

Energy-GDP-exports nexus and energy conservation: evidence from Pakistan and South Asia - Muhammad Shakeel; Abdul Salam (Environmental Science and Pollution Research, 2020)

Transfer learning for neural network model in chlorophyll-a dynamics prediction by Wenchong Tian, Zhenliang Liao, and Xuan Wang - Rana Muhammad Adnan; Ozgur Kisi (Environmental Science and Pollution Research, 2020)

Does carbon dioxide, methane, nitrous oxide, and GHG emissions influence the agriculture? Evidence from China - Abdul Rehman; Hengyun Ma; Muhammad Irfan; Munir Ahmad (Environmental Science and Pollution Research, 2020)

Leading edges in bioremediation technologies for removal of petroleum hydrocarbons - Urooj Naeem; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Compositional and health risk assessment of drinking water from health facilities of District Vehari, Pakistan - Behzad Murtaza; Natasha; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Noor Samad Shah; Ghulam Abbas; Muhammad Asif Naeem; Muhammad Amjad (Environmental Geochemistry and Health, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Re-examining log law velocity profile in smooth open channel flows - Nadeeka S. Miguntanna; Hamish Moses; Muttucumaru Sivakumar; Shu-Qing Yang; Keith James Enever; Muhammad Zain Bin Riaz (Environmental Fluid Mechanics, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Biodegradation of Poly(3-hydroxybutyrate) and Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) by Newly Isolated Penicillium oxalicum SS2 in Soil Microcosms and Partial Characterization of Extracellular Depolymerase - Sadia Mehmood Satti; Ziaullah Shah; Aaisha Luqman; Fariha Hasan; Muhammad Osman; Aamer Ali Shah (Current Microbiology, 2020)

High Prevalence of Pantoea in Diaphorina citri (Hemiptera: Liviidae): Vector of Citrus Huanglongbing Disease - Nurper Guz; Muhammad Arshad; Naciye S. Cagatay; Asli Dageri (Current Microbiology, 2020)

Exendin-4 Ameliorates Cardiac Remodeling in Experimentally Induced Myocardial Infarction in Rats by Inhibiting PARP1/NF-κB Axis in A SIRT1-Dependent Mechanism - Refaat A. Eid; Samah A. Alharbi; Attalla Farag El-kott; Samy M. Eleawa; Mohamed Samir Ahmed Zaki; Fahmy El-Sayed; Muhammad Alaa Eldeen; Hussain Aldera; Abd Al-Rahman Salem Al-Shudiefat (Cardiovascular Toxicology, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Seismic fragility analysis of LNG sub-plant accounting for component dynamic interaction - Muhammad Farhan; Stathis Bousias (Bulletin of Earthquake Engineering, 2020)

A double-locus scarless genome editing system in Escherichia coli - Haiqing Liu; Guofeng Hou; Peng Wang; Guiying Guo; Yu Wang; Nuo Yang; Muhammad Nafees Ur Rehman; Changlong Li; Qian Li; Jiping Zheng; Jifeng Zeng; Shanhu Li (Biotechnology Letters, 2020)

Study of Trace Metal Imbalances in the Scalp Hair of Stomach Cancer Patients with Different Types and Stages - Annum Afzal; Muhammad Abdul Qayyum; Munir H. Shah (Biological Trace Element Research, 2020)

Dynamics of fungal and bacterial groups and their carbon sources during the growing season of maize in a long-term experiment - Muhammad Shahbaz; Thomas Kätterer; Barry Thornton; Gunnar Börjesson (Biology and Fertility of Soils, 2020)
The relative contribution of different microbial groups to soil organic matter (SOM) turnover and utilisation of rhizodeposits during a cropping season has remained largely unknown. We used a long-term field experiment (started in 1956), in which C3 crops were replaced with C4 silage maize in 2000, to investigate dynamics of fungi and bacterial groups and their utilisation of ‘young-C4’ and ‘old-C3’ SOM-derived resource every second week during the cropping season (June–Oct). Treatments include bare fallow, unfertilised, fertilised with mineral N and fertilised with farmyard manure (FYM) addition. Extracted soil phospholipid fatty acids (PLFAs) were pooled into Gram-positive, Gram-negative bacteria and fungi (18:2ω6,9) groups and their δ 13 C values determined. Total PLFAs amount correlated to the SOM contents (highest in FYM) and increased over the cropping season in N-fertilised and FYM treatments. As a result of a peak in plant growth during a period with frequent rain events in August, δ 13 C of total PLFAs significantly increased from − 23.8 to − 21.6‰ and − 26.1 to − 24.7‰, in N-fertilised and FYM addition, respectively. This clearly indicated a shift in microbial utilisation from old to young SOM sources, which was linked to increased soil moisture contents and fungal biomass. The abundance of Gram-positive increased and that of Gram-negative bacteria decreased until August and vice versa thereafter. The mean δ 13 C values of individual microbial groups were highest in fungi (corresponding to their seasonal biomass variation) followed by Gram-positive and Gram-negative bacteria. The results clearly demonstrated that irrespective of fertilisation type, fungi were the main players in seasonal SOM dynamics and were strongly influenced by soil moisture and phenological stage of the maize (i.e. rhizodeposition). Disentangling these microbial controls on C resources utilisation will be crucial for understanding C cycling during a cropping season or on an ecosystem scale.

Examination of glucoraphanin content in broccoli seedlings over growth and the impact of hormones and sulfur-containing compounds - Young Cheon Kim; Muhammad Hussain; Mahdi Badri Anarjan; Sanghyeob Lee (Plant Biotechnology Reports, 2020)

Intracranial hemorrhage complicating anticoagulant prophylactic therapy in three hospitalized COVID-19 patients - Muhammad Usman Ghani; Mukesh Kumar; Usman Ghani; Fnu Sonia; Syed Ali Abbas (Journal of NeuroVirology, 2020)

Erratum to: Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
The article Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018, written by Jawaria GUL, Sher MUHAMMAD, LIU Shi-yin, Siddique ULLAH, Shakeel AHMAD, Huma HAYAT and Adnan Ahmad TAHIR, was originally published Online First without Open Access. After publication in volume 17, issue 3, page 572-587, the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original version of this article has been revised due to a retrospective Open Access order.

Vegetation-environment relationship in conifer dominating forests of the mountainous range of Indus Kohistan in northern Pakistan - Adam Khan; Moinuddin Ahmed; Muhammad Faheem Siddiqi; Mohib Shah; Eduardo Soares Calixto; Afsheen Khan; Paras Shah; Javed Iqbal; Muhammad Azeem (Journal of Mountain Science, 2020)

A novel nonsense mutation in NPR2 gene causing Acromesomelic dysplasia, type Maroteaux in a consanguineous family in Southern Punjab (Pakistan) - Saima Mustafa; Zafrin Akhtar; Muhammad Latif; Mubashir Hassan; Muhammad Faisal; Furhan Iqbal (Genes & Genomics, 2020)
Background Acromesomelic dysplasia, type Maroteaux (AMDM) is a rare skeletal dysplasia following autosomal recessive mode of inheritance and characterized by abnormal growth plates, short and abnormal bones in the extremities and spine. Objective Present study was designed to report the molecular basis of AMDM in enrolled consanguineous family from Pakistan. Methods A consanguineous family from Vehari District in Pakistan having multiple siblings suffering from AMDM was enrolled in present study. Whole exome sequencing (WES) approach was adopted to identify causative agent of AMDM. Human full length NPR2 gene and sequence with nonsense mutation was amplified by using Myc-tagged pXN vector and transformed in E. coli DH5α cells to confirm mutation. SDS-PAGE and Western blotting were done to confirm the production of truncated protein. Computational three dimensional structure generation through homology modeling approach was done to compare protein structure between patients and controls. Results WES reveled a nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene leading to premature termination codon in mRNA of NPR2 gene resulting in a truncated protein with 204 amino acid residues that was confirmed by SDS-PAGE and Western blotting. Sanger sequencing confirmed that mutation in all subjects and mutation followed Mendalian pattern of inheritance. Multiple sequence alignment by ClustalW revealed that mutated domain of NPR2 is conserved region. Proetin structure comparison revealed a significant structural part of NPR2 was missing in truncated protein as compared to control. Conclusion We are reporting that a novel nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene is causing AMDM in a consanguineous Pakistani family.

Codiaeum variegatum in Pakistan harbours pedilanthus leaf curl virus and papaya leaf curl virus as well as a newly identified betasatellite - Afzal Akram; Aqsa Hafeez Khan; Ghulam Rasool; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Archives of Virology, 2020)

Characterization and synthetic biology of lipase from Bacillus amyloliquefaciens strain - Muhammad Tahir Khan; Aman Chandra Kaushik; Qurrat ul ain Rana; Shaukat Iqbal Malik; Anwar Sheed Khan; Dong-Qing Wei; Wasim Sajjad; Shabir Ahmad; Sajid Ali; Ameenullah; Muhammad Irfan (Archives of Microbiology, 2020)

A novel approach for high-level expression and purification of GST-fused highly thermostable Taq DNA polymerase in Escherichia coli - Rahman Ud Din; Muhammad Ismail Khan; Asad Jan; Shah Anwar Khan; Irshad Ali (Archives of Microbiology, 2020)

Ecologically controlling insect and mite pests of tea plants with microbial pesticides: a review - Aisha Lawan Idris; Xiao Fan; Musa Hassan Muhammad; Yachong Guo; Xiong Guan; Tianpei Huang (Archives of Microbiology, 2020)

Effect of reservoir models and climate change on flood analysis in arid regions - Ahmed samy Kamis; Abdullah Al-Wagdany; Jarbou Bahrawi; Muhammad Latif; Amro Elfeki; Abdel Hannachi (Arabian Journal of Geosciences, 2020)

Causes, characterization, damage models, and constitutive modes for rock damage analysis: a review - Zulkifl Ahmed; Shuhong Wang; Muhammad Zaffar Hashmi; Zhang Zishan; Zhu Chengjin (Arabian Journal of Geosciences, 2020)

Evaluation of edible bird’s nest processing plant wastewater quality: a factory case study - Siti Shahara Zulfakar; Farah Natasha Haezam; Mohd Sham Othman; Nur Faizah Abu Bakar; Muhammad Ikram A. Wahab (Arabian Journal of Geosciences, 2020)

Biochar impact on microbial population and elemental composition of red soil - Zabih Ullah; Shafaqat Ali; Niaz Muhammad; Naeem Khan; Muhammad Rizwan; Muhammad Daud Khan; Niamat Khan; Baharullah Khattak; Haifa Abdulaziz S. Alhaithloul; Mona H. Soliman; Hamid Ullah; Dilnaz Begum; et al. (Arabian Journal of Geosciences, 2020)

Effect of particle morphology on mechanical behavior of rock mass - Kausar Sultan Shah; Mohd Hazizan bin Mohd Hashim; Muhammad Zaka Emad; Kamar Shah bin Ariffin; Muhammad Junaid; Naseer Muhammad Khan (Arabian Journal of Geosciences, 2020)

Geoinformatics and geophysical survey-based estimation of best groundwater potential sites through surface and subsurface indicators - Umair Rasool; Jianping Chen; Shafi Muhammad; Jamil Siddique; Senapathi Venkatramanan; Chidambaram Sabarathinam; Muhammad Amir Siddique; Muhammad Awais Rasool (Arabian Journal of Geosciences, 2020)

Spatio-temporal assessment and climatology of atmospheric organic carbon over Pakistan - Muhammad Zaffar Hashmi; Khadija Ashraf; Shahzada Adnan; Shuhong Wang; Siwatt Pongpiachan; Xiaomei Su; Zulkfil Ahmed (Arabian Journal of Geosciences, 2020)

Angiostatic effects of ascorbic acid: current status and future perspectives - Muhammad Torequl Islam (Angiogenesis, 2020)

Seismicity analysis of selected faults in Makran Southern Pakistan - Muhammad Jahangir Khan; Mubarik Ali; Min Xu; Mehrab Khan (Acta Geophysica, 2020)

Modelling reference evapotranspiration by combining neuro-fuzzy and evolutionary strategies - Meysam Alizamir; Ozgur Kisi; Rana Muhammad Adnan; Alban Kuriqi (Acta Geophysica, 2020)

Formulation Development, Characterization, and Evaluation of a Novel Dexibuprofen-Capsaicin Skin Emulgel with Improved In Vivo Anti-inflammatory and Analgesic Effects - Imran Khan Burki; Muhammad Khalid Khan; Barkat Ali Khan; Bushra Uzair; Valdir A. Braga; Qazi Adnan Jamil (AAPS PharmSciTech, 2020)

Development of primary cell culture from spleen of giant gourami Osphronemus goramy for propagation of giant gourami iridovirus (GGIV) - Lila Gardenia; Sukenda Sukenda; Muhammad Zairin Junior; Angela Lusiastuti; Alimuddin Alimuddin (Journal of Fish Diseases, 2020)
The severe mortality of fish due to the infection of megalocytivirus caused significant economic losses. Since 2011, megalocytivirus (giant gourami iridovirus (GGIV)) has become the main pathogen in giant gourami ( Osphronemus goramy ), particularly in West Java, Central Java and Bali. This study aimed to develop primary cell culture from spleen as the target organ for propagating megalocytivirus in vitro, which was developed by explant method with enzymatic dissociation. Optimization was carried out at incubation temperature, medium and serum concentrations. The origin of the primary cell, cell susceptibility and GGIV pathogenicity were observed. The results showed that the primary cell (GP cells) can grow well in 10% foetal bovine serum L‐15 medium at 27°C, which was sufficient for cell growth. PCR and BLAST analyses showed the primary cell was originated from giant gourami. In infected GP cells, cell enlargement and cell rounding were observed. Virus propagated in GP cells was highly virulent when injecting giant gourami in an artificial infection experiment. Intraperitoneal injection of diluted virus supernatant showed 100% mortality in 7–11 days post‐injection and 97% mortality in 21 days post‐cohabitation, with abnormalities observed in spleen and kidney. In conclusion, GP cell was successfully subcultured for more than 30 passages and susceptible to GGIV.

Effects of land use and climate variability on the main stream of the Songhua River Basin, Northeast China - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Faisal Baig; Ahmad Niaz; Tianxiao Li (Hydrological Sciences Journal, 2020)

Chemical constituents from leaves and trunk bark of Rinorea oblongifolia (Violaceae) - Aristide Mfifen Munvera; Blandine Marlyse Wache Ouahouo; Pierre Mkounga; Michelle Ines Kanko Mbekou; Shehla Nuzhat; Muhammad Iqbal Choudhary; Augustin Ephrem Nkengfack (Natural Product Research, 2020)

State-of-the-art strategies and applied perspectives of enzyme biocatalysis in food sector — current status and future trends - Muhammad Bilal; Hafiz M. N. Iqbal (Critical Reviews in Food Science and Nutrition, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

Assessment of antibiotics use for children upper respiratory tract infections: a retrospective, cross-sectional study from Pakistan - Zia Ul Mustafa; Muhammad Salman; Alina Zeeshan Rao; Noman Asif; Sanan Amjad Butt; Naureen Shehzadi; Khalid Hussain (Infectious Diseases, 2020)

Evaluation of Diffusivity and Wettability of Crude Oil-Contaminated Sand from Offshore Petroleum Facility Prior to Remediation Process - Muhammad Shafiq Mat-Shayuti; Tuan Mohammad Yusoff Shah Tuan Ya; Mohamad Zaki Abdullah; Nur Hashimah Alias; Nur Hidayati Othman; Suzalina Zainal (Water, Air, & Soil Pollution, 2020)

The Presence of Microplastics in Water, Sediment, and Milkfish (Chanos chanos) at the Downstream Area of Citarum River, Indonesia - Emenda Sembiring; Achmad Agustian Fareza; Veinardi Suendo; Muhammad Reza (Water, Air, & Soil Pollution, 2020)

Effect of fans and showers on the physiological measures and reproductive performance of Holstein Friesian bulls during subtropical summer - Mahboob Ahmed Butt; Jalees Ahmed Bhatti; Anjum Khalique; Muhammad Qamer Shahid (Tropical Animal Health and Production, 2020)

A comparative evaluation of serum biochemistry profile and antigenic relatedness among velogenic and mesogenic Avian avulavirus 1 infection in chickens and pigeons - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Mushtaq Ahmed; Muhammad Zubair Shabbir (Tropical Animal Health and Production, 2020)

An investigation on the prevalence of peste des petits ruminants in the camels of Sindh, Pakistan - Hamidur Rahman; Asghar Ali Kamboh; Shahid Hussain Abro; Muhammad Abubakar (Tropical Animal Health and Production, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Foliar application of melatonin delay leaf senescence in maize by improving the antioxidant defense system and enhancing photosynthetic capacity under semi-arid regions - Shakeel Ahmad; Wennan Su; Muhammad Kamran; Irshad Ahmad; Xiangping Meng; Xiaorong Wu; Tehseen Javed; Qingfang Han (Protoplasma, 2020)

Light-mediated biosynthesis of phenylpropanoid metabolites and antioxidant potential in callus cultures of purple basil (Ocimum basilicum L. var purpurascens) - Munazza Nazir; Muhammad Asad Ullah; Muhammad Younas; Aisha Siddiquah; Muzamil Shah; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Silybum marianum (milk thistle) improves vancomycin induced nephrotoxicity by downregulating apoptosis - Naila Malkani; Ammara Naeem; Farah Ijaz; Sidra Mumtaz; Saima Ashraf; Muhammad Imran Sohail (Molecular Biology Reports, 2020)

Evolutionarily conserved and testis-specific gene, 4930524B15Rik, is not essential for mouse spermatogenesis and fertility - Ranjha Khan; Jingwei Ye; Ayesha Yousaf; Wasim Shah; Ayesha Aftab; Basit Shah; Qamar Zaman; Muhammad Zubair; Qinghua Shi; Xiaohua Jiang (Molecular Biology Reports, 2020)

Influence of early rearing environment on water-borne cortisol and expression of stress-related genes in grass carp (Ctenopharyngodon idella) - Mahmood ul Hassan Murtaza; Amina Zuberi; Muhammad Ahmad; Imrana Amir; Muhammad Kamran; Manzoor Ahmad (Molecular Biology Reports, 2020)

Protein kinase CK2 impact on intracellular calcium homeostasis in prostate cancer - Muhammad Afzal; Betsy T. Kren; A. Khaliq Naveed; Janeen H. Trembley; Khalil Ahmed (Molecular and Cellular Biochemistry, 2020)

Phenolic Profile and Thermal Stability of Monovarietal Extra Virgin Olive Oils Based on Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Azhar Iqbal; Babar Manzoor Atta; Rahat Ullah; Muhammad Bilal Khan (Journal of Fluorescence, 2020)

Application of Fluorescence Spectroscopy in Wheat Crop: Early Disease Detection and Associated Molecular Changes - Babar Manzoor Atta; Muhammad Saleem; Hina Ali; Muhammad Bilal; Muhammad Fayyaz (Journal of Fluorescence, 2020)

Citric acid enhanced phytoextraction of nickel (Ni) and alleviate Mentha piperita (L.) from Ni-induced physiological and biochemical damages - Kashaf Ul Khair; Mujahid Farid; Umair Ashraf; Muhammad Zubair; Muhammad Rizwan; Sheharyaar Farid; Hafiz Khuzama Ishaq; Usman Iftikhar; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Bisphenol-A induced antioxidants imbalance and cytokines alteration leading to immune suppression during larval development of Labeo rohita - Mehwish Faheem; Muhammad Adeel; Saba Khaliq; Khalid P. Lone; Alaa El-Din-H-Sayed (Environmental Science and Pollution Research, 2020)

A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Human exposure to bisphenol A through dietary sources and development of diabetes mellitus: a cross-sectional study in Pakistani population - Muhammad Ejaz Ul Haq; Muhammad Sajid Hamid Akash; Shakila Sabir; Malik Hassan Mahmood; Kanwal Rehman (Environmental Science and Pollution Research, 2020)

Examining the impacts of future land use/land cover changes on climate in Punjab province, Pakistan: implications for environmental sustainability and economic growth - Abdus Samie; Azhar Abbas; Muhammad Masood Azeem; Sidra Hamid; Muhammad Amjed Iqbal; Shaikh Shamim Hasan; Xiangzheng Deng (Environmental Science and Pollution Research, 2020)

Toxicity evaluation of pesticide chlorpyrifos in male Japanese quails (Coturnix japonica) - Suliman; Ajmal Khan; Syed Sajjad Ali Shah; Naila Gulfam; Muhammad Khisroon; Muhammad Zahoor (Environmental Science and Pollution Research, 2020)

Climate change–induced human conflicts and economic costs in Pakistani Punjab - Khuda Bakhsh; Karim Abbas; Sarfraz Hassan; Muhammad Asim Yasin; Rafaqet Ali; Najid Ahmad; Muhammad Waqas Alam Chattha (Environmental Science and Pollution Research, 2020)

The effects of FDI, technological innovation, and financial development on CO2 emissions: evidence from the BRICS countries - Muhammad Zahid Rafique; Yafei Li; Abdul Razaque Larik; Malepekola Precious Monaheng (Environmental Science and Pollution Research, 2020)

Determinants of household cooking fuels and their impact on women’s health in rural Pakistan - Muhammad Imran; Orhan Ozcatalbas (Environmental Science and Pollution Research, 2020)

Effect of composted organic amendments and zinc oxide nanoparticles on growth and cadmium accumulation by wheat; a life cycle study - Arooj Bashir; Muhammad Rizwan; Shafaqat Ali; Muhammad Adrees; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum (Environmental Science and Pollution Research, 2020)

Does financial development and foreign direct investment improve environmental quality? Evidence from belt and road countries - Mahmood Ahmad; Ping Jiang; Abdul Majeed; Muhammad Yousaf Raza (Environmental Science and Pollution Research, 2020)

Influence of Pseudomonas japonica and organic amendments on the growth and metal tolerance of Celosia argentea L. - Ameena Iqbal; Muhammad Umair Mushtaq; Aqib Hassan Ali Khan; Ismat Nawaz; Sohail Yousaf; Zeshan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Temporal and climate characteristics of respiratory syncytial virus bronchiolitis in neonates and children in Sousse, Tunisia, during a 13-year surveillance - Ines Brini; Sana Bhiri; Muhammad Ijaz; Jihene Bouguila; Sonia Nouri-Merchaoui; Lamia Boughammoura; Hassen Sboui; Naila Hannachi; Jalel Boukadida (Environmental Science and Pollution Research, 2020)

Modeling the transition behaviors of PM10 pollution index - Nurulkamal Masseran; Muhammad Aslam Mohd Safari (Environmental Monitoring and Assessment, 2020)

Zinc status and its requirement by rural adults consuming wheat from control or zinc-treated fields - Muhammad Ahsin; Shahid Hussain; Zed Rengel; Mamoona Amir (Environmental Geochemistry and Health, 2020)

Classification of the intact carbonate and silicate rocks based on their degree of thermal cracking using discriminant analysis - Umer Waqas; M. Farooq Ahmed; Muhammad Arshad (Bulletin of Engineering Geology and the Environment, 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

Human Biomonitoring of Trace Elements in Scalp Hair from Healthy Population of Pakistan - Fouzia Noreen; Ashif Sajjad; Khalid Mahmood; Muhammad Anwar; Manzar Zahra; Amir Waseem (Biological Trace Element Research, 2020)

Three-dimensional visualization of mitochondria in conidia of Pyricularia oryzae using green fluorescent protein (GFP) fused with citrate synthase (CitA) - Muhammad Akhid Syib’li; Aoi Kodama; Ayumi Abe; Teruo Sone (Journal of General Plant Pathology, 2020)

Pigment production by cold-adapted bacteria and fungi: colorful tale of cryosphere with wide range applications - Wasim Sajjad; Ghufranud Din; Muhammad Rafiq; Awais Iqbal; Suliman Khan; Sahib Zada; Barkat Ali; Shichang Kang (Extremophiles, 2020)

Vibration analysis of damaged and undamaged steel structure systems: cantilever column and frame - Muhammad Abuzar Khan; Kareem Akhtar; Naveed Ahmad; Feroz Shah; Naeem Khattak (Earthquake Engineering and Engineering Vibration, 2020)

Cotton leaf curl Kokhran virus in association with Chili leaf curl betasatellite infecting mungbean (Vigna radiata.) and black gram (Vigna mungo.) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Ghulam Raza; Muhammad Zuhaib Khan; Shahid Mansoor; Imran Amin (Australasian Plant Pathology, 2020)

Microbial l-asparaginase: purification, characterization and applications - Faizan Muneer; Muhammad Hussnain Siddique; Farrukh Azeem; Ijaz Rasul; Saima Muzammil; Muhammad Zubair; Muhammad Afzal; Habibullah Nadeem (Archives of Microbiology, 2020)

Diabetes-associated infections: development of antimicrobial resistance and possible treatment strategies - Muhammad Sajid Hamid Akash; Kanwal Rehman; Fareeha Fiayyaz; Shakila Sabir; Mohsin Khurshid (Archives of Microbiology, 2020)

2D numerical modeling of two dam-break flood model studies in an urban locality - Sajjad Haider; Umer Saeed; Muhammad Shahid (Arabian Journal of Geosciences, 2020)

Varying characteristics of electromagnetic radiation from coal failure during hydraulic flushing in coal seam - Hao Wang; Wang Enyuan; Zhonghui Li; Xiaoran Wang; Dexing Li; Muhammad Ali; Qiming Zhang (Arabian Journal of Geosciences, 2020)

Systematic and paleoecological study of the new remains of Brachypotherium (Rhinocerotidae) from the Middle Miocene Siwaliks (Pakistan) - Amtur Rafeh; Abdul Majid Khan; Rana Manzoor Ahmad; Mudassar Iqbal; Muhammad Akhtar (Arabian Journal of Geosciences, 2020)

Occurrence of heavy metals and pesticide residues in tomato crop: a threat to public health - Muhammad Ishaq; Nighat Sultana; Muhammad Ikram; Amjad Iqbal; Farooq Shah; Muhammad Hamayun; Anwar Hussain (Arabian Journal of Geosciences, 2020)

Eocene carbonate microfacies distribution of the Chorgali Formation, Gali Jagir, Khair-e-Murat Range, Potwar Plateau, Pakistan: approach of reservoir potential using outcrop analogue - Muhammad Awais; Muhammad Hanif; Irfan U. Jan; Muhammad Ishaq; Muhammad Younis Khan (Arabian Journal of Geosciences, 2020)

Study of sunspot cycles using fractal dimensions: wave-spectrum scaling - Asma Zaffar; Shaheen Abbas; Muhammad Rashid Kamal Ansari (Arabian Journal of Geosciences, 2020)

Arsenic distribution and metabolism genes abundance in Paddy soils from Punjab and Sindh provinces, Pakistan - Muhammad Zaffar Hashmi; Aatika Kanwal; Siwatt Pongpiachan; Xiaomei Su; Wajid Nasim; Mumtaz Ali Saand; Muhammad Mubeen; Rida Akram; Shuhong Wang; Zulkfil Ahmed (Arabian Journal of Geosciences, 2020)

Soil salinity detection and monitoring using Landsat data: a case study from Kot Addu, Pakistan - Moeen Ijaz; Hamaad Raza Ahmad; Sadia Bibi; Muhammad Ashar Ayub; Shoaib Khalid (Arabian Journal of Geosciences, 2020)

Use of subsurface temperature as a groundwater flow tracer in the environs of Ismailia Canal, Eastern Nile Delta, Egypt - Zenhom El-Said Salem; Mohamed Sobhy Fathy; Abdel-Fattah Ibrahim Helal; Sofia Yahia Afifi; Abdullah Muhammad Attiah (Arabian Journal of Geosciences, 2020)

Lipospheres for Simultaneous Controlled Release and Improved Pharmacokinetic Profiles of Saxagliptin-Enalapril: Formulation, Optimization, and Comparative In Vitro-In Vivo Evaluation - Safirah Maheen; Akhtar Rasul; Muhammad Hanif; Hafeez Ullah Khan (AAPS PharmSciTech, 2020)

Formulation of Chitosan Polymeric Vesicles of Ciprofloxacin for Ocular Delivery: Box-Behnken Optimization, In Vitro Characterization, HET-CAM Irritation, and Antimicrobial Assessment - Ameeduzzafar; Nabil K Alruwaili; Syed Sarim Imam; Nasser Hadal Alotaibi; Nabil A. Alhakamy; Khalid Saad Alharbi; Sultan Alshehri; Muhammad Afzal; Sattam Khulaif Alenezi; Syed Nasir Abbas Bukhari (AAPS PharmSciTech, 2020)

MUCO-DIS: a New AFM-Based Nanoscale Dissolution Technique - Muhammad Usman Ghori; Jorabar Singh Nirwan; Taimoor Asim; Younes Chahid; Samia Farhaj; Zara Khizer; Peter Timmins; Barbara R. Conway (AAPS PharmSciTech, 2020)
Mucoadhesion-based drug delivery systems have recently gained interest because of their bio-adhesion capability, which results in enhanced residence time leading to prolonged duration of action with the mucosal surface, potentially improving compliance and convenience. Mucoadhesion testing of these formulations is widely reported; however, this is technically challenging due to the absence of any standard methods and difficulty in conducting mucoadhesion, formulation-mucosal surface interaction, mucosal surface topography and drug release in a single experiment. As these measurements are currently conducted separately, on replicate formulations, results can often be subjective and difficult to correlate. Hence, the aim of the present study was to develop a new AFM-based single-entity ex vivo muco-dissolution (MUCO-DIS) technique to simultaneously evaluate mucoadhesion force, 3D surface topography, polymer dissolution and drug release characteristics. To demonstrate the potential of the current technique, the interactions between model pectin microparticles containing metformin HCl and a range of gastrointestinal mucosal surfaces (gastric, small intestine, large intestine and buccal) were studied. This novel system has not only successfully determined the mucoadhesion force, polymer dissolution and drug release information but has also highlighted the difference in microparticle performance with different mucosal targets. The current work has highlighted the potential of this newly developed MUCO-DIS system and we believe this will be a valuable tool for characterising these popular pharmaceutical formulations. This technique could also provide an opportunity to other scientific fields to evaluate materials, substrate behaviour and their interactions in their hydrated state at nanoscale with real-time chemical and surface mapping.

Multiple observation processes in spatial capture–recapture models: How much do we gain? - Mahdieh Tourani; Pierre Dupont; Muhammad Ali Nawaz; Richard Bischof (Ecology, 2020)
Population monitoring data may originate from multiple methods and are often sparse and fraught with incomplete information due to practical and economic constraints. Models that can integrate multiple survey methods and are able to cope with incomplete data may help investigators exploit available information more thoroughly. Here, we developed an integrated spatial capture–recapture (SCR) model to incorporate multiple data sources with imperfect individual identification. We contrast inferences drawn from this model with alternate models incorporating only subsets of the data available. Using extensive simulations and an empirical example of multi‐method brown bear ( Ursus arctos ) monitoring data from northern Pakistan, we quantified the benefits of including multiple sources of information in SCR models in terms of parameter precision and bias. Our multiple observation processes SCR model (MOP) yielded a more complete picture of the underlying processes, reduced bias, and led to more precise parameter estimates. Our results suggest that the greatest gains from integrated SCR models can be expected in situations where detection probability is low, a large proportion of detections is not attributable to individuals, and the degree of overlap between individual home ranges is low.

Population Genetics of Konosirus punctatus in Chinese Coastal Waters Inferred From Two mtDNA Genes (COI and Cytb) - Bingjian Liu; Kun Zhang; Kehua Zhu; Muhammad Shafi; Li Gong; Lihua Jiang; Liqin Liu; Faiz Muhammad; Zhenming Lü (Frontiers in Marine Science, 2020)

Risk Assessment of Work Accident in Container Terminals Using the Fault Tree Analysis Method - Muhammad Arif Budiyanto; Haris Fernanda (Journal of Marine Science and Engineering, 2020)
The use of containers in the world is increasing every year in line with international trade flows. In very complex container terminal operations, the risk of work accidents is inevitable and can happen at any time. Therefore, this paper aimed to identify accidents and potential risks occurring in the container terminals. For the case study, the analysis was used the data of accidents during five years in one of the major container terminals in Indonesia. Risk assessment is carried out using the risk matrix method to get the level of risk. The risk that has the highest level is analyzed by using the Fault Tree Analysis method. From the results of the risk assessment shows the container fell to the berth when loading and unloading have the highest risk value. While the results of the Fault Tree Analysis show that traffic accidents are the biggest potential risk, which is 41.8% compared to other accidents. Moreover, human factors especially due to the negligence in operating vehicles or equipment as well as the damage of equipment were the highest common causes of accidents in the container terminal. Based on these results the contribution offered is the risk control options for terminal operators to reduce the possibility of safety failure in the container terminal.

Cavitation Prediction of Ship Propeller Based on Temperature and Fluid Properties of Water - Muhammad Yusvika; Aditya Rio Prabowo; Dominicus Danardono Dwi Prija Tjahjana; Jung Min Sohn (Journal of Marine Science and Engineering, 2020)
Cavitation is a complex phenomenon to measure, depending on site conditions in specific regions of the Earth, where there is water with various physical properties. The development of ship and propulsion technology is currently intended to further explore territorial waters that are difficult to explore. Climate differences affect the temperature and physical properties of water on Earth. This study aimed to determine the effect of cavitation related to the physical properties of water. Numerical predictions of a cavitating propeller in open water and uniform inflow are presented with computational fluid dynamics (CFD). Simulations were carried out using Ansys. Numerical simulation based on Reynolds-averaged Navier–Stokes equations for the conservative form and the Rayleigh–Plesset equation for the mass transfer cavitation model was conducted with turbulent closure of the fully turbulent K-epsilon (k-ε) model and shear stress transport (SST). The influence of temperature on cavitation extension was investigated between 0 and 50 ° C . The results obtained showed a trend of cavitation occurring more aggressively at higher water temperature than at lower temperature.

Remote sensing of water turbidity in the Eastern China Seas from Geostationary Ocean Colour Imager - Shengqiang Wang; Ying Mao; Lufei Zheng; Zhongfeng Qiu; Muhammad Bilal; Deyong Sun (International Journal of Remote Sensing, 2020)

Human Exposure and Risk Assessment Due to Toxic Heavy Metals in Groundwater of Larkana City - Abdul Hameed Kori; Sarfaraz Ahmed Mahesar; Muhammad Saqaf Jagirani; Zahid Hussain Laghari; Tarique Panhwar; Muhammad Dodo Jagirani; Oan Muhammad Sahito; Muhammad Farooque Lanjwani (Water, Air, & Soil Pollution, 2020)

Advanced Degradation of Lignin from Palm Oil Mill Effluent (POME) by a Combination of Photocatalytic-Fenton Treatment and TiO2 Nanoparticle as the Catalyst - Osi Arutanti; Ajeng Arum Sari; Anita Berkah; Muhammad Nurdin; Muhammad Arifuddin Fitriady; Yusnita Parmawati; Nino Rinaldi; Adhi Yuniarto; Tony Hadibarata (Water, Air, & Soil Pollution, 2020)

Inanimate surfaces as potential source of 2019-nCoV spread and their disinfection with biocidal agents - Muhammad Zeeshan Akram (VirusDisease, 2020)

Human coronaviruses with emphasis on the COVID-19 outbreak - Saraj Bahadur; Wenxing Long; Muhammad Shuaib (VirusDisease, 2020)

Calcium-mediated adaptive responses to low phosphorus stress in Chinese fir - Muhammad Haroon U. Rashid; Mulualem Tigabu; Haifeng Chen; Taimoor Hassan Farooq; Xiangqing Ma; Pengfei Wu (Trees, 2020)

A Study of the Role of Microfractures in Counter-Current Spontaneous Imbibition by Lattice Boltzmann Simulation - Yang Liu; Jianchao Cai; Muhammad Sahimi; Chaozhong Qin (Transport in Porous Media, 2020)

Roles of insulin-like growth factor II in regulating female reproductive physiology - Tahir Muhammad; Mengjing Li; Jianfeng Wang; Tao Huang; Shigang Zhao; Han Zhao; Hongbin Liu; Zi-Jiang Chen (Science China Life Sciences, 2020)

Single or Combined Applications of Zinc and Multi-strain Probiotic on Intestinal Histomorphology of Broilers Under Cyclic Heat Stress - Muqader Shah; Hafsa Zaneb; Saima Masood; Rifat Ullah Khan; Muhammad Mobashar; Imad Khan; Salahud Din; Muhammad Shoaib Khan; Habib Ur Rehman; Antonella Tinelli (Probiotics and Antimicrobial Proteins, 2020)

Effect of foliar applied triacontanol on wheat (Triticum aestivum L.) under arsenic stress: a study of changes in growth, yield and photosynthetic characteristics - Hafiz Muhammad Mubashar Ali; Shagufta Perveen (Physiology and Molecular Biology of Plants, 2020)

Thermal structure of hot events and their possible role in maintaining the warm isothermal layer in the Western Pacific warm pool - Anindya Wirasatriya; Hiroshi Kawamura; Muhammad Helmi; Denny Nugroho Sugianto; Teruhisa Shimada; Kohtaro Hosoda; Gentur Handoyo; Yoppik Disma Girindra Putra; Magaly Koch (Ocean Dynamics, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Cross talk between Hsp72, HMGB1 and RAGE/ERK1/2 signaling in the pathogenesis of bronchial asthma in obese patients - Nema Ali Soliman; Muhammad Tarek Abdel Ghafar; Reham Mohamed El Kolaley; Yasser Mostafa Hafez; Rehab E. Abo Elgheit; Marwa Mohamed Atef (Molecular Biology Reports, 2020)

Transcriptome analysis of heat stress response genes in potato leaves - Ruimin Tang; Sanjay K. Gupta; Suyan Niu; Xiu-Qing Li; Qing Yang; Guanshui Chen; Wenjiao Zhu; Muhammad Haroon (Molecular Biology Reports, 2020)

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

Effect of Buried Straw Layer Coupled with Fertigation on Florescence and Yield Parameters of Chinese Cabbage Under Greenhouse Environment - Ghulam Rasool; Xiangping Guo; Zhenchang Wang; Muhammad Hassan; Muhammad Aleem; Qaiser Javed; Sheng Chen (Journal of Soil Science and Plant Nutrition, 2020)

Effects of Silicon and Phosphatic Fertilization on Rice Yield and Soil Fertility - Liying Wang; Umair Ashraf; Chunrong Chang; Muhammad Abrar; Xiong Cheng (Journal of Soil Science and Plant Nutrition, 2020)

Mitigation of Arsenic Toxicity in Wheat by the Exogenously Applied Salicylic Acid, 24-Epi-Brassinolide and Silicon - Kobra Maghsoudi; Mohammad Javad Arvin; Muhammad Ashraf (Journal of Soil Science and Plant Nutrition, 2020)

Integrated Effect of Algal Biochar and Plant Growth Promoting Rhizobacteria on Physiology and Growth of Maize Under Deficit Irrigations - Naseer Ullah; Allah Ditta; Azeem Khalid; Sajid Mehmood; Muhammad Shahid Rizwan; Muhammad Ashraf; Fathia Mubeen; Muhammad Imtiaz; Muhammad Mazhar Iqbal (Journal of Soil Science and Plant Nutrition, 2020)

Distribution and Mobility of Foliar-Applied Boron (10B) in Citrange Rootstock Under Different Boron Conditions - Xiuwen Wu; Muhammad Riaz; Lei Yan; Cuncang Jiang (Journal of Plant Growth Regulation, 2020)

Downregulation of chitin synthase A gene by diallyl trisulfide, an active substance from garlic essential oil, inhibits oviposition and alters the morphology of adult Sitotroga cerealella - Sakhawat Shah; Muhammad Hafeez; Meng-Ya Wu; Su-Su Zhang; Muhammad Ilyas; Gang Wu; Feng-Lian Yang (Journal of Pest Science, 2020)

Fluctuating temperatures influence the susceptibility of pest insects to biological control agents - Muhammad Usman Ghazanfar; Steffen Hagenbucher; Jörg Romeis; Giselher Grabenweger; Michael Meissle (Journal of Pest Science, 2020)

Abundance, type, and origin of litter on No. 1 Bathing Beach of Qingdao, China - Rashid Pervez; Yonghong Wang; Qaisar Mahmood; Muhammad Zahir; Zafarullah Jattak (Journal of Coastal Conservation, 2020)

Influence of Crapemyrtle aphid, Tinocallis kahawaluokalani (Hemiptera: Aphididae) on population characteristics of three aphidophagous ladybird beetles - Muhammad Asif Aziz; Habiba Sadaf; Ayesha Iftikhar; Faisal Hafeez (International Journal of Tropical Insect Science, 2020)

Salivary Proteomic Analysis of Betel Nut (Areca catechu) Consumers by Mass Spectrometry Revealed Primary Indication of Oral Malignancies - Rabia Sultan; Munazza Raza Mirza; Muhammad Iqbal Choudhary; Mehtab Alam; Ikram-ul Haque (International Journal of Peptide Research and Therapeutics, 2020)

Debris Flow Susceptibility Assessment and Runout Prediction: A Case Study in Shiyang Gully, Beijing, China - Yongchao Li; Jianping Chen; Yiwei Zhang; Shengyuan Song; Xudong Han; Muhammad Ammar (International Journal of Environmental Research, 2020)

Efficacy of Alternanthera bettzickiana to Remediate Copper and Cobalt Contaminated Soil Physiological and Biochemical Alterations - Amna Khalid; Mujahid Farid; Muhammad Zubair; Muhmmad Rizwan; Usman Iftikhar; Hafiz Khuzama Ishaq; Sheharyaar Farid; Urousa Latif; Kiran Hina; Shafaqat Ali (International Journal of Environmental Research, 2020)

An Integrated Systems Biology and Network-Based Approaches to Identify Novel Biomarkers in Breast Cancer Cell Lines Using Gene Expression Data - Abbas Khan; Zainab Rehman; Huma Farooque Hashmi; Abdul Aziz Khan; Muhammad Junaid; Abrar Mohammad Sayaf; Syed Shujait Ali; Fakhr Ul Hassan; Wang Heng; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Impact of interleukin IL-6 rs-1474347 and IL-10 rs-1800896 genetic polymorphisms on the susceptibility of HCV-infected Egyptian patients to hepatocellular carcinoma - Reham M. Abd El-Baky; Helal F. Hetta; Gopala Koneru; Marwa Ammar; Engy A. Shafik; Dina A Mohareb; Muhammad Abbas El-Masry; Haidi K. Ramadan; Mohamed Zakaria Abu Rahma; Michael A. Fawzy; Moustafa Fathy (Immunologic Research, 2020)

Ingestion of Arsenic-Contaminated Drinking Water Leads to Health Risk and Traces in Human Biomarkers (Hair, Nails, Blood, and Urine), Pakistan - Ubaid ur Rehman; Sardar Khan; Said Muhammad (Exposure and Health, 2020)

Analyzing carbon emission transfer network structure among provinces in China: new evidence from social network analysis - Licheng Sun; Lin Qin; Farhad Taghizadeh-Hesary; Jijian Zhang; Muhammad Mohsin; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Selective extraction and recovery of polyphenols from palm oil mill sterilization condensate using emulsion liquid membrane process - Norela Jusoh; Muhammad Bukhari Rosly; Norasikin Othman; Hilmi Abdul Rahman; Norul Fatiha Mohamed Noah; Raja Norimie Raja Sulaiman (Environmental Science and Pollution Research, 2020)

Assessing the climate change impacts and adaptation strategies for rice production in Punjab, Pakistan - Ghulam Shabbir; Tasneem Khaliq; Ashfaq Ahmad; Muhammad Saqib (Environmental Science and Pollution Research, 2020)

The efficacy of sustainability reporting towards cost of debt and equity reduction - Muhammad Kashif Shad; Fong-Woon Lai; Amjad Shamim; Michael McShane (Environmental Science and Pollution Research, 2020)

Environmental risks among rice farmers and factors influencing their risk perceptions and attitudes in Punjab, Pakistan - Dilshad Ahmad; Muhammad Afzal; Abdur Rauf (Environmental Science and Pollution Research, 2020)

The influence of consumers’ intention factors on willingness to pay for renewable energy: a structural equation modeling approach - Muhammad Irfan; Zhen-Yu Zhao; Heng Li; Abdul Rehman (Environmental Science and Pollution Research, 2020)

Evaluating the toxicity of polyurethane during marine clay stabilisation - Samaila Saleh; Kamarudin Ahmad; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi (Environmental Science and Pollution Research, 2020)

Knowledge, attitudes, and practices of Egypt’s future physicians towards antimicrobial resistance (KAP-AMR study): a multicenter cross-sectional study - Ahmed Assar; Mohamed Ibrahim Abdelraoof; Mohamed Abdel-Maboud; Kerollos H. Shaker; Amr Menshawy; Asia Hamdy Swelam; Muhammad Eid; Radwa Khalid; Mohamed Mogahed; Abdelrahman I. Abushouk; Lotfi Aleya; Mohamed Abdel-Daim (Environmental Science and Pollution Research, 2020)

Health risks from trace elements in muscles of some commonly available fish in Australia and India - Mohammad Mahmudur Rahman; Muhammad Tahir Shehzad; Amaresh Kumar Nayak; Shruti Sharma; Marjana Yeasmin; Srikanta Samanta; Ray Correll; Ravi Naidu (Environmental Science and Pollution Research, 2020)

The impact of tourism and natural resources on the ecological footprint: a case study of ASEAN countries - Nattapan Kongbuamai; Quocviet Bui; Hafiz Muhammad Abaid Ullah Yousaf; Yun Liu (Environmental Science and Pollution Research, 2020)

Analysis of asymmetries in the nexus among clean energy and environmental quality in Pakistan - Ahmed Usman; Sana Ullah; Ilhan Ozturk; Muhammad Zubair Chishti; Syeda Maria Zafar (Environmental Science and Pollution Research, 2020)

Modeling food growers’ perceptions and behavior towards environmental changes and its induced risks: evidence from Pakistan - Nasir Abbas Khan; Qijie Gao; Muhammad Amjed Iqbal; Muhammad Abid (Environmental Science and Pollution Research, 2020)

Linking environment, malaria, and agricultural returns: a labor time use analysis at different stages of production using 3SLS - Sobia Rose; Muhammad Faisal Ali; Khuda Bakhsh; Muhammad Ashfaq; Sarfraz Hassan (Environmental Science and Pollution Research, 2020)

Water resources and tourism development in South Asia: an application of dynamic common correlated effect (DCCE) model - Muhammad Saeed Meo; Saeed Ahmad Sabir; Hira Arain; Raima Nazar (Environmental Science and Pollution Research, 2020)

Renewable energy, urbanization, and ecological footprint linkage in CIVETS - Solomon Nathaniel; Ozoemena Nwodo; Gagan Sharma; Muhammad Shah (Environmental Science and Pollution Research, 2020)

The impact of temperature, rainfall, and health worker density index on road traffic fatalities in Pakistan - Qamar Ali; Muhammad Rizwan Yaseen; Muhammad Tariq Iqbal Khan (Environmental Science and Pollution Research, 2020)

Optimal oil stockpiling, peak oil, and general equilibrium: case study of South Asia (oil importers) and Middle East (oil supplier) - Muhammad Khalid Anser; Qaiser Abbas; Imran Sharif Chaudhry; Arman Khan (Environmental Science and Pollution Research, 2020)

Multi-functionalized nanocarriers targeting bacterial reservoirs to overcome challenges of multi drug-resistance - Maria Hassan Kiani; Muhammad Imran; Abida Raza; Gul Shahnaz (DARU Journal of Pharmaceutical Sciences, 2020)

Geochemical segregation of early Permian, Paleocene and Eocene sediments of Potwar Basin, Pakistan: I Geophysical and isotopic analysis for source and depositional environment - Muhammad Irfan Jalees; Fazeelat Tahira (Carbonates and Evaporites, 2020)

Sedimentology of Shahejie Formation, Bohai Bay Basin: a case study of Es1 member in Nanpu Sag - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Faisal Rehman; Kamran Shehzad; Muhammad Fahad Ullah; Ghulam Mustafa (Carbonates and Evaporites, 2020)

Achromobacter sp. FB-14 harboring ACC deaminase activity augmented rice growth by upregulating the expression of stress-responsive CIPK genes under salinity stress - Muhammad Shahid; Asad Ali Shah; Farwa Basit; Muhammad Noman; Muhammad Zubair; Temoor Ahmed; Tahir Naqqash; Irfan Manzoor; Awais Maqsood (Brazilian Journal of Microbiology, 2020)

Revisiting the cytotoxicity of quantum dots: an in-depth overview - Sohrab Nikazar; Vishnu Sankar Sivasankarapillai; Abbas Rahdar; Salim Gasmi; P S Anumol; Muhammad Salman Shanavas (Biophysical Reviews, 2020)

Nano-particles of Trace Minerals in Poultry Nutrition: Potential Applications and Future Prospects - Safdar Hassan; Faiz-ul Hassan; Muhammad Saif-ur Rehman (Biological Trace Element Research, 2020)

Yucasin and cinnamic acid inhibit IAA and flavonoids biosynthesis minimizing interaction between maize and endophyte Aspergillus nomius - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Abdul Tawab; Naeem Khan (Symbiosis, 2020)

Impact of Agrobacterium-infiltration and transient overexpression of BroMYB28 on glucoraphanin biosynthesis in broccoli leaves - Young-Cheon Kim; Ahra Cha; Muhammad Hussain; Kwanuk Lee; Sanghyeob Lee (Plant Biotechnology Reports, 2020)

Joint Effect of East Asia-Pacific and Eurasian Teleconnections on the Summer Precipitation in North Asia - Po Hu; Guolin Feng; Muhammad Mubashar Dogar; Jianbo Cheng; Zhiqiang Gong (Journal of Meteorological Research, 2020)

Facies control on selective dolomitization and its impact on reservoir heterogeneities in the Samana Suk Formation (middle Jurassic), Southern Hazara Basin (NW Himalaya, Pakistan): an outcrop analogue - Mumtaz M. Shah; Hamad U. Rahim; Aosaf Hassan; Muhammad R. Mustafa; Imran Ahmad (Geosciences Journal, 2020)

Thermogravimetric Kinetics of Catalytic and Non-Catalytic Pyrolytic Conversion of Palm Kernel Shell with Acid-Treated Coal Bottom Ash - David Onoja Patrick; Suzana Yusup; Noridah B. Osman; Haslinda Zabiri; Yoshimitsu Uemura; Muhammad Shahbaz (BioEnergy Research, 2020)

RLP, a bacteriophage of the family Podoviridae, rescues mice from bacteremia caused by multi-drug-resistant Pseudomonas aeruginosa - Iqbal Ahmad Alvi; Muhammad Asif; Rabia Tabassum; Rehan Aslam; Zaigham Abbas; Shafiq ur Rehman (Archives of Virology, 2020)

Enhancing phosphorus availability in two variable charge soils by the amendments of crop straw biochars - Muhammad Aqeel Kamran; Jackson Nkoh Nkoh; Ren-Kou Xu; Jun Jiang (Arabian Journal of Geosciences, 2020)

Biofloc-based co-culture systems of Nile tilapia (Oreochromis niloticus) and redclaw crayfish (Cherax quadricarinatus) with different carbon–nitrogen ratios - Muhammad H. Azhar; Suciyono Suciyono; Darmawan S. Budi; Mohammad F. Ulkhaq; Mai Anugrahwati; Julie Ekasari (Aquaculture International, 2020)

Towards a Web GIS-based approach for mapping a dengue outbreak - Muhammad A. Butt; A. Khalid; A. Ali; S. A. Mahmood; J. Sami; J. Qureshi; K. Waheed; A. Khalid (Applied Geomatics, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

In-vitro evaluation of antimicrobial, antioxidant, alpha-amylase inhibition and cytotoxicity properties of Cannabis sativa - Syed Bilal Shah; Lubna Sartaj; Shahid Hussain; Nabi Ullah; Muhammad Idrees; Asma Shaheen; Muhammad Sufyan Javed; Muhammad Kashif Aslam (Advances in Traditional Medicine, 2020)

Chemical profile and biological activities of Sonneratia apetala (Buch.-Ham.) - Muhammad Torequl Islam (Advances in Traditional Medicine, 2020)

Extracting mass concentration time series features for classification of indoor and outdoor atmospheric particulates - Lal Hussain; Wajid Aziz; Sharjil Saeed; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Seong-O Shim; Sania Aftar; Jawad-ur-Rehman Pirzada (Acta Geophysica, 2020)

Himalayan wolf distribution and admixture based on multiple genetic markers - Geraldine Werhahn; Yanjiang Liu; Yao Meng; Chen Cheng; Zhi Lu; Luciano Atzeni; Zhixiong Deng; Shi Kun; Xinning Shao; Qi Lu; Jyoti Joshi; Adarsh Man Sherchan; et al. (Journal of Biogeography, 2020)
Aim We explore the phylogeography of Himalayan wolves using multiple genetic markers applied on a landscape‐scale dataset and relate our findings to the biogeographic history of the region. Location Himalayas of Nepal, the Tibetan Plateau of China and mountain ranges of Central Asia. Taxon Himalayan wolf (also called the Tibetan wolf), Canis lupus chanco . Methods We present a large‐scale, non‐invasive study of Himalayan wolves from across their estimated range. We analysed 280 wolf scat samples from western China, Kyrgyzstan and Tajikistan at two mtDNA loci, 17 microsatellite loci, four non‐synonymous SNPs in three nuclear genes related to the hypoxia pathway, and ZF genes on both sex chromosomes. Results Our results corroborate previous studies showing that the Himalayan wolf forms a distinct lineage adapted to high altitudes in excess of 4,000 m elevation. We found a correlation between hypoxia adaptation and the divergent Himalayan wolf mtDNA haplotype found across the Tibetan Plateau of Qinghai, the Tibetan Autonomous Region and the Nepalese Himalayas. We identified a region of admixture between Himalayan and grey wolves at the boundary of their distributions, where the Tibetan Plateau elevation gradually drops. Main Conclusion Based on multiple genetic markers, the Himalayan wolf forms a reciprocally monophyletic lineage with a unique adaptation to high altitude. We propose that the divergence of the lineage is related to past uplift of the region, and that the lineage maintains its high‐altitude niche, in part, by means of its genetic adaptation to hypoxia. We conclude that the Himalayan wolf merits taxonomic recognition and designation as an evolutionary significant unit (ESU).

RETRACTED ARTICLE: Poloxamer-407-Co-Poly (2-Acrylamido-2-Methylpropane Sulfonic Acid) Cross-linked Nanogels for Solubility Enhancement of Olanzapine: Synthesis, Characterization, and Toxicity Evaluation - Kifayat Ullah Khan; Naveed Akhtar; Muhammad Usman Minhas (AAPS PharmSciTech, 2020)

Morphological and biochemical changes in maize under drought and salinity stresses in a semi-arid environment - Leila Romdhane; Leila Radhouane; Muhammad Farooq; Cristian Dal Cortivo; Anna Panozzo; Teofilo Vamerali (Plant Biosystems, 2020)

New citrinin derivatives from the deep-sea-derived fungus Cladosporium sp. SCSIO z015 - Muhammad Amin; Xiao-Yong Zhang; Xin-Ya Xu; Shu-Hua Qi (Natural Product Research, 2020)

Comparative analysis of oil composition and antibacterial activity of aerial parts of Terminalia arjuna (Roxb.) - Shehar Bano; Azeem Intisar; Mahd Rauf; Abdul Ghaffar; Farhat Yasmeen; Waheed-Uz- Zaman; Uzma Intisar; Gulnaz Kausar; Nadeem Muhammad; Aqsa Aamir (Natural Product Research, 2020)

Transferability of object-based image analysis approaches for landslide detection in the Himalaya Mountains of northern Pakistan - Alam Sher Bacha; Harald Van Der Werff; Muhammad Shafique; Hawas Khan (International Journal of Remote Sensing, 2020)

Analysis of the application of an advanced classifier algorithm to ultra-high resolution unmanned aerial aircraft imagery – a neural network approach - Fatwa Ramdani; Muhammad Tanzil Furqon; Budi Darma Setiawan; Alfi Nur Rusydi (International Journal of Remote Sensing, 2020)

Synergistic Long-Term Temperate Climate Nitrogen Removal Performance in Open Raceway Pond and Horizontal Subsurface Flow Constructed Wetland Operated Under Different Regimes - Raana Fahim; Xiwu Lu; Ghulam Ahmad Jilani; Hasan Mahdi; Muhammad Aslam (Water, Air, & Soil Pollution, 2020)

Enteric methane emissions of grazing short-horn zebu weaner bulls vary with estimation method and level of crude protein supplementation - Muhammad Kiggundu; Ziwena Nantongo; Siraj Ismail Kayondo; Swidiq Mugerwa (Tropical Animal Health and Production, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

Appraisal of wheat genomics for gene discovery and breeding applications: a special emphasis on advances in Asia - Awais Rasheed; Shigeo Takumi; Muhammad Adeel Hassan; Muhammad Imtiaz; Mohsin Ali; Alex I. Morgunov; Tariq Mahmood; Zhonghu He (Theoretical and Applied Genetics, 2020)

Post-translational regulation of plasma membrane H+-ATPase is involved in the release of biological nitrification inhibitors from sorghum roots - Muhammad Rahil Afzal; Maoxing Zhang; Heyu Jin; Genmei Wang; Mingchao Zhang; Ming Ding; Sajjad Raza; Jun Hu; Houqing Zeng; Xiang Gao; Guntur Venkata Subbarao; Yiyong Zhu (Plant and Soil, 2020)

Genome-wide association study identifies various loci underlying agronomic and morphological traits in diversified potato panel - Muhammad Abu Bakar Zia; Ufuk Demirel; Muhammad Azhar Nadeem; Mehmet Emin Çaliskan (Physiology and Molecular Biology of Plants, 2020)

Recent developments and comparison of transformation strategies for organic halides to aldehydes and ketones - Muhammad Faisal; Aamer Saeed; Danish Shahzad; Parsa Dar; Fayaz Ali Larik (Molecular Diversity, 2020)

Selective cyclooxygenase-2 inhibitors: A review of recent chemical scaffolds with promising anti-inflammatory and COX-2 inhibitory activities - Noor-ul-Amin Mohsin; Muhammad Irfan (Medicinal Chemistry Research, 2020)

First report of leaf spots in Caryota mitis L. caused by Alternaria alstroemeriae in Pakistan - Imran Ul haq; Siddra Ijaz; Anjum Faraz; Muhammad Kaleem Sarwar; Muhammad Zunair Latif; Nabeeha Aslam Khan (Journal of Plant Pathology, 2020)

Growth and physiological responses of selected pakchoi varieties to Plasmodiophora brassicae infection - Hongfang Zhu; Xiaofeng Li; Muhammad Khalid; Dandan Xi; Zhaohui Zhang; Yuying Zhu (Journal of Plant Pathology, 2020)

First report of cucurbit aphid borne yellows virus (CABYV) infecting melon in Pakistan - Muhammad Ahsan; Muhammad Ashfaq; Tariq Mukhtar; Nadeem Akhtar Abbasi; Zohaib Asad (Journal of Plant Pathology, 2020)

Molecular epidemiology of Shigella flexneri isolated from pediatrics in a diarrhea-endemic area of Khyber Pakhtunkhwa, Pakistan - Iqbal Nisa; Muhammad Qasim; Arnold Driessen; Jeroen Nijland; Fazli Bari; Mohammad Haroon; Hazir Rahman; Nusrat Yasin; Taj Ali Khan; Mubbashir Hussain; Waheed Ullah (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Patterns of inheritance for cotyledon resistance against Sclerotinia sclerotiorum in Brassica napus - Muhammad Azam Khan; Wallace Cowling; Surinder Singh Banga; Ming Pei You; Vikrant Tyagi; Baudh Bharti; Martin J. Barbetti (Euphytica, 2020)

Asymmetric effects of energy efficiency and renewable energy on carbon emissions of BRICS economies: evidence from nonlinear panel autoregressive distributed lag model - Rabia Akram; Muhammad Tariq Majeed; Zeeshan Fareed; Fahad Khalid; Chengang Ye (Environmental Science and Pollution Research, 2020)

Hazards of nitrogen fertilizers and ways to reduce nitrate accumulation in crop plants - Moddassir Ahmed; Muhammad Rauf; Muhammad Akhtar; Zahid Mukhtar; Nasir Ahmad Saeed (Environmental Science and Pollution Research, 2020)

Urbanization and energy consumption effects on carbon dioxide emissions: evidence from Asian-8 countries using panel data analysis - Muhammad Ali Abbasi; Shabana Parveen; Saleem Khan; Muhammad Abdul Kamal (Environmental Science and Pollution Research, 2020)

Impact of selenium, zinc and their interaction on key enzymes, grain yield, selenium, zinc concentrations, and seedling vigor of biofortified rice - Hla Hla Ei; Tengda Zheng; Muhammad Umer Farooq; Rui Zeng; Yang Su; Yujie Zhang; Yuanke Liang; Zhichen Tang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2020)

An unintended challenge of microplastic pollution in the urban surface water system of Lahore, Pakistan - Muhammad Irfan; Abdul Qadir; Mehvish Mumtaz; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2020)

Energy consumption and financial development indicators nexuses in Asian economies: a dynamic seemingly unrelated regression approach - Li Yang; Peng Hui; Rizwana Yasmeen; Sana Ullah; Muhammad Hafeez (Environmental Science and Pollution Research, 2020)

A study on the seasonal transfer of two metals from pasture to animals: health risk assessment - Zafar Iqbal Khan; Mubeen Akhtar; Kafeel Ahmad; Asma Ashfaq; Muhammad Nadeem; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik (Environmental Science and Pollution Research, 2020)

Environmental degradation and population health outcomes: a global panel data analysis - Muhammad Tariq Majeed; Ilhan Ozturk (Environmental Science and Pollution Research, 2020)

Flood hazards and factors influencing household flood perception and mitigation strategies in Pakistan - Dilshad Ahmad; Muhammad Afzal (Environmental Science and Pollution Research, 2020)

Relationship between inward FDI and environmental degradation for Pakistan: an exploration of pollution haven hypothesis through ARDL approach - Abdul M. Nadeem; Tariq Ali; Muhammad T. I. Khan; Zhengquan Guo (Environmental Science and Pollution Research, 2020)

Sodium arsenite toxicity on hematology indices and reproductive parameters in Teddy goat bucks and their amelioration with vitamin C - Muhammad Zubair; Maqbool Ahmad; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Mushtaq Ahmad; Christopher Joseph Martyniuk; Qudrat Ullah; Saqib Umar (Environmental Science and Pollution Research, 2020)

Dose and duration-dependent toxicological evaluation of lead acetate in chicks - Saeeda Hussain; Shaukat Ali; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Hafiz Muhammad Tahir; Mazhar Ulhaq; Muhammad Adeeb Khan; Muhammad Tariq Zahid (Environmental Science and Pollution Research, 2020)

Plastic driven pollution in Pakistan: the first evidence of environmental exposure to microplastic in sediments and water of Rawal Lake - Tahira Irfan; Sofia Khalid; Mahwish Taneez; Muhammad Zaffar Hashmi (Environmental Science and Pollution Research, 2020)

Nephroprotective effects of curcumin loaded chitosan nanoparticles in cypermethrin induced renal toxicity in rabbits - Maira Anwar; Faqir Muhammad; Bushra Akhtar; Sajjad ur Rehman; Muhammad Kashif Saleemi (Environmental Science and Pollution Research, 2020)

Renewable energy, urbanization, and ecological footprint in the Middle East and North Africa region - Solomon Nathaniel; Ogochukwu Anyanwu; Muhammad Shah (Environmental Science and Pollution Research, 2020)

A forecasting model approach of sustainable electricity management by developing adaptive neuro-fuzzy inference system - Aamir Nawaz Khan; Muhammad Asif Nadeem; Muhammad Shahid Hussain; Muhammad Aslam; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2020)

Assessment of denitrification potential for coastal and inland sites using groundwater and soil analysis: the multivariate approach - Muntaka Dahiru; Nor Kartini Abu Bakar; Ismail Yus off; Kah Hin Low; Muhammad N. Mohd (Environmental Monitoring and Assessment, 2020)

Type 1 Fimbriae and Motility Play a Pivotal Role During Interactions of Salmonella typhimurium with Acanthamoeba castellanii (T4 Genotype) - Talha Mannan; Muhammad Wasim Rafique; Muhammad Haroon Bhatti; Abdul Matin; Irfan Ahmad (Current Microbiology, 2020)

Impact of urbanization, economic growth, and population size on residential carbon emissions in the SAARC countries - Muhammad Khalid Anser; Majed Alharthi; Babar Aziz; Sarah Wasim (Clean Technologies and Environmental Policy, 2020)

Effect of Organic Manure and Mineral Fertilizers on Bioaccumulation and Translocation of Trace Metals in Maize - Kinza Wajid; Kafeel Ahmad; Zafar Iqbal Khan; Muhammad Nadeem; Humayun Bashir; Fu Chen; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2020)

Helicobacter pylori infection induced genome instability and gastric cancer - Xiangyu Liu; Muhammad Irfan; Xingzhi Xu; Chi-Yen Tay; Barry J. Marshall (Genome Instability & Disease, 2020)
Genome stability and integrity are constantly challenged by exogenous insults such as bacterial infections. When genome stability is perturbed, oncogenic transformation can ensue. Helicobacter pylori ( H. pylori ) infection is a driving factor of gastric cancer, which is the third leading cause of cancer-related mortality worldwide. Mechanistically, H. pylori infection drives inflammation and directly or indirectly induces DNA damage such as oxidative damage and double-strand breaks (DSBs) in host cells. In addition, the resulting genetic and/or epigenetic perturbations alter the choice of DNA repair pathways. These changes result in imprecise DNA repair, genomic instability as well as chromosomal aberrations that eventually lead to gastric carcinogenesis. In this review, we summarize the mechanisms how H. pylori infection cause DNA damage and alter the DNA damage response pathways in host cells. We highlight the relationship between H. pylori infection and genomic instability that can lead to gastric cancer and propose a potential strategy to interrupt gastric carcinogenesis.

Dissecting microbial community structure in sewage treatment plant for pathogens’ detection using metagenomic sequencing technology - Abdulmoseen Segun Giwa; Nasir Ali; Muhammad Ammar Athar; Kaijun Wang (Archives of Microbiology, 2020)

Effect of biochars, biogenic, and inorganic amendments on dissolution and kinetic release of phytoavailable silicon in texturally different soils under submerged conditions - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Ashar Ayub; Tariq Aziz; Muhammad Saqib; Ghulam Murtaza (Arabian Journal of Geosciences, 2020)

Failure analysis of rock cut slope formed by layered blocks at Fort Munro, Pakistan - Zulkifl Ahmed; Shuhong Wang; Muhammad Zaffar Hashmi; Chengjin Zhu; Zhang Zishan; Alipujiang Jierula; Wang Pengyu (Arabian Journal of Geosciences, 2020)

Effect of biochar and phosphate solubilizing bacteria on growth and phosphorus uptake by maize in an Aridisol - Muhammad Arif Ali; Muhammad Mustansar Ajaz; Muhammad Rizwan; Muhammad Farooq Qayyum; Muhammad Arshad; Sajjad Hussain; Niaz Ahmad; Muhammad Amjad Qureshi (Arabian Journal of Geosciences, 2020)

Hankyongella ginsenosidimutans gen. nov., sp. nov., isolated from mineral water with ginsenoside coverting activity - Muhammad Zubair Siddiqi; Wan-Taek Im (Antonie van Leeuwenhoek, 2020)

Evaluating antimicrobial resistance in the global shrimp industry - Kelly Thornber; David Verner‐Jeffreys; Steve Hinchliffe; Muhammad Meezanur Rahman; David Bass; Charles R. Tyler (Reviews in Aquaculture, 2020)
Antimicrobial resistance ( AMR ) is a growing threat to global public health, and the overuse of antibiotics in animals has been identified as a major risk factor. With high levels of international trade and direct connectivity to the aquatic environment, shrimp aquaculture may play a role in global AMR dissemination. The vast majority of shrimp production occurs in low‐ and middle‐income countries, where antibiotic quality and usage is widely unregulated, and where the integration of aquaculture with family livelihoods offers many opportunities for human, animal and environmental bacteria to come into close contact. Furthermore, in shrimp growing areas, untreated waste is often directly eliminated into local water sources. These risks are very different to many other major internationally‐traded aquaculture commodities, such as salmon, which is produced in higher income countries where there are greater levels of regulation and well‐established management practices. Assessing the true scale of the risk of AMR dissemination in the shrimp industry is a considerable challenge, not least because obtaining reliable data on antibiotic usage is very difficult. Combating the risks associated with AMR dissemination is also challenging due to the increasing trend towards intensification and its associated disease burden, and because many farmers currently have no alternatives to antibiotics for preventing crop failure. In this review, we critically assess the potential risks the shrimp industry poses to AMR dissemination. We also discuss some of the possible risk mitigation strategies that could be considered by the shrimp industry as it strives for a more sustainable future in production.

The Economic Value of Shark and Ray Tourism in Indonesia and Its Role in Delivering Conservation Outcomes - Putu Liza Kusuma Mustika; Muhammad Ichsan; Hollie Booth (Frontiers in Marine Science, 2020)

Aluminium oxide nanoparticles inhibit EPS production, adhesion and biofilm formation by multidrug resistant Acinetobacter baumannii - Saima Muzammil; Mohsin Khurshid; Iqra Nawaz; Muhammad Hussnain Siddique; Muhammad Zubair; Muhammad Atif Nisar; Muhammad Imran; Sumreen Hayat (Biofouling, 2020)

Trunk Posture Exposure Patterns among Prairie Ranch and Grain Farmers - Muhammad Idrees Khan; Brenna Bath; Aaron Kociolek; Xiaoke Zeng; Niels Koehncke; Catherine Trask (Journal of Agromedicine, 2020)

Accuracy of genotype MTBDR plus line probe assay in patients with tuberculous pleural effusion: comparison with clinical and culture based diagnosis - Muhammad Irfan; Farah Idrees; Kauser Jabeen; Ali Bin Sarwar Zubairi; Sehrish Butt; Rumina Hasan (Infectious Diseases, 2020)

Potential perspectives of biodegradable plastics for food packaging application-review of properties and recent developments - Muhammad Imran Din; Tayabba Ghaffar; Jawayria Najeeb; Zaib Hussain; Rida Khalid; Hafsa Zahid (Food Additives & Contaminants: Part A, 2020)

Detection of porcine pepsin in model cheese using polyclonal antibody-based ELISA - Raja Mohd Hafidz Raja Nhari; Azyan Nafisah Muhammad Zailani; Nur Fadhilah Khairil Mokhtar; Irwan Hanish (Food Additives & Contaminants: Part A, 2020)

Mechanism and Degradation Pathways of Bisphenol A in Aqueous Solution by Strong Ionization Discharge - Tingting Geng; Chengwu Yi; Rongjie Yi; Liu Yang; Muhammad Imran Nawaz (Water, Air, & Soil Pollution, 2020)

Droughts’ projections in homogeneous climatic regions using Standardized Precipitation Index in Pakistan - Hamd Ullah; Muhammad Akbar; Firdos Khan (Theoretical and Applied Climatology, 2020)

Characterization of regional hydrological drought using improved precipitation records under multi-auxiliary information - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Marco Andreas Grzegorczyk; Ibrahim M. Almanjahie; Amna Nazeer; Ishfaq Ahmad (Theoretical and Applied Climatology, 2020)

Risk assessment of extreme air pollution based on partial duration series: IDF approach - Nurulkamal Masseran; Muhammad Aslam Mohd Safari (Stochastic Environmental Research and Risk Assessment, 2020)

NaCl improved Cd tolerance of the euhalophyte Suaeda glauca but not the recretohalophyte Limonium aureum - Songlin Zhang; Xilu Ni; Muhammad Arif; Jie Zheng; Annastacia Stubbs; Changxiao Li (Plant and Soil, 2020)

Functional characteristics of a calcium-dependent protein kinase (MaCDPK1) enduring stress tolerance from Morus atropurpurea Roxb. - Zhenming Cao; Qianhua He; Pengwei Wang; Jiming Yan; Main Muhammad Awais; Zicheng Liu; Huichao Yan; Jingchen Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Spicing up gastrointestinal health with dietary essential oils - Mahwish Tanveer; Charles Wagner; Muhammad Ikram ul Haq; Nilton C. Ribeiro; Thriumurugan Rathinasabapathy; Masood Sadiq Butt; Aamir Shehzad; Slavko Komarnytsky (Phytochemistry Reviews, 2020)

Synthesis of Ligand Functionalized ErbB-3 Targeted Novel DNA Nano-Threads Loaded with the Low Dose of Doxorubicin for Efficient In Vitro Evaluation of the Resistant Anti-Cancer Activity - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Anam Ahsan; Mehreen Jabeen; Muhammad Asim Farooq; Reyaj Mikrani; Muhammad Abbas; Muhammad Naveed; Said Abasse Kassim; Faisal Raza; Afzal Ahmed Dar; Muhammad Tayyab Ansari (Pharmaceutical Research, 2020)

Synthesis and characterization of newly synthesized neodymium zirconate zinc sulfide nanocomposite and its effect on selected aspects of albino mice behavior - Tafheem Khosa; Aysha Faiz; Asia Hayder; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Assessment of sugar and sugar accumulation-related gene expression profiles reveal new insight into the formation of low sugar accumulation trait in a sweet orange (Citrus sinensis) bud mutant - Syed Bilal Hussain; Ling-Xia Guo; Cai-Yun Shi; Muhammad Abbas Khan; Ying-Xing Bai; Wei Du; Yong-Zhong Liu (Molecular Biology Reports, 2020)

Resistance to Chilo infuscatellus (Lepidoptera: Pyraloidea) in transgenic lines of sugarcane expressing Bacillus thuringiensis derived Vip3A protein - Saman Riaz; Idrees Ahmad Nasir; Muhammad Umar Bhatti; Olawale Samuel Adeyinka; Nida Toufiq; Iqra Yousaf; Bushra Tabassum (Molecular Biology Reports, 2020)

Role of serum Metadherin mRNA expression in the diagnosis and prediction of survival in patients with colorectal cancer - Muhammad Tarek Abdel Ghafar; Fatma Gharib; Sherief Abdel-Salam; Reham Abdelkader Elkhouly; Ahmed Elshora; Khaled H. Shalaby; Dina El-Guindy; Mohamed Ali El-Rashidy; Nema A. Soliman; Mira Maged Abu-elenin; Alzahraa A. Allam (Molecular Biology Reports, 2020)

In vitro and in silico evaluations of new aryloxy-1,4-naphthoquinones as anti-Trypanosoma cruzi agents - Alejandra González; Nohemí Becerra; Muhammad Kashif; Mercedes González; Hugo Cerecetto; Elena Aguilera; Benjamín Nogueda-Torres; Karla F. Chacón-Vargas; J. José Zarate-Ramos; Uziel Castillo-Velázquez; Cristian O. Salas; Gildardo Rivera; et al. (Medicinal Chemistry Research, 2020)

Impact of jet stream and associated mechanisms on winter precipitation in Pakistan - Fayyaz Ahmed; Shahzada Adnan; Muhammad Latif (Meteorology and Atmospheric Physics, 2020)

Mitogenomic Perspectives on the Adaptation to Extreme Alkaline Environment of Amur ide (Leuciscus waleckii) - Chuanju Dong; Xiaodi Duan; Laghari Muhammad Younis; Meng Zhang; Xiao Ma; Baohua Chen; Xuejun Li; Peng Xu (Marine Biotechnology, 2020)

Soil nutrients and heavy metal availability under long-term combined application of swine manure and synthetic fertilizers in acidic paddy soil - Muhammad Qaswar; Liu Yiren; Huang Jing; Liu Kaillou; Muhammad Mudasir; Lv Zhenzhen; Hou Hongqian; Lan Xianjin; Ji Jianhua; Waqas Ahmed; Li Dongchu; Zhang Huimin (Journal of Soils and Sediments, 2020)

Identification of stripe rust resistant genes and their validation in seedling and adult plant glass house tests - Shamaila Tahir; Iram Zia; Iqra Dilshad; Muhammad Fayyaz; Nighat Noureen; Sumaira Farrakh (Genetic Resources and Crop Evolution, 2020)

Shigella flexneri: an emerging pathogen - Iqbal Nisa; Muhammad Qasim; Nusrat Yasin; Rafi Ullah; Anwar Ali (Folia Microbiologica, 2020)

Gene cloning and characterization of Tk1281, a flap endonuclease 1 from Thermococcus kodakarensis - Hira Muzzamal; Qurat ul Ain; Muhammad Sulaiman Saeed; Naeem Rashid (Folia Microbiologica, 2020)

Composition and source apportionment of saccharides in aerosol particles from an agro-industrial zone in the Indo-Gangetic Plain - Muhammad Usman Alvi; Magdalena Kistler; Imran Shahid; Khan Alam; Farrukh Chishtie; Tariq Mahmud; Anne Kasper-Giebl (Environmental Science and Pollution Research, 2020)

On the asymmetric effects of premature deindustrialization on CO2 emissions: evidence from Pakistan - Sana Ullah; Ilhan Ozturk; Ahmed Usman; Muhammad Tariq Majeed; Parveen Akhtar (Environmental Science and Pollution Research, 2020)

Selective and simultaneous detection of cadmium, lead and copper by tapioca-derived carbon dot–modified electrode - Musa Yahaya Pudza; Zurina Zainal Abidin; Suraya Abdul-Rashid; Faizah Md Yasin; Ahmad Shukri Muhammad Noor; Jaafar Abdullah (Environmental Science and Pollution Research, 2020)

Comparative adsorption capabilities of rubbish tissue paper–derived carbon-doped MgO and CaCO3 for EBT and U(VI), studied by batch, spectroscopy and DFT calculations - Ayub Khan; Dongli Wei; Fazli Khuda; Ran Ma; Muhammad Ismail; Yuejie Ai (Environmental Science and Pollution Research, 2020)

Mineral carbonation of sedimentary mine waste for carbon sequestration and potential reutilization as cementitious material - Faradiella Mohd Kusin; Sharifah Nur Munirah Syed Hasan; Muhammad Afiq Hassim; Verma Loretta M. Molahid (Environmental Science and Pollution Research, 2020)

Industrial pollution and human health: evidence from middle-income countries - Hafiz Muhammad Abubakar Siddique; Adiqa K. Kiani (Environmental Science and Pollution Research, 2020)

Impact of financial development on CO2 emissions: A comparative analysis of developing countries (D8) and developed countries (G8) - Hafiz Muhammad Shoaib; Muhammad Zahid Rafique; Abdul Majeed Nadeem; Shaoan Huang (Environmental Science and Pollution Research, 2020)

Oxidative stress risk assessment through heavy metal and arsenic exposure in terrestrial and aquatic bird species of Pakistan - Shamsa Kanwal; Naeem Akhtar Abbasi; Muhammad Jamshed Iqbal Chaudhry; Sajid Rashid Ahmad; Riffat Naseem Malik (Environmental Science and Pollution Research, 2020)

Short stay, long impact: ecological footprints of sojourners - Qing Ye; Muhammad Azfar Anwar; Rongting Zhou; Fahad Asmi; Intikhab Ahmad (Environmental Science and Pollution Research, 2020)

Ammonia inhalation-induced inflammation and structural impairment in the bursa of fabricius and thymus of broilers through NF-κB signaling pathway - Syed Waqas Ali Shah; Muhammad Ishfaq; Muhammad Nasrullah; Abdul Qayum; Muhammad Usman Akhtar; Hyeonsoo Jo; Muhammad Hussain; Xiaohua Teng (Environmental Science and Pollution Research, 2020)

Association of intronic polymorphisms (rs1549339, rs13402242) and mRNA expression variations in PSMD1 gene in arsenic-exposed workers - Saqiba Ahmad; Bushra Arif; Zertashia Akram; Malik Waqar Ahmed; Asad Ullah Khan; Muhammad Zahid Hussain; Faisal Rahman; Mahmood Akhtar Kayani; Ishrat Mahjabeen (Environmental Science and Pollution Research, 2020)

Ameliorative effect of naringin against thiram-induced tibial dyschondroplasia in broiler chicken - Xiong Jiang; Aoyun Li; Yaping Wang; Mudassar Iqbal; Muhammad Waqas; Hao Yang; Zhixing Li; Khalid Mehmood; Hammad Qamar; Jiakui Li (Environmental Science and Pollution Research, 2020)

Health risks of heavy metal exposure and microbial contamination through consumption of vegetables irrigated with treated wastewater at Dubai, UAE - Muhammad Iftikhar Hussain; Asad Sarwar Qureshi (Environmental Science and Pollution Research, 2020)

The financial development-environmental degradation nexus in the United Arab Emirates: the importance of growth, globalization and structural breaks - Muhammad Shahbaz; Ilham Haouas; Kazi Sohag; Ilhan Ozturk (Environmental Science and Pollution Research, 2020)

Evaluating the combination of Metarhizium anisopliae and an enhanced form of diatomaceous earth (Grain-Guard) for the environmentally friendly control of stored grain pests - Nadia Saeed; Waqas Wakil; Muhammad Farooq; Muhammad Shakeel; Muhammad Shahid Arain; Qaiser Shakeel (Environmental Monitoring and Assessment, 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

Competitiveness, governance and globalization: What matters for poverty alleviation? - Muhammad Shahid Hassan; Samra Bukhari; Noman Arshed (Environment, Development and Sustainability, 2020)

Bioavailability and Speciation of Heavy Metals in Polluted Soil as Alleviated by Different Types of Biochars - Weijie Xu; Shuzhen Hou; Yaqian Li; Muhammad Aman Khan; Wenxuan Luo; Zhenhua Chen; Yongqing Li; Xiangdong Wu; Zhengqian Ye; Dan Liu (Bulletin of Environmental Contamination and Toxicology, 2020)

Litter decay in rangeland sites with varying history of human disturbance: a study with Hazargangi Chiltan mountain - Imran Khan; Shamim Gul; Sarfraz Ahmad; Gul Bano Rehman; Agha Waqar Yunus; Iram Gul; Imran Ali; Ali Akbar; Muhammad Islam (Journal of Mountain Science, 2020)

Expression Profiles and Biochemical Analysis of Chemosensory Protein 3 from Nilaparvata lugens (Hemiptera: Delphacidae) - Muhammad Irfan Waris; Aneela Younas; Asif Ameen; Fatima Rasool; Man-Qun Wang (Journal of Chemical Ecology, 2020)

Evaluation of the bioenergy potential of invasive Pennisetum purpureum through pyrolysis and thermogravimetric analysis - Md Sumon Reza; Shafi Noor Islam; Shammya Afroze; Muhammad S. Abu Bakar; Rahayu S. Sukri; Saidur Rahman; Abul K. Azad (Energy, Ecology and Environment, 2020)

Transcriptomic analysis of root specific drought mediated response of G. arboreum and G. hirsutum - Zarnab Ahmad; Sajjad Sadique; Muhammad B. Sarwar; Bushra Rashid; Sameera Hassan; Sultana Rasheed; Khurram Bashir; Motoaki Seki; Tayyab Husnain (Biologia, 2020)

Evaluation of host–pathogen interactions for selection of entomopathogenic fungal isolates against Oligonychus afrasiaticus (McGregor) - Abid Hussain; Muhammad Rizwan-ul-Haq; Ahmed Mohammed AlJabr; Hassan Al-Ayedh (BioControl, 2020)

Blood-based gene expression profile of oxidative stress and antioxidant genes for identifying surrogate markers of liver tissue injury in chronic hepatitis C patients - Muhammad Shahid; Muhammad Idrees; Azeem Mehmood Butt; Syed Mohsin Raza; Iram Amin; Afza Rasul; Samia Afzal (Archives of Virology, 2020)

Implication of Physiological and Biochemical Variables of Prognostic Importance in Lead Exposed Subjects - Arif Malik; Muhammad Abdul Basit Ashraf; Muhammad Waqas Khan; Ayesha Zahid; Hassan Shafique; Sulayman Waquar; Siew Hua Gan; Muhammad Ashraf (Archives of Environmental Contamination and Toxicology, 2020)

Geotechnical properties of Lower Eocene limestones, Sinn El-Kaddab Plateau, southwest of Aswan, Egypt - Kamal Abou Elmagd; Ashraf Emam; Muhammad Hazem (Arabian Journal of Geosciences, 2020)

Numerical simulation of the morphological effect of rock joints in the processes of concentrating elastic strain energy: a direct shear study - Xiaojun Feng; Qiming Zhang; Xiaofei Liu; Muhammad Ali (Arabian Journal of Geosciences, 2020)

GIS-based assessment of aridity over Punjab Province, Pakistan, by using climatic indices - Kanwal Javid; Muhammad Ameer Nawaz Akram; Maria Mumtaz Ranjha; Shazia Pervaiz (Arabian Journal of Geosciences, 2020)

Financial instability and CO2 emissions: cross-country evidence - Bo Yang; Minhaj Ali; Muhammad Rizwan Nazir; Wajeeh Ullah; Muhammad Qayyum (Air Quality, Atmosphere & Health, 2020)

Food Protein-Based Nanodelivery Systems for Hydrophobic and Poorly Soluble Compounds - Mily Bazezy Joelle Maviah; Muhammad Asim Farooq; Rukhshona Mavlyanova; Hanitrarimalala Veroniaina; Mensura Sied Filli; Md Aquib; Samuel Kesse; Kofi Oti Boakye-Yiadom; Bo Wang (AAPS PharmSciTech, 2020)

Model Structures and Identification for Fully Embedded Thrusters: 360-Degrees-Steerable Steering-Grid and Four-Channel Thrusters - Gerben Peeters; Muhammad Raheel Afzal; Maarten Vanierschot; René Boonen; Peter Slaets (Journal of Marine Science and Engineering, 2020)
The European Watertruck + project introduced a new fleet of self-propelled inland cargo barges to the European waters, in order to induce more sustainable freight transport in the European hinterland. An augmentation of the automation level of this fleet could further advance their competitiveness and potentially pave the way for unmanned inland cargo vessels. The motion control of such a vessel forms a key component in this envisaged automation chain and benefits from the knowledge of the capabilities of the propulsion system, which here envelops a 360-degrees-steerable steering-grid thruster in conjunction with a 360-degrees-steerable four-channel thruster. Therefore, this study details the mechanical design of both thrusters and lists their experimental towing-tank data. Furthermore, two different modelling methods are offered, one theoretically based and one using a multilayer neural network. A model structure comparison, based on a bias-variance trade-off, verifies the adequacy of the theoretical model which got expended with an angle-dependent thrust deduction coefficient. In addition, several multilayer feedforward neural network architectures exemplify their inherent capability to model the complex, nonlinear, flow phenomena inside the thrusters. These identified model structures can additionally improve thrust allocation algorithms and offer better plant models to study more advanced control strategies.

Anticancer and antibacterial potential of Rhus punjabensis and CuO nanoparticles - Sania Naz; Saira Tabassum; Nelson Freitas Fernandes; Mohammad Mujahid; Muhammad Zia; Esperanza J. Carcache de Blanco (Natural Product Research, 2020)

First Investigations on the Removal of Tungsten Species from Water Using Multi-walled Carbon Nanotubes - Ihsanullah Ihsanullah; Muhammad Sajid; Muhamed Kabeer; Ahsan Mushir Shemsi; Muataz Ali Atieh (Water, Air, & Soil Pollution, 2020)

Life cycle analysis of palm kernel shell gasification for supplying heat to an asphalt mixing plant - Sunu Herwi Pranolo; Prabang Setyono; Muhammad Akvis Fauzi (Waste Disposal & Sustainable Energy, 2020)

Regeneration response of carnation cultivars in response of silver nanoparticles under in vitro conditions - Muhammad Zia; Kamran Yaqoob; Abdul Mannan; Sobia Nisa; Ghulam Raza; Riaz ur Rehman (Vegetos, 2020)

Utilization of Leucaena leucocephala and Gliricidia sepium as supplements by goats fed Panicum maximum basal diet - Muhammad Rusdy; Muhammad Yusuf; Ismartoyo (Tropical Animal Health and Production, 2020)

Farmer’s Perception of and Factors Influencing Agroforestry Practices in the Indus River Basin, Pakistan - Muhammad Imran Mahmood; Muhammad Zubair (Small-scale Forestry, 2020)

Diverse and dynamic roles of F-box proteins in plant biology - Nur-Athirah Abd-Hamid; Muhammad-Izzat Ahmad-Fauzi; Zamri Zainal; Ismanizan Ismail (Planta, 2020)

Streptomyces sp. LH 4 promotes plant growth and resistance against Sclerotinia sclerotiorum in cucumber via modulation of enzymatic and defense pathways - Bong-Gyu Mun; Won-Hee Lee; Sang-Mo Kang; Sang-Uk Lee; Seok-Min Lee; Dong Yeol Lee; Muhammad Shahid; Byung-Wook Yun; In-Jung Lee (Plant and Soil, 2020)

Brassinosteroid seed priming with nitrogen supplementation improves salt tolerance in soybean - Mona Soliman; Amr Elkelish; Trabelsi Souad; Haifa Alhaithloul; Muhammad Farooq (Physiology and Molecular Biology of Plants, 2020)

Exogenously applied 5-aminolevulinic acid modulates growth, secondary metabolism and oxidative defense in sunflower under water deficit stress - Rizwan Rasheed; Humaira Yasmeen; Iqbal Hussain; Muhammad Iqbal; Muhammad Arslan Ashraf; Abida Parveen (Physiology and Molecular Biology of Plants, 2020)

Identification and validation of superior housekeeping gene(s) for qRT-PCR data normalization in Agave sisalana (a CAM-plant) under abiotic stresses - Muhammad Bilal Sarwar; Zarnab Ahmad; Batcho Agossa Anicet; Moon Sajid; Bushra Rashid; Sameera Hassan; Mukhtar Ahmed; Tayyab Husnain (Physiology and Molecular Biology of Plants, 2020)

Foliar applied fullerol differentially improves salt tolerance in wheat through ion compartmentalization, osmotic adjustments and regulation of enzymatic antioxidants - Fahad Shafiq; Muhammad Iqbal; Muhammad Arslan Ashraf; Muhammad Ali (Physiology and Molecular Biology of Plants, 2020)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)

Spatio-statistical analysis of rainfall fluctuation, anomaly and trend in the Hindu Kush region using ARIMA approach - Muhammad Dawood; Atta-ur Rahman; Sami Ullah; Shakeel Mahmood; Ghani Rahman; Kamran Azam (Natural Hazards, 2020)

Characterization of antifungal metabolites produced by Lactobacillus plantarum and Lactobacillus coryniformis isolated from rice rinsed water - Shazia Anwer Bukhari; Mahwish Salman; Muhammad Numan; Muhammad Rizwan Javed; Muhammad Zubair; Ghulam Mustafa (Molecular Biology Reports, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Groundwater quality assessment for drinking purpose: a case study from Sindh Industrial Trading Estate, Karachi, Pakistan - Muhammad Jahangir Khan; Bilal Ahmed Shah; Bassam Nasir (Modeling Earth Systems and Environment, 2020)

An experimental and modelling approach to produce biochar from banana peels through pyrolysis as potential renewable energy resources - Anurita Selvarajoo; Dinie Muhammad; Senthil Kumar Arumugasamy (Modeling Earth Systems and Environment, 2020)

Partial substitution of chemical fertilizers with organic amendments increased rice yield by changing phosphorus fractions and improving phosphatase activities in fluvo-aquic soil - Muhammad Qaswar; Rushan Chai; Waqas Ahmed; Huang Jing; Tianfu Han; Kailou Liu; Xinxin Ye; Yongmei Xu; Christian Kofi Anthonio; Huimin Zhang (Journal of Soils and Sediments, 2020)

Exogenous Selenium-Instigated Physiochemical Transformations Impart Terminal Heat Tolerance in Bt Cotton - Muhammad Farrukh Saleem; Muhammad Asif Kamal; Muhammad Shahid; Amna Saleem; Amir Shakeel; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Approaches in Enhancing Thermotolerance in Plants: An Updated Review - Shafaqat Ali; Muhammad Rizwan; Muhammad Saleem Arif; Rehan Ahmad; Mirza Hasanuzzaman; Basharat Ali; Afzal Hussain (Journal of Plant Growth Regulation, 2020)

Ameliorative Effects of Biochar on Rapeseed (Brassica napus L.) Growth and Heavy Metal Immobilization in Soil Irrigated with Untreated Wastewater - Muhammad Kamran; Zaffar Malik; Aasma Parveen; Li Huang; Muhammad Riaz; Saqib Bashir; Adnan Mustafa; Ghulam Hassan Abbasi; Bin Xue; Umeed Ali (Journal of Plant Growth Regulation, 2020)

In-Silico Evaluation of a New Gene From Wheat Reveals the Divergent Evolution of the CAP160 Homologous Genes Into Monocots - Muhammad Zayed; Mohamed A. Badawi (Journal of Molecular Evolution, 2020)

Pathogen-induced Defense Strategies in Plants - Qari Muhammad Imran; Byung-Wook Yun (Journal of Crop Science and Biotechnology, 2020)

Testing the effect of different insecticides on Myzus persicae (Homoptera: Aphididae) in field mustard (Brassicae campestris L.) Czern for possible consideration in an IPM strategy - Muhammad Shahbaz Khan; Muhammad Faheem Akbar; Amjad Sultan; Muhammad Shoaib Saleem; Chand Gul (International Journal of Tropical Insect Science, 2020)

Damage potential of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) on wheat grains stored in hermetic and non-hermetic storage bags - Bilal Atta; Muhammad Rizwan; Arshed Makhdoom Sabir; Muhammad Dildar Gogi; Kazam Ali (International Journal of Tropical Insect Science, 2020)

Allelopathic Crop Water Extracts Application Improves the Wheat Productivity Under Low and High Fertilizer Inputs in a Semi-Arid Environment - Ali Ahsan Bajwa; Ahmad Nawaz; Muhammad Farooq (International Journal of Plant Production, 2020)

Tachykinin-1 receptor antagonism suppresses substance-P- and compound 48/80-induced mast cell activation from rat mast cells expressing functional mas-related GPCR B3 - Muhammad N. A. Sahid; Shuang Liu; Masaki Mogi; Kazutaka Maeyama (Inflammation Research, 2020)

The role of garlic oil in the amelioration of oxidative stress and tissue damage in rohu Labeo rohita treated with silver nanoparticles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Wajid; Sabeen Sabri; Muhammad Shakir (Fisheries Science, 2020)

Therapeutic role of garlic and vitamins C and E against toxicity induced by lead on various organs - Shumaila Mumtaz; Shaukat Ali; Rida Khan; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Samiara Mumtaz; Saiqa Andleeb (Environmental Science and Pollution Research, 2020)

Achieving environmental sustainability through information technology: “Digital Pakistan” initiative for green development - Hassan Ahmad Nizam; Khalid Zaman; Khan Burhan Khan; Rubeena Batool; Muhammad Adnan Khurshid; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2020)

Fabrication of Pt-Pd@ITO grown heterogeneous nanocatalyst as efficient remediator for toxic methyl parathion in aqueous media - Ali Muhammad Mahar; Aamna Balouch; Farah Naz Talpur; Abdullah; Pirah Panah; Raj Kumar; Ameet Kumar; Abdul Hameed Pato; Dadu Mal; Sagar Kumar; Akrajas Ali Umar (Environmental Science and Pollution Research, 2020)

The effects of deforestation and urbanization on sustainable growth in Asian countries - Zeeshan Arshad; Margarita Robaina; Muhammad Shahbaz; Anabela Botelho Veloso (Environmental Science and Pollution Research, 2020)

Quantitative analysis of lead in cows and buffaloes for health assessment - Wuyi Liu; Naunain Mehmood; Humera Saeed; Muhammad Arshad; Zafar Iqbal Khan; Hira Muqaddas (Environmental Science and Pollution Research, 2020)

Identification of wheat (Triticum aestivum L.) genotypes for food safety on two different cadmium contaminated soils - Min Lu; Xuerui Cao; Jianqing Pan; Tingqiang Li; Muhammad Bilal Khan; Hanumanth Kumar Gurajala; Zhenli He; Xiaoe Yang (Environmental Science and Pollution Research, 2020)

Characterization of phenolic compounds in two novel lines of Pisum sativum L. along with their in vitro antioxidant potential - Nausheen Nazir; Mohammad Nisar; Sajjad Ahmad; Syed Fazal Wadood; Tour Jan; Muhammad Zahoor; Manzoor Ahmad; Abid Ullah (Environmental Science and Pollution Research, 2020)

Highly effective removal of Pb2+ in aqueous solution by Na-X zeolite derived from coal gangue - Qilong Ge; Muhammad Moeen; Qi Tian; Jianjie Xu; Kaiqing Feng (Environmental Science and Pollution Research, 2020)

Organochlorine pesticides in the surrounding soils of POPs destruction facility: source fingerprinting, human health, and ecological risks assessment - Syeda Nazish Ali; Mujtaba Baqar; Mehvish Mumtaz; Uzma Ashraf; Muhammad Naveed Anwar; Abdul Qadir; Sajid Rashid Ahmad; Abdul-Sattar Nizami; Huang Jun (Environmental Science and Pollution Research, 2020)

Does regional energy consumption disparities assist to control environmental degradation in OBOR: an entropy approach - Guijuan Sun; Chunhui Yuan; Muhammad Hafeez; Salman Raza; Liu Jie; Xiaodan Liu (Environmental Science and Pollution Research, 2020)

Examining foreign direct investment and environmental pollution linkage in Asia - Muhammad Azam Khan; Ilhan Ozturk (Environmental Science and Pollution Research, 2020)

The effects of tourism and globalization over environmental degradation in developed countries - Daniel Balsalobre-Lorente; Oana M. Driha; Muhammad Shahbaz; Avik Sinha (Environmental Science and Pollution Research, 2020)

Estimation of forest carbon stocks in temperate and subtropical mountain systems of Pakistan: implications for REDD+ and climate change mitigation - Anwar Ali; Muhammad Irfan Ashraf; Saeed Gulzar; Muhammad Akmal (Environmental Monitoring and Assessment, 2020)

Mangrove health along the hyper-arid southern Red Sea coast of Saudi Arabia - Muhammad Arshad; Ebrahem M. Eid; Mudassir Hasan (Environmental Monitoring and Assessment, 2020)

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)

Forecasting Nitrous Oxide emissions based on grey system models - Huaping Sun; Jingjing Jiang; Muhammad Mohsin; Jijian Zhang; Yasir Ahmed Solangi (Environmental Geochemistry and Health, 2020)

Comparing farmers’ perceptions of climate change with meteorological data in three irrigated cropping zones of Punjab, Pakistan - Muhammad Imran; Rajendra P. Shrestha; Avishek Datta (Environment, Development and Sustainability, 2020)

Estimation of rare and clustered population mean using stratified adaptive cluster sampling - Muhammad Nouman Qureshi; Cem Kadilar; Muhammad Hanif (Environmental and Ecological Statistics, 2020)

TiO2 Coated-Asphalt Buton Photocatalyst for High-Performance Motor Vehicles Gas Emission Mitigation - Muhammad Zakir Muzakkar; Muhammad Nurdin; Ima Ismail; Maulidiyah Maulidiyah; Dwiprayogo Wibowo; Ratna Ratna; Siti Khatijah Md Saad; Akrajas Ali Umar (Emission Control Science and Technology, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

ASTER-based remote sensing investigation of gypsum in the Kohat Plateau, north Pakistan - Asad Khan; Shah Faisal; Muhammad Shafique; Saad Khan; Alam Sher Bacha (Carbonates and Evaporites, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Isolation and genetic characterization of virulent strains of avian paramyxovirus-1 from multiple avian species in Azad Jammu and Kashmir 2017–2018 - Abid Hussain; Abdul Wajid; Safa Ather; Kashaf Alyas; Muhammad Awais; Muhammad Rizwan Khan; Tanveer Hussain; Masroor Ellahi Babar (Brazilian Journal of Microbiology, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

Disparities in Trace Metal Levels in Hodgkin/Non-Hodgkin Lymphoma Patients in Comparison with Controls - Muhammad Abdul Qayyum; Munir Hussain Shah (Biological Trace Element Research, 2020)

Integrated assessment of extreme climate and landuse change impact on sediment yield in a mountainous transboundary watershed of India and Pakistan - Muhammad Babur; Sangam Shrestha; Binod Bhatta; Avishek Datta; Hayat Ullah (Journal of Mountain Science, 2020)

Temperature trends and elevation dependent warming during 1965–2014 in headwaters of Yangtze River, Qinghai Tibetan Plateau - Naveed Ahmed; Gen-xu Wang; Adeyeri Oluwafemi; Sarfraz Munir; Zhao-yong Hu; Aamir Shakoor; Muhammad Ali Imran (Journal of Mountain Science, 2020)

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km 2 each, situated in the Chitral region (Hindukush Mountains) were investigated in this study. Digital Elevation Model (DEM) and available cloud-free continuous series of Landsat and Sentinel the entire study area was a retreat of -231 ± 140 m. No obvious relationship was found between the glacier variation trends and the available gauged climatic data possibly due to the presence of debris cover in ablation zones of all the studied glaciers which provides insulation and reduces the immediate climatic effects.

Migration and Household Adaptation in Climate-Sensitive Hotspots in South Asia - Amina Maharjan; Ricardo Safra de Campos; Chandni Singh; Shouvik Das; Arjun Srinivas; Mohammad Rashed Alam Bhuiyan; Sultan Ishaq; Muhammad Awais Umar; Tanzina Dilshad; Krity Shrestha; Suruchi Bhadwal; Tuhin Ghosh; et al. (Current Climate Change Reports, 2020)
Purpose of Review South Asia is highly vulnerable to the impacts of climate change, owing to the high dependency on climate-sensitive livelihoods and recurrent extreme events. Consequently, an increasing number of households are adopting labour migration as a livelihood strategy to diversify incomes, spread risks, and meet aspirations. Under the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) initiative, four research consortia have investigated migration patterns and their inherent linkages to adaptation to climate change in climate hotspots. This article synthesizes key findings in regional context of South Asia. Recent Findings The synthesis suggests that in climate-sensitive hotspots, migration is an important livelihood diversification strategy and a response to various risks, including climate change. Typically, one or more household members, often young men, migrated internally or internationally to work in predominantly informal sectors. Remittances helped spatially diversify household income, spread risks, and insure against external stressors. The outcomes of migration are often influenced by who moves, where to, and what capacities they possess. Summary Migration was found to help improve household adaptive capacity, albeit in a limited capacity. Migration was mainly used as a response to risk and uncertainty, but with potential to have positive adaptation co-benefits.

Assessment of subsurface lithology, groundwater depth, and quality of UET Lahore, Pakistan, using electrical resistivity method - Zahid Mehmood; Noor Muhammad Khan; Shamsher Sadiq; Saeed-ullah Jan Mandokhail; Syed Zishan Ashiq (Arabian Journal of Geosciences, 2020)

Analysis and mapping of present and future drivers of local urban climate using remote sensing: a case of Lahore, Pakistan - Muhammad Imran; Aqsa Mehmood (Arabian Journal of Geosciences, 2020)

Application of GIS/RS for monitoring of the ecological environment in a coastal zone - Rui Xie; Haihong Xiao; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

Impact assessment of land use and climate changes on the variation of runoff in Margalla Hills watersheds, Pakistan - Muhammad Shahid; Khalil Ur Rahman; Khaled S. Balkhair; Amjad Nabi (Arabian Journal of Geosciences, 2020)

Simplicispira hankyongi sp. nov., a novel denitrifying bacterium isolated from sludge - Muhammad Zubair Siddiqi; Wichny Sok; Gyumin Choi; Sang Yong Kim; Ji-Hyang Wee; Wan Taek Im (Antonie van Leeuwenhoek, 2020)

Core Competencies for Undergraduates in Bioengineering and Biomedical Engineering: Findings, Consequences, and Recommendations - John A. White; Donald P. Gaver; Robert J. Butera; Bernard Choi; Mary J. Dunlop; K. Jane Grande-Allen; Anna Grosberg; Robert W. Hitchcock; Aileen Y. Huang-Saad; Miiri Kotche; Aaron M. Kyle; Amy L. Lerner; et al. (Annals of Biomedical Engineering, 2020)

Pyrrolidine alkaloids and their promises in pharmacotherapy - Muhammad Torequl Islam; Mohammad Suleiman Mubarak (Advances in Traditional Medicine, 2020)

Antimicrobial, cytotoxic, phytochemical and biological properties of crude extract and solid phase fractions of Monotheca buxifolia - Joham Sarfraz Ali; Ihsan Khan; Muhammad Zia (Advances in Traditional Medicine, 2020)

Leea macrophylla (Roxb.) root extract reverses CCl4 induced liver injury through upregulation of antioxidative gene expression: a molecular interaction for therapeutic inception - Md. Rakibul Hassan Bulbul; Md. Atiar Rahman; Md. Zillur Rahman; Talha Bin Emran; Mirola Afroze; Mala Khan; Muhammad Abid Hasan Chowdhury; Mohammed Auwal Ibrahim; Mohammed Sohel Chowdhury (Advances in Traditional Medicine, 2020)

First Report Regarding the Simultaneous Molecular Detection of Anaplasma marginale and Theileria annulata in Equine Blood Samples Collected from Southern Punjab in Pakistan - Muhammad Asif; Asia Parveen; Sehrish Ashraf; Mureed Hussain; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Acta Parasitologica, 2020)

Linking traditional anti-ulcer use of rhizomes of Bergenia ciliata (Haw.) to its anti-Helicobacter pylori constituents - Ejaz Ali; Najma Arshad; Nadeem Irfan Bukhari; Muhammad Nawaz Tahir; Shamail Zafar; Amjad Hussain; Sajida Parveen; Shaista Qamar; Naureen Shehzadi; Khalid Hussain (Natural Product Research, 2020)

Urease inhibitory potential of extracts and active phytochemicals of Hypochaeris radicata (Asteraceae) - Tareq Abu-Izneid; Abdur Rauf; Muhammad Saleem; Nashwa Mansour; Mohamed I. S. Abdelhady; Munjed M. Ibrahim; Seema Patel (Natural Product Research, 2020)

Recent advances in protein derived bionanocomposites for food packaging applications - Muhammad Zubair; Aman Ullah (Critical Reviews in Food Science and Nutrition, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Datura suaveolens and Verbena tenuisecta mediated silver nanoparticles, their photodynamic cytotoxic and antimicrobial evaluation - Ahsan Ashraf; Nighat Fatima; Irum Shahzadi; Hina Tariq; Anam Shahzadi; Muhammad Arfat Yameen; Jamshed Iqbal; Muhammad Rafi (World Journal of Microbiology and Biotechnology, 2020)

Photocatalytic Performance of Zinc Ferrite Magnetic Nanostructures for Efficient Eriochrome Black-T Degradation from the Aqueous Environment under Unfiltered Sunlight - Ikramullah; Nisar Ali; Farman Ali; Zeshan Ali Sheikh; Muhammad Bilal; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2020)

Photocatalytic Degradation of Congo Red Dye from Aqueous Environment Using Cobalt Ferrite Nanostructures: Development, Characterization, and Photocatalytic Performance - Nisar Ali; Amir Said; Farman Ali; Fazal Raziq; Zarshad Ali; Muhammad Bilal; Laurence Reinert; Tasleem Begum; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2020)

Coagulation- and Adsorption-Based Environmental Impact Assessment and Textile Effluent Treatment - Muhammad Aleem; Jiashun Cao; Chao Li; Haroon Rashid; Yang Wu; Muhammad Imran Nawaz; Muhammad Abbas; Muhammad Waqar Akram (Water, Air, & Soil Pollution, 2020)

Fine mapping of root lesion nematode (Pratylenchus thornei) resistance loci on chromosomes 6D and 2B of wheat - Muhammad Shefatur Rahman; Katherine J. Linsell; Julian D. Taylor; Matthew J. Hayden; Nicholas C. Collins; Klaus H. Oldach (Theoretical and Applied Genetics, 2020)

Application of non-conventional soft computing approaches for estimation of reference evapotranspiration in various climatic regions - Ali Raza; Muhammad Shoaib; Afzaal Khan; Faisal Baig; Muhammad Abrar Faiz; Mudasser Muneer Khan (Theoretical and Applied Climatology, 2020)

The bacterial RNA ligase RtcB accelerates the repair process of fragmented rRNA upon releasing the antibiotic stress - Muhammad Ramzan Manwar; Changjun Shao; Xing Shi; Jian Wang; Qiang Lin; Yigang Tong; Yu Kang; Jun Yu (Science China Life Sciences, 2020)

Ketamine Alleviates Fear Generalization Through GluN2B-BDNF Signaling in Mice - Muhammad Asim; Bo Hao; Yu-Han Yang; Bu-Fang Fan; Li Xue; Yan-Wei Shi; Xiao-Guang Wang; Hu Zhao (Neuroscience Bulletin, 2020)

5-Endo-dig cyclizations in organic syntheses - Muhammad Aamir Sajid; Zulfiqar Ali Khan; Sohail Anjum Shahzad; Syed Ali Raza Naqvi; Muhammad Usman (Molecular Diversity, 2020)

Characterization of a novel Helicobacter pylori East Asian-type CagA ELISA for detecting patients infected with various cagA genotypes - Dalla Doohan; Muhammad Miftahussurur; Yuichi Matsuo; Yasutoshi Kido; Junko Akada; Takeshi Matsuhisa; Than Than Yee; Kyaw Htet; Hafeza Aftab; Ratha-korn Vilaichone; Varocha Mahachai; Thawee Ratanachu-ek; et al. (Medical Microbiology and Immunology, 2020)

Tillage practices improve rice yield and soil phosphorus fractions in two typical paddy soils - Waqas Ahmed; Muhammad Qaswar; Huang Jing; Dong Wenjun; Sun Geng; Liu Kailou; Meng Ying; Tang Ao; Sun Mei; Li Chao; Xu Yongmei; Sehrish Ali; et al. (Journal of Soils and Sediments, 2020)

Microzonation map of the Abbottabad basin and immediate surroundings - Sarfraz Khan; Muhammad Waseem; Muhammad Asif Khan; Zahid Hussain; Waqas Ahmed; Ahmad Hamad Khaliq; Nisar Bin Umair; Mian Luqman Hussain (Journal of Seismology, 2020)

Lethal and parasitism effects of selected novel pesticides on adult Trichogramma chilonis (Hymenoptera: Trichogrammatidae) - Muhammad Ashraf Khan (Journal of Plant Diseases and Protection, 2020)

First report of post-harvest rot of Citrus reticulata cv. ‘Kinnow’ caused by Rhizopus arrhizus in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Aman Ullah Malik; Mark Lawrence Gleason; Binyamin Rana; Muhammad Amjad Ali (Journal of Plant Pathology, 2020)

Molecular characterization and phylogenetic analysis of Pantoea stewartii subspecies stewartii causing bronzing disease of jackfruit in Malaysia based on cps and hrp gene sequences - Rohaya Ibrahim; Noor Wahida Ismail-Suhaimy; Tan Shu-Qing; Siti Izera Ismail; Nuraizat Abidin; Mansor Hakiman; Daljit Singh Karam; Muhammad Saiful Ahmad-Hamdani; Mohd Termizi Yusof; Dzarifah Zulperi (Journal of Plant Pathology, 2020)

First report of Alternaria brown spot of Citrus reticulata cv. ‘Kinnow’ caused by Alternaria arborescens in Pakistan - Anam Moosa; Ayaz Farzand; Muhammad Fahim Abbas; Shahbaz Talib Sahi; Sajid Aleem Khan; Mark Lawrence Gleason (Journal of Plant Pathology, 2020)

An overview of the common bacterial diseases of potato in Pakistan, associated crop losses and control stratagems - Abdul Majeed; Zahir Muhammad (Journal of Plant Pathology, 2020)

First report of Nigrospora sphaerica causing leaf spot of date palm in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Shahbaz Ahmad; Mubeen Sarwar; Aamir Nawaz; Samiya Mahmood Khan; Sajid Ali; Sidra Aslam; Abdul Mannan (Journal of Plant Pathology, 2020)

CRISPR/Cas9: targeted genome editing for the treatment of hereditary hearing loss - Rimsha Farooq; Khadim Hussain; Muhammad Tariq; Ali Farooq; Muhammad Mustafa (Journal of Applied Genetics, 2020)

Effects of Burkholderia sp. D54 on growth and cadmium uptake of tomato, ryegrass and soybean plants - J. K. Guo; J. Zhao; X. H. Ren; H. L. Jia; H. Muhammad; X. Lv; T. Wei; L. Hua (International Journal of Environmental Science and Technology, 2020)

Characteristically Insights, Artificial Neural Network (ANN), Equilibrium, and Kinetic Studies of Pb(II) Ion Adsorption on Rice Husks Treated with Nitric Acid - Sami Ullah; Mohammed Ali Assiri; Abdullah Ghodran Al-Sehemi; Mohamad Azmi Bustam; Muhammad Sagir; Firas Ayad Abdulkareem; Muhammad Rafi Raza; Muhammad Ayoub; Ahmad Irfan (International Journal of Environmental Research, 2020)

Correction to: Moringa oleifera leaf extracts attenuate Complete Freund’s adjuvant-induced arthritis in Wistar rats via modulation of inflammatory and oxidative stress biomarkers - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Moringa rivae leaf extracts attenuate Complete Freund’s adjuvant-induced arthritis in Wistar rats via modulation of inflammatory and oxidative stress biomarkers - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

The mRNA expression patterns of kisspeptins, GnRHs, and gonadotropins in the brain and pituitary gland of a tropical damselfish, Chrysiptera cyanea, during the reproductive cycle - Satoshi Imamura; Sung-Pyo Hur; Yuki Takeuchi; Muhammad Badruzzaman; Angka Mahardini; Dinda Rizky; Akihiro Takemura (Fish Physiology and Biochemistry, 2020)

Copper-induced oxidative stress, initiation of antioxidants and phytoremediation potential of flax (Linum usitatissimum L.) seedlings grown under the mixing of two different soils of China - Muhammad Hamzah Saleem; Shah Fahad; Shahid Ullah Khan; Mairaj Din; Abid Ullah; Ayman EL Sabagh; Akbar Hossain; Analía Llanes; Lijun Liu (Environmental Science and Pollution Research, 2020)

Effects of divalent copper on tetracycline degradation and the proposed transformation pathway - Ying Zhu; Kun Liu; Yaseen Muhammad; Hanbing Zhang; Zhangfa Tong; Binbin Yu; Maria Sahibzada (Environmental Science and Pollution Research, 2020)

The role of financial development, energy demand, and technological change in environmental sustainability agenda: evidence from selected Asian countries - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir (Environmental Science and Pollution Research, 2020)

Revealing heterogeneous causal links among financial development, construction industry, energy use, and environmental quality across development levels - Munir Ahmad; Gul Jabeen; Muhammad Khizar Hayat; Rana Ejaz Ali Khan; Shoaib Qamar (Environmental Science and Pollution Research, 2020)

Energy capacity, industrial production, and the environment: an empirical analysis from Pakistan - Muhammad Tariq Mahmood; Sadaf Shahab; Muhammad Hafeez (Environmental Science and Pollution Research, 2020)

Effects of silicon nanoparticles on growth and physiology of wheat in cadmium contaminated soil under different soil moisture levels - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Adrees; Muhammad Farooq Qayyum; Sofia Khalid; Muhammad Zia ur Rehman; Muhammad Aleem Sarwar (Environmental Science and Pollution Research, 2020)

Economics of energy and environmental efficiency: evidence from OECD countries - Robina Iram; Jijian Zhang; Seyfettin Erdogan; Qaiser Abbas; Muhammad Mohsin (Environmental Science and Pollution Research, 2020)

Contamination of soil with potentially toxic metals and their bioaccumulation in wheat and associated health risk - Jawad Ali; Sardar Khan; Anwarzeb Khan; Muhammad Waqas; Muhammad Jamal Nasir (Environmental Monitoring and Assessment, 2020)

Investigating municipal solid waste management system performance during the Arba’een event in the city of Kerbala, Iraq - Muhammad Abdulredha; Patryk Kot; Rafid Al Khaddar; David Jordan; Ali Abdulridha (Environment, Development and Sustainability, 2020)

An epicardial delivery of nitroglycerine by active hydraulic ventricular support drug delivery system improves cardiac function in a rat model - Xue Li; Reyaj Mikrani; Cunyu Li; Muhammad Naveed; Ziwei Liu; Muhammad Abbas; Yijie Cheng; Lei Han; Zhijie Wang; Xiaohui Zhou (Drug Delivery and Translational Research, 2020)

Evidence for genetic structuring and limited dispersal ability in the Great Barrier Reef sponge Carteriospongia foliascens - Megan R. Shaffer; Heidi M. Luter; Nicole S. Webster; Muhammad A. Abdul Wahab; James J. Bell (Coral Reefs, 2020)

An effective modification of finite element method for heat and mass transfer of chemically reactive unsteady flow - Yasir Nawaz; Muhammad Shoaib Arif (Computational Geosciences, 2020)

Cytotoxic and Genotoxic Assessment of Silicon Dioxide Nanoparticles by Allium and Comet Tests - Recep Liman; Yaser Acikbas; İbrahim Hakkı Ciğerci; Muhammad Muddassir Ali; Meltem Demirel Kars (Bulletin of Environmental Contamination and Toxicology, 2020)

Correction to: Synthesis and Biodistribution Study of Biocompatible 198Au Nanoparticles by use of Arabinoxylan as Reducing and Stabilizing Agent - Fozia Iram; Mohammad S. Iqbal; Irfan U. Khan; Rashid Rasheed; Aqsa Khalid; Muhammad Khalid; Saira Aftab; Abdul R. Shakoori (Biological Trace Element Research, 2020)

Inhibition of Hyperuricemia and Gouty Arthritis in BALB/c Mice Using Copper Oxide Nanoparticles - Mubin Mustafa Kiyani; Hamza Rehman; Mir Arif Hussain; Saira Jahan; Muhammad Afzal; Irum Nawaz; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2020)

Changes in abundance and composition of nitrifying communities in barley (Hordeum vulgare L.) rhizosphere and bulk soils over the growth period following combined biochar and urea amendment - Lu Yu; Peter M. Homyak; Xiaoxi Kang; Philip C. Brookes; Yikai Ye; Yeneng Lin; Afzal Muhammad; Jianming Xu (Biology and Fertility of Soils, 2020)

Journey of begomovirus betasatellite molecules: from satellites to indispensable partners - Muhammad Mubin; Sehrish Ijaz; Nazia Nahid; Muhammad Hassan; Ayesha Younus; Javaria Qazi; Muhammad Shah Nawaz-ul-Rehman (Virus Genes, 2020)

Long-segment transverse myelitis in an immunocompetent patient due to varicella zoster virus reactivation - Tanvi Goyal; Muhammad Zaheer; Anirudh Goyal; Zubair Khan (Journal of NeuroVirology, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Spatio-Temporal Variability of Summer Monsoon Onset over Pakistan - Shaukat Ali; Bushra Khalid; Rida Sehar Kiani; Romaisa Babar; Sana Nasir; Nadia Rehman; Muhammad Adnan; Muhammad Arif Goheer (Asia-Pacific Journal of Atmospheric Sciences, 2020)

TAC1, an unclassified bacteriophage of the family Myoviridae infecting Acinetobacter baumannii with a large burst size and a short latent period - Muhammad Asif; Iqbal Ahmad Alvi; Rabia Tabassum; Shafiq Ur Rehman (Archives of Virology, 2020)

Delineation of regional groundwater vulnerability using DRASTIC model for agricultural application in Pakistan - Aamir Shakoor; Zahid M. Khan; Hafiz U. Farid; Muhammad Sultan; Ijaz Ahmad; Naveed Ahmad; Muhammad H. Mahmood; Muhammad U. Ali (Arabian Journal of Geosciences, 2020)

Dynamics of AB-DTPA-extractable Zn in high and low limed calcareous soils amended with biochar and farmyard and poultry manures - Abida Saleem; Dost Muhammad; Mumtaz Khan; Qudrat Ullah Khan; Muhammad Rizwan; Salma Shaheen; Hamza Noor; Shiza Gul; Muhammad Daud Khan; Shafaqat Ali (Arabian Journal of Geosciences, 2020)

3D modelling of the strength effect of backfill-rocks on controlling rockburst risk: a case study - Xiaojun Feng; Qiming Zhang; Muhammad Ali (Arabian Journal of Geosciences, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

Spatiotemporal variability in spate irrigation systems in Khirthar National Range, Sindh, Pakistan (case study) - Abdul Ghani Soomro; Muhammad Munir Babar; Muhammad Arshad; Anila Memon; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Estimation of groundwater potential using GIS modeling in Kohistan region Jamshoro district, Southern Indus basin, Sindh, Pakistan (a case study) - Aneela Memon; Kamran Ansari; Abdul Ghani Soomro; Muhammad Afzal Jamali; Babar Naeem; Arshad Ashraf (Acta Geophysica, 2020)

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus - Zulcaif Ahmad; Muhammad Imran Khan; Muhammad Irfan Siddique; Hafiz Shoaib Sarwar; Gul Shahnaz; Syed Zajif Hussain; Nadeem Irfan Bukhari; Irshad Hussain; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Development and Characterization of Bioadhesive Film Embedded with Lignocaine and Calcium Fluoride Nanoparticles - Hira Ghafar; Muhammad Imran Khan; Hafiz Shoaib Sarwar; Samiya Yaqoob; Syed Zajif Hussain; Imran Tariq; Asad Ullah Madni; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

In Vivo Evaluation of a Novel Chitosan-Polycaprolactone Based Mucoadhesive Gastro-Retentive Sustained Release Drug Delivery System for Milnacipran HCl - Talib Hussain; Muhammad Ijaz; Rahat Shamim; Khalid Hussain; Nasir Abbas; Amjad Hussain; Julia Anita Griessinger; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2020)

Assessing Drug Release from Manipulated Abuse Deterrent Formulations - Xin Feng; Ahmed Zidan; Nahid S. Kamal; Xiaoming Xu; Dajun Sun; Ross Walenga; Heather Boyce; Celia N. Cruz; Muhammad Ashraf (AAPS PharmSciTech, 2020)

EVALUATION OF AQUACROP MODEL IN SIMULATING BITTER GOURD WATER PRODUCTIVITY UNDER SALINE IRRIGATION - Kamran Baksh Soomro; Sina Alaghmand; Muhammad Rizwan Shahid; Sanyogita Andriyas; Amin Talei (Irrigation and Drainage, 2020)
The agricultural sector, globally, faces multifaceted challenges to produce more with a minimum amount of water to enhance water productivity (WP). In this regard, crop modelling is an efficient approach for estimating WP and plays a significant role in addressing water management strategies. The present research has been conducted in Malir, Karachi—a semi‐arid region in the Sindh Province of Pakistan. The aim was to evaluate the effects of two different qualities of irrigation water including, fresh quality (IT 1 0.56 dS m −1 ) and saline groundwater (IT 2 2.89 dS m −1 ) on canopy cover (CC), biomass, crop yield and water productivity (WP) of bitter‐gourd. The AquaCrop model was used for the first time for bitter gourd in a semi‐arid region under drip irrigation. Simulations were carried out for two cropping seasons (i.e. season one (summer) and season two (winter). The modelled values were slightly higher than the measured biomass and yield values in both calibration and validation procedures. The performance of the AquaCrop model was estimated through different statistical indicators such as model efficiency ( E ), root mean square error (RMSE), and index of agreement ( d index ). These indicators revealed that the model simulated bitter gourd biomass and crop yield well. In addition, the model's performance was good under all irrigation treatments, with RMSE in the range 1.2–3.7, 0.5–1.8, d index 0.94–0.98 and E 0.93–0.97. The model also overestimated the biomass and crop yield. Overall, the AquaCrop model overestimated biomass and crop yield for both seasons. © 2019 John Wiley & Sons, Ltd.

Applications of microalga Chlorella vulgaris in aquaculture - Muhammad Talba Ahmad; Mohamed Shariff; Fatimah Md. Yusoff; Yong Meng Goh; Sanjoy Banerjee (Reviews in Aquaculture, 2020)
Microalgae biomass is used in aquaculture as feed, growth enhancers and immunostimulants. Chlorella vulgaris is an important species with a good biomolecular composition. Commercially, it is one of the most commonly used microalga in aquaculture. Several studies confirmed its ability to improve nutrition, immunity, aquatic bioremediation, amelioration of stress, disease resistance of fish and inhibits bacterial quorum sensing when used appropriately. Despite claims of its benefits, C. vulgaris is reported to have unfavourable effects when incorporated in diets at higher inclusion levels. In addition, its rigid cell wall might restrict the access of digestive enzymes to the intracellular components for proper digestion and assimilation. Thus, this review discusses the role of C. vulgaris and its importance in aquaculture with emphasis on its environmental requirements, morphology, pigments, digestibility, dynamics on growth performance, antibacterial activity, bacterial quorum sensing, immunomodulatory effect, anti‐stress effect, gut microbiome, aquatic bioremediation and its safety as food or feed.

Exploring socio-hydrological determinants of crop yield in under-performing irrigation schemes: pathways for sustainable intensification - Muhammad Khalifa; Nadir Ahmed Elagib; Bashir Mohammed Ahmed; Lars Ribbe; Karl Schneider (Hydrological Sciences Journal, 2020)

Line matching of wide baseline images in an affine projection space - Qiang Wang; Wei Zhang; Xiaolong Liu; Zhenxin Zhang; Muhammad Hasan Ali Baig; Guo Wang; Long He; Tiejun Cui (International Journal of Remote Sensing, 2020)

To Ban or Not to Ban? Reviewing an Ongoing Dilemma on Sea Turtle Egg Trade in Terengganu, Malaysia - Jarina Mohd Jani; Muhammad Allim Jamalludin; Seh Ling Long (Frontiers in Marine Science, 2020)

In-vitro and in-silico anticancer potential of taxoids from Taxus wallichiana Zucc - Mughal Qayum; Muhammad Nisar; Abdur Rauf; Imran Khan; Waqar Ahmad Kaleem; Muslim Raza; Nasiara Karim; Munawar Ahmad Saleem; Saud Bawazeer; Sengul Uysal; Gokhan Zengin; Saqib Jahan; et al. (Biologia Futura, 2020)
Introduction Natural products derived from medicinal plants provide beneficial cancer chemotherapeutic drugs. Bioactive constituents from plants are explored for their anticancer properties. Methods Three known compounds (deacetylbaccatin III, tasumatrol B, and taxawallin J) were isolated from Taxus wallichiana . Compounds were screened against four cancer cell lines, such as eA498, HepG2, NCI-H226, and MDR 2780AD. Cytotoxic activity was evaluated using MTT assay against cancer cell lines. Results Tasumatrol B showed good cytotoxic activity conducted for the improvement of inhibiting potential of these compounds against the cancer drug target protein (EGFR tyrosine kinase enzyme). The docking study showed that all compounds have binding affinities and interaction profile with the receptor tyrosine kinase. Discussion The study suggests that these compounds could be used for the discovery of novel inhibitors against the target receptors for the treatment of cancer.

Natural and semisynthetic polymers blended orodispersible films of citalopram - Yasser Shahzad; Maimoona Maqbool; Talib Hussain; Abid Mehmood Yousaf; Ikram Ullah Khan; Tariq Mahmood; Muhammad Jamshaid (Natural Product Research, 2020)

Variations in the microbial community of biofilms under different near-wall hydraulic shear stresses in agricultural irrigation systems - Peng Hou; Tianzhi Wang; Bo Zhou; Peng Song; Wenzhi Zeng; Tahir Muhammad; Yunkai Li (Biofouling, 2020)

Population diversity of Cistopus indicus inferred from mitochondrial DNA (Cytochrome b) variation from China and Vietnam - Canfeng Dou; Faiz Muhammad; Liqin Liu; Li Gong; Yongjiu Chen; Baoying Guo; Zhenming Lü (Molluscan Research, 2020)

Efficient Capture of Phosphate and Cadmium Using Biochar with Multifunctional Amino and Carboxylic Moieties: Kinetics and Mechanism - Faheem; Jiangkun Du; Jianguo Bao; Muhammad Azher Hassan; Sana Irshad; Muhammad Afnan Talib; Han Zheng (Water, Air, & Soil Pollution, 2020)

Propagation of the Multi-Scalar Aggregative Standardized Precipitation Temperature Index and its Application - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Dost Muhammad Khan; Rizwan Niaz; Elsayed Elsherbini Elashkar; Alaa Mohamd Shoukry (Water Resources Management, 2020)

Genetic survey of cystic echinococcosis in farm animals in Oman - Fadya Abdullah AlKitani; Senan Baqir; Muhammad Khalid Mansoor; Shumoos AlRiyami; Muhammad Hammad Hussain; Derek Roberts (Tropical Animal Health and Production, 2020)

Linking Morphology of Porous Media to Their Macroscopic Permeability by Deep Learning - Serveh Kamrava; Pejman Tahmasebi; Muhammad Sahimi (Transport in Porous Media, 2020)

Pore Network Investigation of Trapped Gas and Foam Generation Mechanisms - Muhammad M. Almajid; Anthony R. Kovscek (Transport in Porous Media, 2020)

Spatial analysis of temperature time series over the Upper Indus Basin (UIB) Pakistan - Yasir Latif; Ma Yaoming; Muhammad Yaseen; Sher Muhammad; Muhammad Atif Wazir (Theoretical and Applied Climatology, 2020)
Runoff generated from the Upper Indus Basin (UIB) mainly originates in the massifs of the Hindukush–Karakoram–Himalaya (HKH) region of Pakistan. Water supply in early spring depends upon the snow accumulation in the winter and the subsequent temperature. Seasonal temperature variations corroborate the contemporary dynamics of snow and glaciers. Recently, there has been increasing evidence of accelerated warming in high mountain areas, termed as elevation-dependent warming (EDW). We have identified trends, analyzed inconsistencies, and calculated changes in the maximum, minimum, mean and diurnal temperature range ( T max , T min , T mean , and DTR) at 20 weather stations during four-time series: 1961–2013 (first), 1971–2013 (second), 1981–2013 (third), and 1991–2013 (fourth). We employed the Mann–Kendall test to determine the existence of a trend and Sen’s method for the estimation of prevailing trends, whereas homogeneity analysis was applied before trend identification using three different tests. This study revealed that the largest and smallest magnitudes of trends appeared in the winter and summer, respectively, particularly during the fourth data series. T max revealed robust warming at ten stations, most remarkably at Gupis, Khunjrab, and Naltar at rates of 0.29, 0.36, and 0.43 °C/decade, respectively, during the fourth series. We observed that T min exhibits a mixed pattern of warming and cooling during the second and third series, but cooling becomes stronger during the fourth series, exhibiting significant trends at twelve stations. Khunjrab and Naltar showed steady warming during the fourth series (spring), at rates of 0.26 and 0.13 °C/decade in terms of T mean . The observed decreases in DTR appeared stronger in the fourth series during the summer. These findings tend to partially support the notion of EDW but validate the dominance of cooling spatially and temporally.

Investigating effect of climate change on drought propagation from meteorological to hydrological drought using multi-model ensemble projections - Muhammad Jehanzaib; Muhammad Nouman Sattar; Joo-Heon Lee; Tae-Woong Kim (Stochastic Environmental Research and Risk Assessment, 2020)

Osmoprotection in plants under abiotic stresses: new insights into a classical phenomenon - Faisal Zulfiqar; Nudrat Aisha Akram; Muhammad Ashraf (Planta, 2020)

Isolation and functional characterization of an Ethylene Response Factor (RhERF092) from rose (Rosa hybrida) - Muhammad Ali Khan; Muhammad Imtiaz; Adil Hussain; Fazal Jalal; Sikandar Hayat; Sayed Hussain; Fazal Said; Mehboob Alam; Rabia Amir (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

3D-Deep Learning Based Automatic Diagnosis of Alzheimer’s Disease with Joint MMSE Prediction Using Resting-State fMRI - Nguyen Thanh Duc; Seungjun Ryu; Muhammad Naveed Iqbal Qureshi; Min Choi; Kun Ho Lee; Boreom Lee (Neuroinformatics, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

Chemical screening identifies an extract from marine Pseudomonas sp.-PTR-08 as an anti-aging agent that promotes fission yeast longevity by modulating the Pap1–ctt1+ pathway and the cell cycle - Muhammad Eka Prastya; Rika Indri Astuti; Irmanida Batubara; Hiroshi Takagi; Aris Tri Wahyudi (Molecular Biology Reports, 2020)

Awareness and current knowledge of epilepsy - Asmat Ullah Khan; Muhammad Akram; Muhammad Daniyal; Naheed Akhter; Muhammad Riaz; Naheed Akhtar; Mohammad Ali Shariati; Fozia Anjum; Samreen Gul Khan; Abida Parveen; Saeed Ahmad (Metabolic Brain Disease, 2020)

In situ immobilization of Cr and its availability to maize plants in tannery waste–contaminated soil: effects of biochar feedstock and pyrolysis temperature - Muhammad Imran Rafique; Adel R. A. Usman; Munir Ahmad; Abdelazeem Sallam; Mohammad I. Al-Wabel (Journal of Soils and Sediments, 2020)

Antibiotics in poultry manure and their associated health issues: a systematic review - Juma Muhammad; Sardar Khan; Jian Qiang Su; Abd El-Latif Hesham; Allah Ditta; Javed Nawab; Abid Ali (Journal of Soils and Sediments, 2020)

Loop-mediated isothermal amplification for the detection of R81T mutation in nAChR with crude genomic DNA extracted from individual Myzus persicae - Muhammad Umair Sial; Zhenzhen Zhao; Lan Zhang; Yanning Zhang; Liangang Mao; Hongyun Jiang (Journal of Pest Science, 2020)

Genotyping of methicillin-resistant Staphylococcus aureus from sepsis patients in Pakistan and detection of antibodies against staphylococcal virulence factors - Stefan Monecke; Muhammad Ali Syed; Mushtaq Ahmad Khan; Shehzad Ahmed; Sadia Tabassum; Darius Gawlik; Elke Müller; Annett Reissig; Sascha D. Braun; Ralf Ehricht (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Fluorosis and cognitive development among children (6–14 years of age) in the endemic areas of the world: a review and critical analysis - Muhammad Saeed; Riffat Naseem Malik; Atif Kamal (Environmental Science and Pollution Research, 2020)

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

Photocatalytic degradation and kinetic modeling of azo dye using bimetallic photocatalysts: effect of synthesis and operational parameters - Nadia Riaz; Maryam Hassan; Maria Siddique; Qaisar Mahmood; Umar Farooq; Rizwana Sarwar; Muhammad Saqib Khan (Environmental Science and Pollution Research, 2020)

Energy efficiency and underlying carbon emission trends - Muhammad Javid; Muhammad Khan (Environmental Science and Pollution Research, 2020)

Spatial prioritization of willingness to pay for ecosystem services. A novel notion of distance from origin’s impression - Sufyan Ullah Khan; Guobin Liu; Minjuan Zhao; Hsiaoping Chien; Qian Lu; Arshad Ahmad Khan; Muhammad Abu Sufyan Ali; Misbahullah (Environmental Science and Pollution Research, 2020)

Synergistic effect of heartwood extracts in combination with linseed oil as wood preservatives against subterranean termite Heterotermes indicola (Blattodea: Rhinotermitidae) - Babar Hassan; Sohail Ahmed; Grant Kirker; Mark E. Mankowski; Muhammad Misbah ul Haq (Environmental Science and Pollution Research, 2020)

International tourism, social distribution, and environmental Kuznets curve: evidence from a panel of G-7 countries - Muhammad Khalid Anser; Zahid Yousaf; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Human health risks by potentially toxic metals in drinking water along the Hattar Industrial Estate, Pakistan - Shah Jehan; Seema Anjum Khattak; Said Muhammad; Liaqat Ali; Abdur Rashid; Mian Luqman Hussain (Environmental Science and Pollution Research, 2020)

Modeling heterogeneous dynamic interactions among energy investment, SO2 emissions and economic performance in regional China - Munir Ahmad; Zhen-Yu Zhao; Muhammad Irfan; Marie Claire Mukeshimana; Abdul Rehman; Gul Jabeen; Heng Li (Environmental Science and Pollution Research, 2020)

Nonrenewable energy—environmental and health effects on human capital: empirical evidence from Pakistan - Muhammad Mansoor Asghar; Zhaohua Wang; Bo Wang; Syed Anees Haider Zaidi (Environmental Science and Pollution Research, 2020)

Assessment of noise pollution and its effects on human health in industrial hub of Pakistan - Zia Ur Rahman Farooqi; Muhammad Sabir; Junaid Latif; Zubair Aslam; Hamaad Raza Ahmad; Iftikhar Ahmad; Muhammad Imran; Predrag Ilić (Environmental Science and Pollution Research, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

Socio-economic, macroeconomic, demographic, and environmental variables as determinants of child mortality in South Asia - Muhammad Zakaria; Samia Tariq; Muhammad Iftikhar ul Husnain (Environmental Science and Pollution Research, 2020)

Glycinebetaine alleviates the chromium toxicity in Brassica oleracea L. by suppressing oxidative stress and modulating the plant morphology and photosynthetic attributes - Rehan Ahmad; Shafaqat Ali; Muhammad Abid; Muhammad Rizwan; Basharat Ali; Asif Tanveer; Irfan Ahmad; Muhammad Azam; Muhammad Awais Ghani (Environmental Science and Pollution Research, 2020)

Assessment of soil erosion risk and its response to climate change in the mid-Yarlung Tsangpo River region - Li Wang; Fan Zhang; Suhua Fu; Xiaonan Shi; Yao Chen; Muhammad Dodo Jagirani; Chen Zeng (Environmental Science and Pollution Research, 2020)

Role of cotton sticks biochar in immobilization of nickel under induced toxicity condition and growth indices of Trigonella corniculata L. - Uzma Younis; Subhan Danish; Saeed Ahmad Malik; Niaz Ahmed; Tariq Muhammad Munir; Muhammad Khalid Rasheed (Environmental Science and Pollution Research, 2020)

Reduced Cd, Pb, and As accumulation in rice (Oryza sativa L.) by a combined amendment of calcium sulfate and ferric oxide - Weiwei Zhai; Wenliang Zhao; Honghong Yuan; Ting Guo; Muhammad Zaffar Hashmi; Xingmei Liu; Xianjin Tang (Environmental Science and Pollution Research, 2020)

Modification of acidic and textural properties of a sulphated zirconia catalyst for efficient conversion of high-density polyethylene into liquid fuel - Muhammad N. Almustapha; Muhammad Farooq; Misbahu L. Mohammed; Muhammad Farhan; Muhammad Imran; John M. Andresen (Environmental Science and Pollution Research, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Delineation of contaminated aquifers using integrated geophysical methods in Northeast Punjab, Pakistan - Muhammad Hasan; Yanjun Shang; Gulraiz Akhter; Weijun Jin (Environmental Monitoring and Assessment, 2020)

Assessment of arsenic exposure by drinking well water and associated carcinogenic risk in peri-urban areas of Vehari, Pakistan - Ali Haidar Shah; Muhammad Shahid; Sana Khalid; Natasha; Zunaira Shabbir; Hafiz Faiq Bakhat; Behzad Murtaza; Amjad Farooq; Muhammad Akram; Ghulam Mustafa Shah; Wajid Nasim; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2020)

Potential predictability of boreal winter precipitation over central-southwest Asia in the North American multi-model ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui (Climate Dynamics, 2020)

Adsorption–Desorption Behavior of Polar Imidazolinone Herbicides in Tropical Paddy Fields Soils - Saba Yavari; Nasiman B. Sapari; Amirhossein Malakahmad; Muhammad Azzam Bin Razali; Tchawe Siewe Gervais; Sara Yavari (Bulletin of Environmental Contamination and Toxicology, 2020)

Synthesis and Biodistribution Study of Biocompatible 198Au Nanoparticles by use of Arabinoxylan as Reducing and Stabilizing Agent - Fozia Iram; Mohammad S. Iqbal; Irfan U. Khan; Rashid Rasheed; Aqsa Khalid; Muhammad Khalid; Saira Aftab; Abdul R. Shakoori (Biological Trace Element Research, 2020)

Comparison of water use efficiency, profitability and consumer preferences of different rice varieties in Punjab, Pakistan - Muhammad Asad ur Rehman Naseer; Muhammad Ashfaq; Amar Razzaq; Qamar Ali (Paddy and Water Environment, 2020)

Spatiotemporal trends in reference evapotranspiration over South Korea - Ju Ha Hwang; Muhammad Azam; Maeng Seung Jin; Yong Ho Kang; Jae Eun Lee; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Muhammad Zaffar Hashmi (Paddy and Water Environment, 2020)

Cell membrane fatty acid and pigment composition of the psychrotolerant cyanobacterium Nodularia spumigena CHS1 isolated from Hopar glacier, Pakistan - Noor Hassan; Alexandre M. Anesio; Muhammad Rafiq; Jens Holtvoeth; Ian Bull; Christopher J. Williamson; Fariha Hasan (Extremophiles, 2020)

Middle Miocene Giraffokeryx (Giraffidae) with marks of enamel hypoplasia from Dhok Bun Amir Khatoon, Punjab, Pakistan - Muhammad Akbar Khan; Muhammad Asim (Arabian Journal of Geosciences, 2020)

Land-use change in plateau lake basin and its impact on urban ecological security - Zijiang Yang; Xiong He; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

Structural styles, hydrocarbon prospects, and potential of Miano and Kadanwari fields, Central Indus Basin, Pakistan - Saif-Ur-Rehman K. Jadoon; Ding Lin; Siddique Akhtar Ehsan; Ishtiaq A. K. Jadoon; Muhammad Idrees (Arabian Journal of Geosciences, 2020)

The application of the intelligent algorithm in the prevention and early warning of mountain mass landslide disaster - Yuan Yan; Muhammad Aqeel Ashraf (Arabian Journal of Geosciences, 2020)

Biomass for renewable energy production in Pakistan: current state and prospects - Muhammad Yaseen; Farhat Abbas; Muhammad Bilal Shakoor; Aitazaz A. Farooque; Muhammad Rizwan (Arabian Journal of Geosciences, 2020)

Tephra glass chemistry provides storage and discharge details of five magma reservoirs which fed the 75 ka Youngest Toba Tuff eruption, northern Sumatra - Nicholas J.G. Pearce; John A. Westgate; Guilherme A.R. Gualda; Emma Gatti; Ros F. Muhammad (Journal of Quaternary Science, 2020)
The Youngest Toba Tuff contains five distinct glass populations, identified from Ba, Sr and Y compositions, termed PI (lowest Ba) – PV (highest Ba), representing five compositionally distinct pre‐eruptive magma batches that fed the eruption. The PI–PV compositions display systematic changes, with higher FeO, CaO, MgO, TiO 2 and lower incompatible element concentrations in the low‐SiO 2 PIV/PV, than the high‐SiO 2 PI–PIII compositions. Glass shard abundances indicate PIV and PV were the least voluminous magma batches, and PI and PIII the most voluminous. Pressure estimates using rhyolite‐MELTS indicate PV magma equilibrated at ~6 km, and PI magma at ~3.8 km. Glass population proportions in distal tephra and proximal (caldera‐wall) material describe an eruption which commenced by emptying the deepest PIV and PV reservoirs, this being preferentially deposited in a narrow band across southern India (possibly due to jet‐stream and/or plinian eruption transport), and as abundant pumice clasts in the lowermost proximal ignimbrites. Later, shallower magma reservoirs erupted, with PI being the most abundant as the eruption ended, sourcing the majority of distal ash from co‐ignimbrite clouds (PI‐ and PIII‐dominant), where associated ignimbrites isolated earlier (PIV‐ and PV‐rich) deposits. This study shows how analysis of tephra glass compositional data can yield pre‐eruption magma volume estimates, and enable aspects of magma storage conditions and eruption dynamics to be described.

An ensemble procedure for pattern recognition of regional drought - Zulfiqar Ali; Ijaz Hussain; Muhammad Faisal; Muhammad Yousuf Shad; Elsayed E. Elashkar; Showkat Gani (International Journal of Climatology, 2020)
Drought being a complex natural hazard is challenging to monitor. Although standardized procedures for drought characterization are commonly used, the uncertainty about accurate drought characterization under various procedures always exists. Therefore, for effective drought mitigation policies, it is necessary to compare the performance of new and the existing drought procedures. In this study, we proposed a new procedure— The Drought Intensity Pattern Determinate (DIPD) to examine and compare the spatial‐temporal intensities of various drought episodes based on Standardized Drought Indices (SDI). The DIPD framework provides a new tool— The Drought Concentration Index ( DCI ) to understand the annual intensity of drought classes by alluding the observed frequencies of drought episodes. At the preliminary level of assessment, DIPD is employed at 52 meteorological stations of Pakistan, and compared three commonly used standardized drought indices: Standardized Precipitation Index (SPI), Standardized Evapotranspiration Index (SPEI) and Standardized Precipitation Temperature Index (SPTI). Exploratory analysis shows a mixed picture as all the drought indices behaving similar for some patterns of drought classes, while some classes show significant discrepancies. In addition, we assessed and compared the spatial distributions using spatial Poisson lognormal model by assuming SDI as a non‐Gaussian process for individual total classes of observed DCI. Results show that the proposed method has ability to incorporate the inner variability in patterns of drought classes. In summary, the DIPD provided a new regional based comparative framework, which accounts the all possible episodes of drought classes and effect of inner discrepancies among quantitative values of SDI.

Construction of homogeneous climatic regions by combining cluster analysis and L‐moment approach on the basis of Reconnaissance Drought Index for Pakistan - Hamd Ullah; Muhammad Akbar; Firdos Khan (International Journal of Climatology, 2020)
Drought is a natural hazard which has slow onset and assessment of its vulnerability is important for water resources management and sustainable development particularly in the most vulnerable areas to climate change and its worse impacts. Pakistan is facing acute water scarcity and regionalization of drought is a pre‐planning strategy for coping the severe condition of water management in the country. This study is conducted to identify homogenous climatic regions (HCRs) with respect to drought condition based on Reconnaissance Drought Index using climate data of 55 metrological stations across Pakistan. For this purpose two statistical methods, cluster analysis and L‐moments technique were used. First, cluster analysis was performed using site characteristics of the stations which identified five homogenous groups. Second, two statistical measures that is, discordancy measures and heterogeneity measure were implied after some regional adjustments, to satisfy the homogeneity of the homogenous groups developed in step one based on at‐site statistics of the stations using L‐moments technique. These statistical measures established validity of five homogeneous climatic regions for Pakistan. Third, to assess these HCRs several results using site characteristics and climate data of the stations were calculated which show that elevation has key role in the rainfall pattern and aridity of the regions. According to the results, there is high variability among these regions with respect to water recourses. First two regions consists most elevated areas with enough rainfall and glacier. Regions (3) and (4) include most vulnerable and drought‐prone areas of Sindh and Baluchistan provinces while Region (5) has enough rainfall in monsoon season. This study findings will help in adaptation, mitigation and future's planning regarding climate, water resources management, monitoring droughts and its projections etc. in different areas and fill the gaps in existing literature in Pakistan.

Rainfall reconstruction for the Karakoram region in Pakistan since 1540 CE reveals out‐of‐phase relationship in rainfall between the southern and northern slopes of the Hindukush‐Karakorum‐Western Himalaya region - Adam Khan; Feng Chen; Moinuddin Ahmed; Muhammad Usama Zafar (International Journal of Climatology, 2020)
Climate change has influenced the glaciers and water resources in the Hindukush‐Karakorum‐Himalaya region. The relatively short instrumental record of northern Pakistan makes long‐term climate change assessments difficult. In this paper, tree‐ring width chronologies were developed from two stands of spruce species ( Picea smithiana ) in the Karakoram region of northern Pakistan. The results of the correlation analysis revealed that tree‐ring growth of spruce was limited by annual (June–May) precipitation. Based on the regional chronology, we developed an annual precipitation reconstruction for the period 1540–2016 CE. The precipitation reconstruction equation accounts for 40% of the regional precipitation variance during the instrumental period 1946–2016. Dry episodes with rainfall below the 477‐year average occurred from 1569 to 1577, 1598 to 1612, 1621 to 1621, 1638 to 1654, 1673 to 1680, 1697 to 1720, 1728 to 1739, 1753 to 1761, 1777 to 1793, 1801 to 1840, 1860 to 1874, 1914 to 1932, 1960 to 1985, 1998 to 2011. Wet episodes occurred from 1540 to 1568, 1578 to 1597, 1613 to 1620, 1632 to 1637, 1655 to 1672, 1681 to 1696, 1721 to 1727, 1740 to 1752, 1762 to 1776, 1794 to 1800, 1841 to 1859, 1875 to 1913, 1933 to 1959, 1986 to 1997. Furthermore, the results of spatial correlation analyses show that the reconstructed precipitation represents the regional precipitation variations for northern Pakistan and nearby high‐altitude mountains. The out‐of‐phase relationship in tree‐ring records of the Karakoram region and surrounding areas suggests that the Karakoram was under the control of large‐scale ocean–atmosphere–land circulations on a decadal timescale in the past centuries. In addition, by the comparison between the precipitation reconstruction and the instrumental data, we found that the drought risk of Karakoram has increased in the past 70 years and that extreme events are likely to become more severe and more frequent under the backdrop of climatic warming.